Lithographic printing plate precursor, method for manufacturing lithographic printing plate, and printing method

By using an aluminum alloy plate and an anodized coating support in the lithographic printing plate original, combined with an infrared absorber and an acid chromogenic image recording layer, the spot-like chromogenic failure problem after passing through time is solved, and high visual recognition and printing quality are improved.

CN119768282APending Publication Date: 2025-04-04FUJIFILM CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202380061777.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-31
Filing Date
2023-08-25
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The original on-organic developing lithographic printing plates are prone to spot-like chromatic failures after passing through time during the manufacturing process, and the visual recognition is insufficient.

Method used

Using a support with an aluminum alloy plate and an anodized coating, the image recording layer contains an infrared absorber and an acid chromic agent. By adjusting the density of intermetallic compounds and the microporous structure of the anodized coating, chromic failures are suppressed and visual recognition is improved.

Benefits of technology

It effectively suppresses color failure after ejaculation, improves the visual recognition of the image exposure part, and ensures the printing quality of the lithographic printing plate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119768282A_ABST
    Figure CN119768282A_ABST
Patent Text Reader

Abstract

The present invention addresses the problem of providing an on-press developable lithographic printing original plate which suppresses color development failure after time and which has excellent visibility. The present invention also addresses the problem of providing a method for manufacturing a lithographic printing plate and a printing method. The lithographic printing plate precursor of the present invention is an on-press developing lithographic printing plate precursor having a support and an image recording layer, the support having an aluminum alloy plate and an anodized film disposed on the aluminum alloy plate, the density of intermetallic compounds having a major axis of 2.0 [mu] m or more on the surface of the support on the opposite side from the image recording layer is 1,000 / mm2 or less, the image recording layer contains an infrared absorbent and an acid chromophoric agent, and the color development coefficient of the acid chromophoric agent as determined by a predetermined measurement method is 20,000 or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a lithographic printing plate precursor, a method for manufacturing a lithographic printing plate, and a printing method. Background Art

[0002] Lithographic printing is a method that utilizes the mutual repulsion between water and oily inks to create a difference in ink adhesion on the surface of the lithographic printing plate by using the lipophilic image area of ​​the lithographic printing plate as the ink receiving area and the hydrophilic non-image area as the fountain solution receiving area (ink non-receiving area). The ink is then transferred to a printed material such as paper to perform printing by making the ink adhere only to the image area.

[0003] In order to produce a lithographic printing plate having such an oleophilic image area and a hydrophilic non-image area, a lithographic printing plate precursor (PS plate) having an oleophilic photosensitive resin layer (image recording layer) provided on a hydrophilic support is widely used. Generally, a lithographic printing plate is produced by the following method: after the lithographic printing plate precursor is exposed to an original image such as a high-contrast film (lithofilm), the portion of the image recording layer that becomes the image area is left, and the unnecessary image recording layer is removed by dissolving with an alkaline developer or an organic solvent, thereby exposing the hydrophilic support surface to form a non-image area.

[0004] As concern for the global environment increases, issues related to waste liquid accompanying wet processes such as development processes have received attention.

[0005] In order to solve the above problems, the development and plate making process can be simplified or eliminated. As one of the measures, a method called "on-press development" is being carried out. That is, after the lithographic printing plate precursor is exposed, it is directly mounted on the printing press without development treatment, and unnecessary parts of the image recording layer are removed at the initial stage of the printing process.

[0006] As a lithographic printing plate precursor used for such on-press development, the lithographic printing plate precursor described in Patent Document 1 can be cited, for example.

[0007] Patent document 1 describes a technology related to an on-press developing type lithographic printing plate precursor, which has a support and an image recording layer on the support, the image recording layer containing an initiator, an infrared absorber capable of donating electrons to the initiator, and a color body precursor, and the brightness change of the image recording layer before and after exposure with a specified infrared laser is greater than a specified value.

[0008] Previous technical literature

[0009] Patent Literature

[0010] Patent Document 1: International Publication No. 2020 / 262692 Summary of the invention

[0011] Technical issues to be solved by the invention

[0012] The present inventors, with reference to Patent Document 1, have studied the various physical properties of the planographic printing plate precursor and have found that sometimes spot-like coloration failure (tiny dot-like coloration) occurs in the appearance of the planographic printing plate precursor after a specified period of time from manufacture, and that further improvements are needed to suppress such spot-like coloration failure after a period of time.

[0013] An object of the present invention is to provide an on-press developing type planographic printing plate precursor which has excellent visibility and suppresses color development failure after aging.

[0014] Furthermore, an object of the present invention is to provide a method for producing a lithographic printing plate and a printing method.

[0015] Means for solving technical problems

[0016] The present inventors have found that the above-mentioned problems can be solved by the following configuration.

[0017] [1] A lithographic printing plate precursor, which is an on-press developing type lithographic printing plate precursor having a support and an image recording layer,

[0018] The support body comprises an aluminum alloy plate and an anodic oxide film disposed on the aluminum alloy plate, and the density of intermetallic compounds having a major diameter of 2.0 μm or more on a surface of the support body opposite to the image recording layer is 1,000 / mm 2 Hereinafter, the image recording layer contains an infrared absorber and an acid coloring agent, and the color development coefficient of the acid coloring agent determined by the measurement X described later is 20,000 or more.

[0019] [2] The lithographic printing plate precursor according to [1], wherein

[0020] The density of the intermetallic compounds having a major diameter of 2.0 μm or more on the surface of the support opposite to the image recording layer is 500 / mm 2 the following.

[0021] [3] The lithographic printing plate precursor according to [1] or [2], wherein

[0022] The density of the intermetallic compounds having a major diameter of 2.0 μm or more on the surface of the support opposite to the image recording layer is 10 / mm 2 the following.

[0023] [4] The lithographic printing plate precursor according to any one of [1] to [3], wherein

[0024] The density of the recessed portions having a depth of 0.7 μm or more from the average surface obtained by measuring the range of 400 μm×400 μm on the surface of the anodized film side of the support body using a non-contact three-dimensional roughness meter was 3,000 / mm. 2 above.

[0025] [5] The lithographic printing plate precursor according to any one of [1] to [4], wherein

[0026] The actual area Sx obtained by the approximate three-point method based on the three-dimensional data obtained by measuring 256×256 points in a range of 25μm×25μm on the surface of the above-mentioned anodized coating side of the above-mentioned support using an atomic force microscope and the geometrically measured area S0 of the surface of the above-mentioned anodized coating side of the above-mentioned support, the surface area ratio ΔS calculated by the following formula (S1) is greater than 25%.

[0027] [6] The lithographic printing plate precursor according to any one of [1] to [5], wherein

[0028] The above-mentioned anodized film has micropores extending from the surface of the above-mentioned anodized film in the depth direction, and the above-mentioned micropores include: a large-diameter pore portion, which extends from the surface of the above-mentioned anodized film in the depth direction; and a small-diameter pore portion, which is connected to the bottom of the above-mentioned large-diameter pore portion and extends in the depth direction; the average diameter of the above-mentioned large-diameter pore portion at the surface of the above-mentioned anodized film is 15 to 50nm, and the depth of the above-mentioned large-diameter pore portion is 30 to 1,000nm, and the average diameter of the above-mentioned small-diameter pore portion at the connection position with the above-mentioned large-diameter pore portion is less than 15nm, and the depth of the above-mentioned small-diameter pore portion is 300 to 3,000nm.

[0029] [7] The lithographic printing plate precursor according to any one of [1] to [5], wherein

[0030] The above-mentioned anodized film has micropores extending from the surface of the anodized film along the depth direction, and the micropores include: an upper pore portion, extending from the surface of the anodized film along the depth direction; a middle pore portion, which is connected to the bottom of the upper pore portion and extends along the depth direction; and a lower pore portion, which is connected to the bottom of the middle pore portion and extends to the bottom of the micropore along the depth direction, the average diameter of the upper pore portion at the surface of the anodized film is 15 to 50 nm, the depth of the upper pore portion is 30 to 1,000 nm, the maximum diameter of the middle pore portion is 20 to 100 nm and is larger than the average diameter of the upper pore portion at the surface of the anodized film, the average diameter of the lower pore portion at the connection position with the middle pore portion is less than 20 nm, and the depth of the lower pore portion is 500 to 3,000 nm.

[0031] [8] The lithographic printing plate precursor according to any one of [1] to [7], wherein

[0032] The anodized film has micropores extending from the surface of the anodized film in the depth direction, and the density of the micropores on the surface of the anodized film is 400 to 1500 micropores / μm. 2 The opening ratio of the surface of the anodized film based on the micropores is 30 to 85%.

[0033] [9] The lithographic printing plate precursor according to any one of [1] to [8], wherein

[0034] The color development coefficient of the acid color developing agent determined by the above-mentioned measurement X is 20,000 to 100,000.

[0035]

[10] The lithographic printing plate precursor according to any one of [1] to [9], wherein

[0036] The color body generated from the acid coloring agent has an absorption maximum wavelength λmax in the wavelength range of 380 to 750 nm in the range of 500 to 650 nm.

[0037]

[11] The lithographic printing plate precursor according to any one of [1] to

[10] , wherein

[0038] The acid coloring agent has at least one of the groups represented by the formula (1a) to (1d) described below.

[0039]

[12] The lithographic printing plate precursor according to

[11] , wherein

[0040] The acid coloring agent has any of the structures represented by the formulae (2a) to (2f) described below.

[0041]

[13] The lithographic printing plate precursor according to

[11] , wherein

[0042] The acid coloring agent includes a compound represented by the formula (3a) described later or a compound represented by the formula (3b).

[0043]

[14] The lithographic printing plate precursor according to any one of [1] to

[13] , wherein

[0044] The image recording layer further includes a polymerization initiator, and the polymerization initiator includes an electron accepting polymerization initiator and an electron donating polymerization initiator.

[0045]

[15] The lithographic printing plate precursor according to

[14] , wherein

[0046] The electron accepting polymerization initiator is an onium salt compound, and the electron donating polymerization initiator is a borate compound.

[0047]

[16] The lithographic printing plate precursor according to

[14] or

[15] , wherein

[0048] The total content of the electron accepting polymerization initiator and the electron donating polymerization initiator is 1.0 molar equivalent or more relative to the content of the acid color forming agent.

[0049]

[17] The lithographic printing plate precursor according to any one of

[14] to

[16] , wherein

[0050] The value obtained by subtracting the lowest unoccupied molecular orbital of the infrared absorber from the lowest unoccupied molecular orbital of the electron accepting polymerization initiator is 0.55 eV or less.

[0051]

[18] The lithographic printing plate precursor according to any one of [1] to

[17] , wherein

[0052] The image recording layer further contains polymer particles.

[0053]

[19] The lithographic printing plate precursor according to

[18] , wherein

[0054] The above-mentioned polymer particles are microgels.

[0055]

[20] The lithographic printing plate precursor according to

[18] , wherein

[0056] The polymer particles include a polymer having a hydrophobic main chain,

[0057] The polymer comprises a structural unit having a cyano side group directly bonded to the hydrophobic main chain and a structural unit having a side group comprising a hydrophilic polyalkylene oxide segment.

[0058]

[21] The lithographic printing plate precursor according to any one of [1] to

[20] , wherein

[0059] The infrared absorbent includes a decomposable infrared absorbent that is decomposed by exposure to infrared rays.

[0060]

[22] The lithographic printing plate precursor according to

[21] , wherein

[0061] The decomposable infrared absorber is a compound represented by the formula (A) described below.

[0062]

[23] The lithographic printing plate precursor according to any one of [1] to

[22] , further comprising a protective layer on the image recording layer.

[0063]

[24] The lithographic printing plate precursor according to

[23] , wherein

[0064] The protective layer contains a color body precursor.

[0065]

[25] The lithographic printing plate precursor according to

[24] , wherein

[0066] The color body precursor contains an infrared absorber.

[0067]

[26] The lithographic printing plate precursor according to

[24] or

[25] , wherein

[0068] The color body precursor contains a decomposable infrared absorber that is decomposed by exposure to infrared rays.

[0069]

[27] A method for manufacturing a lithographic printing plate, comprising: an exposure step of exposing the image recording layer of the lithographic printing plate original described in any one of claims [1] to

[26] to an image state to form an exposed portion and an unexposed portion; and an on-press development step of supplying at least one of printing ink and fountain solution on a printing press to remove the unexposed portion of the image recording layer exposed to an image state, thereby manufacturing a lithographic printing plate.

[0070]

[28] A printing method, comprising: an exposure step of exposing the image recording layer of the planographic printing plate original described in any one of claims [1] to

[26] to an image state to form an exposed portion and an unexposed portion; an on-press development step of supplying at least one of printing ink and fountain solution on a printing press to remove the unexposed portion of the image recording layer exposed to an image state, thereby producing a planographic printing plate; and a printing step of printing using the produced planographic printing plate.

[0071] Effects of the Invention

[0072] According to the present invention, it is possible to provide an on-press developing type planographic printing plate precursor which has excellent visibility and suppresses color development failure over time.

[0073] Furthermore, according to the present invention, a method for producing a planographic printing plate and a printing method can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0074] Figure 1 This is a schematic cross-sectional view showing an example of the structure of the planographic printing plate precursor of the present invention.

[0075] Figure 2 2 shows an example of an image obtained by photographing the surface of the support of the lithographic printing plate precursor on the opposite side to the image recording layer using a scanning electron microscope.

[0076] Figure 32 shows an example of an image obtained by photographing the surface of the support of the lithographic printing plate precursor on the opposite side to the image recording layer using a scanning electron microscope.

[0077] Figure 4 This is a schematic cross-sectional view showing an example of an embodiment of an anodic oxide film.

[0078] Figure 5 It is a schematic cross-sectional view showing another example of the embodiment of the anodized film.

[0079] Figure 6 This is a graph showing an example of an alternating waveform current waveform diagram used in a hydrochloric acid electrolysis treatment in a method for producing a support body.

[0080] Figure 7 This is a side view showing an example of a radial type unit used in a hydrochloric acid electrolysis treatment using an alternating current in a method for manufacturing a support body.

[0081] Figure 8 This is a schematic diagram of an anodizing treatment apparatus used in anodizing treatment in the production of a support. DETAILED DESCRIPTION

[0082] Hereinafter, the present invention will be described in detail.

[0083] Although the description of the constituent elements described below may be made based on representative embodiments of the present invention, the present invention is not limited to such embodiments.

[0084] In addition, in this specification, the numerical range expressed using "to" means a range including the numerical values ​​described before and after "to" as the lower limit and the upper limit.

[0085] In this specification, “(meth)acrylic acid” is a term used as a concept including both acrylic acid and methacrylic acid, and “(meth)acryloyl” is a term used as a concept including both acryloyl and methacryloyl.

[0086] The term "process" in this specification includes not only an independent process but also a process that cannot be clearly distinguished from other processes as long as the intended purpose of the process can be achieved.

[0087] Unless otherwise specified, the measurements of various physical properties were performed at 25°C.

[0088] Unless otherwise specified, in the present specification, each component in the composition or each structural unit in the polymer may be contained alone or in combination of two or more.

[0089] In this specification, regarding the amount of each component in a composition or the amount of each structural unit in a polymer, when there are multiple substances or structural units corresponding to each component in the composition or each structural unit in the polymer, unless otherwise specified, it means the total amount of the corresponding multiple substances present in the composition or the corresponding multiple structural units present in the polymer.

[0090] In the present specification, a combination of two or more preferred aspects is a more preferred aspect.

[0091] The weight average molecular weight (Mw) and number average molecular weight (Mn) in this specification, unless otherwise specified, are molecular weights calculated using polystyrene as a standard substance by detecting the molecular weight of the target compound in a THF (tetrahydrofuran) solvent using a gel permeation chromatography (GPC) analysis apparatus using a column of TSKgel GMHxL, TSKgel G4000HxL, or TSKgel G2000HxL (all product names manufactured by TOSOH CORPORATION) by a differential refractometer.

[0092] In this specification, the term "lithographic printing plate original" includes not only lithographic printing plate originals but also discarded plate originals. Furthermore, the term "lithographic printing plate" includes not only lithographic printing plates produced by performing exposure, development and other operations on lithographic printing plate originals as required, but also discarded plates. In the case of discarded plate originals, exposure and development operations are not necessarily required. In addition, discarded plates refer to lithographic printing plate originals used to be mounted on unused plate cylinders when a portion of the layout is printed in monochrome or two-color in color newspaper printing, for example.

[0093] In this specification, the term "on-press development type" means that the lithographic printing plate precursor can be used for on-press development.

[0094] In this specification, “excellent printing durability” means that a large number of sheets can be printed on a lithographic printing plate.

[0095] [Original lithographic edition]

[0096] The lithographic printing plate precursor according to the present invention is an on-press development type lithographic printing plate precursor having a support and an image recording layer, wherein:

[0097] The support body comprises an aluminum alloy plate and an anodized film disposed on the aluminum alloy plate.

[0098] The density of the intermetallic compounds having a major diameter of 2.0 μm or more on the surface of the support opposite to the image recording layer is 1,000 / mm 2 the following,

[0099] The image recording layer contains an infrared absorber and an acid color former.

[0100] The color development coefficient of the acid color developing agent determined by the measurement X described later is 20,000 or more.

[0101] As described above, the present inventors have found that mottled color development failure (microscopic dot-shaped color development contamination) may occur in the appearance of a lithographic printing plate precursor after a predetermined period of time has passed since its production.

[0102] The present inventors studied the cause of the spot-like color development failure (hereinafter also referred to as "color development failure over time") generated in the lithographic printing plate precursor after the aging, and found that in order to improve the visibility of the exposed part in the plate inspection operation of confirming the exposed part after the lithographic printing plate precursor is subjected to image exposure (hereinafter also referred to as "visual recognition"), when an acid coloring agent with relatively high color development property is used as a color body precursor, the tendency of color development failure over time is easy to occur. In addition, the present inventors found that even when such an acid coloring agent is used, by using an aluminum alloy plate having an intermetallic compound (hereinafter also referred to as "specific intermetallic compound") with a major diameter of 2.0 μm or more and a number of the compounds being less than a specified value as a support of the lithographic printing plate precursor, the color development failure over time can be effectively suppressed while maintaining excellent visual recognition, thereby completing the present invention.

[0103] The cause of the color development failure over time is believed to be the chemical change of the acid coloring agent on the color body due to the corrosion reaction with the intermetallic compound present in the aluminum alloy plate. It is speculated that by reducing the number of specific intermetallic compounds in the aluminum alloy plate, a planographic printing plate precursor can be provided that has excellent visual recognition based on the acid coloring agent while suppressing the color development failure over time.

[0104] Figure 1 This is a schematic cross-sectional view showing an example of the structure of the planographic printing plate precursor of the present invention.

[0105] Figure 1 The planographic printing plate precursor 10 shown has a support 11 and an image recording layer 12. The support 11 has an aluminum alloy plate 13 and an anodized film 14 disposed on the aluminum alloy plate 13.

[0106] In addition, the structure of the planographic printing plate precursor is not limited to Figure 1 For example, as described later, a primer layer may be provided between the support and the image recording layer, or a protective layer may be provided on the surface of the image recording layer on the side opposite to the support.

[0107] Hereinafter, each structure of the planographic printing plate precursor according to the present invention will be described.

[0108] 〔Supporting body〕

[0109] The planographic printing plate precursor according to the present invention comprises a support including an aluminum alloy plate and an anodic oxide film disposed on the aluminum alloy plate.

[0110] The anodic oxide film in the support is located on the image recording layer side. That is, the planographic printing plate precursor has the aluminum alloy plate, the anodic oxide film, and the image recording layer in this order.

[0111] Hereinafter, unless otherwise specified, the term "support" means a support including an aluminum alloy plate and an anodized film disposed on the aluminum alloy plate.

[0112] <Density of Intermetallic Compounds>

[0113] In the lithographic printing plate precursor according to the present invention, the density of the specific intermetallic compound on the surface of the support on the side opposite to the image recording layer is 1,000 pieces / mm 2 the following.

[0114] Here, intermetallic compounds refer to compounds that are insoluble in aluminum alloys and crystallize in the aluminum alloy in the form of eutectic ("Basics and Industrial Technology of Aluminum Materials", published by the Light Metals Association, page 32, etc.). In addition, it is known that intermetallic compounds are usually composed of two or more metal elements, and the atomic ratio of the components is not necessarily a stoichiometric ratio.

[0115] Examples of the intermetallic compound include Al 3 Fe、Al 6 Fe、Al m Fe、Al 6 Mn、Al 3 Ti and Al 2 Intermetallic compounds composed of two elements such as Cu; intermetallic compounds composed of three elements such as α-AlFeSi and p-AlFeSi; and intermetallic compounds composed of four elements such as α-AlFeMnSi and β-AlFeMnSi.

[0116] In this specification, the “long diameter” of the intermetallic compound refers to the longest diameter of the intermetallic compound shown in an image obtained by observing the surface of the support on the side opposite to the image recording layer from the normal direction.

[0117] In addition, the major axis and density of the above-mentioned intermetallic compound are measured by the following method.

[0118] First, the surface of the support body including the anodized film and the aluminum alloy plate on the side opposite to the image recording layer (hereinafter also referred to as the "target surface") is wiped with acetone to be used as a measurement sample. In the case where inorganic matter is attached to the target surface, the inorganic matter on the target surface is removed by a suitable removal method. When it is difficult to remove, mechanical grinding and mirror finishing can be performed on the target surface.

[0119] Next, a reflected electron image of the target surface is captured under the following conditions using a scanning electron microscope (SEM: Scanning Electron Microscope) (for example, "SU8010" manufactured by Hitachi High-Technologies Corporation).

[0120] Accelerating voltage: 12.0 kV

[0121] Magnification: 2000 times

[0122] Probe setting: High

[0123] Gain primary setting: Medium

[0124] Gain next stage setting: High

[0125] Next, five randomly selected locations on the surface of the object (1 mm when magnified 370 times) were analyzed. 2 The area of ​​the object is measured by scanning electron microscope (SEM) and an image of the reflected electron image is taken from the normal direction of the object surface. In the obtained image, the intermetallic compound present on the surface of the object appears as a particle-shaped area that is brighter than the surrounding area. The size of the area representing the particle shape of the intermetallic compound is measured, and the number of areas with a major diameter of more than 2.0 μm is calculated. The density of the specific intermetallic compound is obtained by calculating the arithmetic mean of the number of areas with a major diameter of more than 2.0 μm from the SEM images of 5 locations and converting it to per unit area (unit: pieces / mm 2 ).

[0126] When calculating the density of the intermetallic compound according to the SEM image of the surface of the object, for example, the image analysis software can be used as follows. The images of the 5 captured parts are saved in JPEG format and converted to bmp (bitmap) format using MS-Paint (manufactured by Microsoft Corporation). After the bmp format file is read into the image analysis software ImageFactory Ver.3.2 Japanese version (manufactured by Ashahi Hi-tech Co., Ltd.) and image analysis is performed, the image is subjected to static binary processing. The number of granular regions of bright white color corresponding to the intermetallic compound is counted from the obtained image, and the major diameter of each granular region is specified as a feature value to obtain the particle size distribution. The density of the intermetallic compound whose major diameter on the surface of the object is within a specified range (2.0 μm or more, etc.) can be calculated based on the result of the particle size distribution calculated from the image data of the 5 parts.

[0127] exist Figure 2 and Figure 3 An example of an image obtained by photographing the target surface of a support body using a SEM is shown in FIG. It can be seen that in each image, a white particle-like region corresponding to the intermetallic compound is reflected in the area surrounded by a dotted or solid circle. The "long axis" of the metal compound is measured as the maximum value of the distance between two parallel straight lines that sandwich the displayed particle-like region and are connected to the contour line of the particle-like region.

[0128] Figure 2 The image shown is an example of a SEM image of the target surface of the support body possessed by the planographic printing plate precursor of the present invention. Figure 2 In the image shown, the long diameters of the intermetallic compound particles surrounded by the dotted circle are all less than 2.0 μm, and no particle images with a long diameter of 2.0 μm or more are observed. Figure 3 In the image shown, four long axes enclosed by solid circles are observed (in Figure 3 The particle image of the intermetallic compound (represented by "L" in the figure) is larger than 2.0 μm.

[0129] Furthermore, the major diameter and density of the intermetallic compound on the target surface of the support can also be measured by analyzing the target surface of the support using an electron probe microanalyzer (EPMA) to obtain the composition distribution on the target surface.

[0130] From the viewpoint of achieving more excellent effects of the present invention, the density of the specific intermetallic compound on the surface of the support opposite to the image recording layer is preferably 500 particles / mm 2 Below, more preferably 100 pieces / mm 2Below, more preferably 10 / mm 2 Below. The lower limit can be 0 pieces / mm 2 .

[0131] In order to achieve a more excellent effect of the present invention, the density of the intermetallic compounds having a major diameter of 0.1 μm or more and less than 2.0 μm on the surface of the support opposite to the image recording layer is preferably 10,000 / mm. 2 More than 25,000 pieces / mm 2 More preferably, 35,000 pieces / mm 2 above.

[0132] The upper limit is not particularly limited, but is preferably 90,000 pieces / mm from the viewpoint of better color development failure over time. 2 The number of the plurality of electrodes is preferably 70,000 or less, and more preferably 70,000 or less

[0133] A support body having a density of the specific intermetallic compound on the surface of the object within the above range can be produced by setting conditions such as the cooling rate when casting the aluminum alloy, for example, in a method for producing a support body described below.

[0134] Similarly, a support having an intermetallic compound density of 0.1 μm or more and less than 2.0 μm in the major axis on the target surface can be produced by setting conditions such as the cooling rate when casting the aluminum alloy in the support production method described below.

[0135] <Aluminum Alloy Plate>

[0136] The aluminum alloy plate is composed of a metal containing dimensionally stable aluminum as a main component and also containing a trace amount of foreign elements.

[0137] Examples of heterogeneous elements contained in the aluminum alloy constituting the aluminum alloy plate include silicon, iron, manganese, copper, magnesium, chromium, zinc, bismuth, nickel, and titanium. Among them, at least one heterogeneous element selected from silicon, iron, manganese, titanium, and copper is contained in the aluminum alloy plate as a heterogeneous element constituting an intermetallic compound with aluminum. The total content of heterogeneous elements in the aluminum alloy is preferably 10% by mass or less.

[0138] The composition of the aluminum alloy plate is not particularly limited, and a known material (for example, a material satisfying standards such as JIS A1050, JIS A 1100, JIS A 3103, and JIS A 3005) can be used appropriately.

[0139] As the composition of the aluminum alloy plate, for example, the following compositions can be mentioned.

[0140] Si: 0.03-0.20 mass%

[0141] Fe: 0.11-0.45 mass%

[0142] Al: the remainder (e.g. 99 mass % or more)

[0143] The aluminum alloy plate may contain the above-mentioned different elements as alloy components.

[0144] The content of Si contained in the aluminum alloy plate is preferably 0.03 to 0.20 mass %, more preferably 0.04 to 0.18 mass %, and further preferably 0.05 to 0.15 mass %.

[0145] This is because when the Si content is within this range, even when anodizing treatment is performed after electrolytic roughening treatment, defects are less likely to occur in the anodized film, and the corrosion contamination suppression property as a planographic printing plate becomes good.

[0146] Si is an element contained in the Al metal ingot as a raw material as an inevitable impurity at about 0.03 to 0.1 mass %, and is usually intentionally added in a small amount in order to prevent variations due to differences in raw materials.

[0147] The solid solution amount of Si in the aluminum alloy plate is preferably 120 to 600 mass ppm, more preferably 150 to 600 mass ppm, and further preferably 150 to 500 mass ppm.

[0148] When the solid solution amount of Si is within this range, the anodic oxide film becomes uniform, and micropores having average opening diameters of 0.01 to 0.05 μm and 0.05 to 1.5 μm are uniformly formed over the entire surface.

[0149] The amount of Fe contained in the aluminum alloy plate that is solid-dissolved in aluminum is small, and most of it remains as an intermetallic compound.

[0150] The content of Fe contained in the aluminum alloy plate is preferably 0.11 to 0.45 mass %, more preferably 0.15 to 0.45 mass %, and further preferably 0.20 to 0.43 mass %.

[0151] When the Fe content is within this range, Fe is dispersed as fine intermetallic compounds, which function as starting points for the electrolytic roughening treatment, and as a result, the anodic oxide film becomes uniform.

[0152] Furthermore, from the viewpoint of easily manufacturing an aluminum alloy plate having a predetermined amount of intermetallic compounds having a major axis of 0.1 μm or more and less than 2.0 μm, the solid solution amount of Fe in the aluminum alloy plate is preferably 100 ppm or less, more preferably 50 ppm or less, and further preferably 40 ppm or less.

[0153] Furthermore, from the viewpoint of obtaining more excellent heat resistance of the aluminum alloy plate, the solid solution amount of Fe in the aluminum alloy plate is preferably 10 ppm or more, and more preferably 20 ppm or more.

[0154] The aluminum alloy plate may contain Cu. When the aluminum alloy plate contains Cu, the content is preferably 0.030 mass % or less from the viewpoint of maintaining uniformity of electrolytic roughening.

[0155] The aluminum alloy plate may contain grain refining elements such as Ti and B to prevent cracks from occurring during casting. When the aluminum alloy plate contains Ti, for example, Ti can be added in a range of 0.05 mass % or less. When the aluminum alloy plate contains B, for example, B can be added in a range of 0.02 mass % or less.

[0156] The aluminum alloy plate may contain inevitable impurities.

[0157] Examples of the inevitable impurities include Mg, Mn, Zn, Cr, Zr, V, Zn, and Be, and each of these may be contained in an amount of 0.05 mass % or less.

[0158] Furthermore, most of the inevitable impurities are contained in the Al metal ingot. The inevitable impurities do not impair the effects of the present invention as long as they are impurities contained in a metal ingot having an Al purity of 99.5%.

[0159] Unavoidable impurities may be contained in an amount described in, for example, LF Mondolfo's "Aluminum Alloys: Structure and properties" (1976).

[0160] The remainder of the aluminum alloy plate other than the above-mentioned foreign elements and inevitable impurities is Al.

[0161] The width of the aluminum alloy plate is preferably about 400 to 2,000 mm, and the thickness is preferably 0.1 to 0.6 mm, more preferably 0.1 to 0.5 mm. Both the width and thickness can be appropriately changed according to the size of the printing press, the size of the printing plate, and the user's wishes.

[0162] <Anodized coating>

[0163] The anodic oxide film included in the support is a film generally formed on the surface of an aluminum alloy plate by anodizing treatment.

[0164] The amount of anodized film is not particularly limited, but is preferably 2.0 g / m 2 More preferably 3.2 g / m 2 Above, more preferably 3.4 g / m 2There is no particular upper limit, but 5.0 g / m 2 The following situations are more common, preferably 4.0g / m 2 the following.

[0165] (Micropores)

[0166] The anodized film preferably has micropores (hereinafter also referred to as "micropores") formed on the surface of the image recording layer side of the anodized film (hereinafter also referred to as "film surface"). The micropores extend from the film surface in the depth direction (direction toward the aluminum alloy plate, thickness direction). In addition, a plurality of micropores are formed on the film surface, and in most cases, they are evenly distributed on the film surface.

[0167] In addition, the term "micropore" is a term generally used as a term to indicate the pore structure formed in the anodized film by anodizing treatment, and does not define the size of the pore.

[0168] The density of micropores on the surface of the film is not particularly limited, but is preferably 200 to 2,000 pores / μm. 2 , more preferably 400 to 1,500 / μm 2 .

[0169] The density of micropores is as follows: The film surface was observed using a field emission scanning electron microscope (FE-SEM) at a magnification of 150,000 times, and 400×600 nm was randomly selected from four images obtained by observing four different locations. 2 The number of micropores present in the measurement area is measured, the number of micropores per unit area of ​​the measurement area is calculated for each image, and the calculated values ​​are arithmetic averaged to obtain a value.

[0170] From the viewpoint of achieving better printing durability, the average diameter (average opening diameter) of the micropores on the surface of the coating is preferably 15 to 100 nm, more preferably 20 to 50 nm, and further preferably 23 to 35 nm.

[0171] The average diameter of the micropores is as follows: The film surface was observed using a field emission scanning electron microscope (FE-SEM) at a magnification of 150,000 times, and 400×600 nm was randomly selected from four images obtained by observing four different locations. 2 The diameter of the micropores present in the measurement area is measured, and the value obtained by arithmetic averaging all the measured values.

[0172] When the shape of the openings of the film surface based on micropores is not circular, the equivalent circle diameter is used. The “equivalent circle diameter” refers to the diameter of a circle having the same projected area as the projected area of ​​the openings.

[0173] The opening ratio of the film surface based on micropores is preferably 10 to 90%, more preferably 30 to 85%.

[0174] The above-mentioned opening ratio refers to a value calculated by converting the value obtained by multiplying the average area of ​​the opening portion based on the micropores by the density (number density) of the micropores on the surface of the coating into a percentage, and the average area of ​​the opening portion based on the micropores is calculated using the average radius obtained by dividing the average diameter of the micropores on the surface of the coating by 2.

[0175] The depth of the micropores is not particularly limited, but is preferably 10 to 1000 nm, more preferably 50 to 500 nm, and further preferably 70 to 200 nm. The depth of the micropores refers to the distance in the depth direction from the micropore film surface to the deepest part of the bottom of the micropores.

[0176] The depth of the micropores is the following value: a cross section along the depth direction of the anodized coating is observed using a FE-SEM at a magnification of 150,000 times, 25 or more micropores are randomly selected from four observation images obtained by observing four different cross sections, the depth of the selected micropores is measured, and the measured values ​​are arithmetic averaged to obtain the value.

[0177] The shape of the micropore is not particularly limited, and can be a generally straight tube (generally cylindrical) in which the diameter of the micropore is almost constant in the depth direction, or can be a micropore whose diameter changes continuously or discontinuously in the depth direction. As the shape of the micropore whose diameter changes in the depth direction, a conical shape whose diameter decreases in the depth direction, a truncated cone shape whose diameter increases in the depth direction, and a shape in which a plurality of holes having different diameters are connected along the depth direction as described later can be cited.

[0178] Furthermore, the shape of the bottom of the micropore is not particularly limited, and may be curved (convex) or flat.

[0179] Figure 4 This is a schematic cross-sectional view showing an example of an embodiment of an anodic oxide film. Figure 4 The illustrated anodized film 14A has micropores 20 including large-diameter pore portions 22 and small-diameter pore portions 24 .

[0180] The large-diameter hole portion 22 extends from the coating surface 21 (the surface of the anodized coating 14A on the image recording layer side not shown) to a depth D1 (reference Figure 4 ) is connected to the small diameter hole portion 24 at the bottom 22A. The small diameter hole portion 24 is connected to the bottom 22A of the large diameter hole portion 22 and further extends from the connecting position 23 to a depth D2 (reference Figure 4 ) position of the hole portion.

[0181] The average diameter of the large-diameter pores 22 in the coating surface 21 is the same as the average diameter of the micropores in the coating surface, and the preferred range and measurement method of the average diameter are also the same.

[0182] The depth D1 of the large-diameter pores 22 (the distance from the coating surface 21 to the bottom 22A) is preferably 10 to 1,000 nm, more preferably 20 to 1,000 nm, further preferably 30 to 500 nm, and particularly preferably 50 to 200 nm.

[0183] The depth D1 of the large-diameter hole portion 22 and the depth D2 of the small-diameter hole portion 24 can be measured according to the above-mentioned method for measuring the depth of micropores.

[0184] The shape of the large diameter hole 22 is not limited to Figure 4 The substantially straight tube shape (substantially cylindrical shape) shown may be, for example, a cone shape whose diameter decreases toward the depth direction or a truncated cone shape whose diameter increases toward the depth direction. The shape of the large-diameter hole portion 22 is preferably a substantially straight tube shape.

[0185] The shape of the bottom 22A of the large-diameter hole portion 22 is not particularly limited, and may be a curved surface (convex shape) or a flat surface.

[0186] The small diameter hole portion 24 is a hole portion that communicates with the bottom portion 22A of the large diameter hole portion 22 and extends from the communication position 23 further in the depth direction. Figure 4 In the micropore 20 shown, one large-diameter pore portion 22 communicates with one small-diameter pore portion 24 , but two or more small-diameter pore portions may communicate with one large-diameter pore portion.

[0187] The average diameter at the communication position 23 of the small-diameter pore portion 24 is not particularly limited as long as it is smaller than the average diameter of the large-diameter pore portion 22, and is preferably 15 nm or less, more preferably 13 nm or less, further preferably 11 nm or less, and particularly preferably 10 nm or less. The lower limit is not particularly limited, but is preferably 5 nm or more.

[0188] The average diameter of the communicating position of the small-diameter pores is as follows: The film surface was observed using a field emission scanning electron microscope (FE-SEM) at a magnification of 150,000 times, and 400×600 nm was randomly selected from 4 images obtained by observing 4 different locations. 2 The diameter of the small-diameter pores existing in the measurement area is measured, and the value obtained by arithmetic averaging all the measured values.

[0189] When measuring the above-mentioned average diameter of the small-diameter pore portion, if the large-diameter pore portion is deep, the upper portion of the anodized coating (a certain area of ​​the large-diameter pore portion) can be cut as needed (for example, cutting by argon gas), and then the surface of the exposed anodized coating can be observed using FE-SEM to calculate the average diameter of the connecting position between the small-diameter pore portion and the large-diameter pore portion according to the above method.

[0190] Furthermore, when the shape of the small-diameter hole portion at the communication position with the large-diameter hole portion is not circular, the circle equivalent diameter is used.

[0191] The depth D2 of the small-diameter hole portion 24 (the distance from the communication position 23 with the large-diameter hole portion 22 to the bottom 24A of the small-diameter hole portion 24) is preferably 100 to 5,000 nm, more preferably 200 to 4,000 nm, further preferably 300 to 3,000 nm, and particularly preferably 500 to 1,800 nm.

[0192] The shape of the small-diameter hole 24 is not limited to Figure 4 The substantially straight tube shape (substantially cylindrical shape) shown may be, for example, a cone shape whose diameter decreases toward the depth direction or a truncated cone shape whose diameter increases toward the depth direction. The shape of the small-diameter hole portion 24 is preferably substantially straight tube shape.

[0193] The shape of the bottom 24A of the small-diameter hole portion 24 is not particularly limited, and may be a curved surface (convex shape) or a flat surface.

[0194] The ratio of the average diameter in the coating surface 21 of the large diameter hole portion 22 to the average diameter at the connecting position 23 of the small diameter hole portion 24 ((average diameter at the coating surface of the large diameter hole portion) / (average diameter at the connecting position of the small diameter hole portion)) is preferably 1.1 to 13, and more preferably 2.5 to 6.5.

[0195] Furthermore, the ratio (D1 / D2) of the depth D1 of the large-diameter hole portion 22 to the depth D2 of the small-diameter hole portion 24 is preferably 0.005 to 50, and more preferably 0.025 to 40.

[0196] As a preferred example of a micropore including a large-diameter pore portion and a small-diameter pore portion, there can be cited a micropore including a large-diameter pore portion and a small-diameter pore portion, wherein the depth D1 of the large-diameter pore portion from the coating surface is 30 to 1,000 nm and the average diameter at the coating surface is 15 to 50 nm, and the depth D2 of the small-diameter pore portion from the connection position with the large-diameter pore portion is 300 to 3,000 nm and the average diameter at the connection position with the large-diameter pore portion is 15 nm or less. Among the above-mentioned micropores, micropores having the above-mentioned preferred modes of average diameter, depth and shape of each pore portion are more preferred.

[0197] Figure 5 It is a schematic cross-sectional view showing another example of the embodiment of the anodized film. Figure 5 The anodized film 14B shown has micropores 30 including upper pores 32, middle pores 34, and lower pores 36. In the micropores 30, the upper pores 32, the middle pores 34, and the lower pores 36 are connected to each other.

[0198] The upper hole portion 32 extends from the coating surface 31 (the surface of the anodized coating 14B on the image recording layer side not shown) to a depth D3 (reference Figure 5 ) is connected to the middle hole 34 at the bottom 32A.

[0199] The middle hole portion 34 is connected to the bottom 32A of the upper hole portion 32 and further extends from the connecting position 33 with the upper hole portion 32 to a depth D4 (refer to Figure 5 ) is connected to the lower hole portion 36 in the bottom 34A.

[0200] The lower hole portion 36 is connected to the bottom 34A of the middle hole portion 34 and further extends from the connecting position 35 with the middle hole portion 34 to a position at a depth D5 (refer to Figure 5 ) is located at the hole portion of the bottom 36A.

[0201] The average diameter of the upper pores 32 in the coating surface 31 is the same as the average diameter of the micropores in the coating surface, and the preferred range and measurement method of the average diameter are also the same.

[0202] The depth D3 of the upper hole portion 32 (the distance from the coating surface 31 to the bottom 32A) is preferably 10 to 1,000 nm, more preferably 30 to 1,000 nm, further preferably 50 to 500 nm, and particularly preferably 90 to 300 nm.

[0203] The depth D3 of the upper hole portion 32 , the depth D4 of the intermediate hole portion 34 described later, and the depth D5 of the lower hole portion 36 described later can be measured by the above-mentioned method for measuring the depth of micropores.

[0204] The shape of the upper hole 32 is not limited to Figure 5 The substantially straight tube shape (substantially cylindrical shape) shown may be, for example, a cone shape whose diameter decreases toward the depth direction or a truncated cone shape whose diameter increases toward the depth direction. The shape of the upper hole portion 32 is preferably a substantially straight tube shape.

[0205] The intermediate hole portion 34 is a hole portion that communicates with the bottom portion 32A of the upper hole portion 32 and extends further in the depth direction from the communication position 33 .

[0206] The maximum diameter of the intermediate pores 34 is preferably 20 to 100 nm, more preferably 30 to 100 nm, and further preferably 40 to 80 nm.

[0207] Furthermore, the maximum diameter of the intermediate pores 34 may be, for example, 1.2 to 5.0 times the average diameter of the upper pores 32 in the coating surface 31 .

[0208] The average diameter at the communication position 33 of the intermediate hole 34 and the average diameter at the communication position 35 of the lower hole 36 described later can be measured by the method for measuring the average diameter at the communication position 23 between the small diameter hole 24 and the large diameter hole 22 described above.

[0209] The depth D4 of the intermediate hole portion 34 (the distance from the communication position 33 with the large-diameter hole portion 32 to the communication position 35 with the lower hole portion 36 ) is preferably 500 to 3000 nm, more preferably 700 to 2000 nm, and further preferably 800 to 1600 nm.

[0210] The shape of the middle hole 34 is not limited to Figure 5 The substantially straight tube shape (substantially cylindrical shape) shown may be, for example, a cone shape whose diameter decreases toward the depth direction or a truncated cone shape whose diameter increases toward the depth direction. The shape of the intermediate hole 34 is preferably a substantially straight tube shape.

[0211] The shape of the bottom 34A of the intermediate hole 34 is not particularly limited, and may be a curved surface (convex shape) or a flat surface.

[0212] and, Figure 5 The micropore 30 shown has a substantially straight tube-shaped hole portion as the middle hole portion 34 between the upper hole portion 32 and the lower hole portion 36, but the middle hole portion may have a structure in which a plurality of holes having different diameters are connected along the depth direction. When the middle hole portion has a plurality of holes, the preferred form of the size and shape of each hole portion is as described above.

[0213] The lower hole portion 36 is a hole portion that communicates with the bottom portion 34A of the intermediate hole portion 34 and extends further in the depth direction from the communication position 35 .

[0214] The average diameter of the lower pores 36 at the communication position 35 is preferably smaller than the average diameter at the coating surface 31 of the upper pores 32, and smaller than the average diameter at the communication position 33 of the intermediate pores 34. The average diameter of the lower pores 36 at the communication position 35 is preferably 15 nm or less, more preferably 13 nm or less, more preferably 11 nm or less, and particularly preferably 10 nm or less. The lower limit is not particularly limited, but is preferably 5 nm or more.

[0215] The depth D5 of the lower hole 36 (the distance from the communication position 35 with the middle hole 34 to the bottom 36A of the lower hole 36) is preferably 500 to 3,000 nm, more preferably 700 to 2,000 nm, further preferably 700 to 1,700 nm, and particularly preferably 800 to 1,500 nm.

[0216] The shape of the lower hole 36 is not limited to Figure 5 The substantially straight tube shape (substantially cylindrical shape) shown may be, for example, a cone shape whose diameter decreases toward the depth direction or a truncated cone shape whose diameter increases toward the depth direction. The shape of the lower hole portion 36 is preferably a substantially straight tube shape.

[0217] The shape of the bottom portion 36A of the lower hole portion 36 is not particularly limited, and may be a curved surface (convex shape) or a flat surface.

[0218] As a preferred example of micropores including an upper pore portion, a middle pore portion and a small-diameter pore portion, there can be cited the following micropores: an upper pore portion, wherein the depth D3 from the coating surface is 30 to 1,000 nm and the average diameter at the coating surface is 15 to 50 nm; a middle pore portion, wherein the maximum diameter is 20 to 100 nm and is larger than the average diameter at the coating surface of the upper pore portion; and a small-diameter pore portion, wherein the depth D5 from the connection position with the middle pore portion is 500 to 3,000 nm and the average diameter at the connection position with the middle pore portion is less than 15 nm.

[0219] Among the micropores described above, micropores having an average diameter, depth, and shape of each pore portion that are in the above-described preferred embodiments are more preferred.

[0220] The microporous structure of the anodized film is not limited to Figure 4 and Figure 5 The method shown.

[0221] For example, as described above, the intermediate pores may have a structure in which a plurality of pores having different diameters are connected along the depth direction. That is, the micropores may have a structure in which four or more pores having different diameters are connected along the depth direction.

[0222] Furthermore, the micropores of the anodized film may include the following: a small-diameter pore portion extending from the film surface in the depth direction; and a large-diameter pore portion connected to the bottom of the small-diameter pore portion and further extending from the connection position in the depth direction and having a diameter at the connection position larger than the diameter of the film surface of the small-diameter pore portion. Figure 4 The microwells shown have identical pore sections.

[0223] (concave density)

[0224] From the viewpoint of better brush resistance, the density of the recessed portions (hereinafter also referred to as “specific recessed portions”) having a depth of 0.7 μm or more from the average surface, obtained by measuring the surface of the anodized coating side of the support body in a range of 400 μm × 400 μm using a non-contact three-dimensional roughness meter, is preferably 3,000 pieces / mm 2 More than 3,500 pieces / mm 2 More preferably, 5,000 pieces / mm 2 The upper limit of the density of the specific recessed portions is not particularly limited, but is preferably 10,000 / mm 2 Below, more preferably 8,000 pieces / mm 2 the following.

[0225] The density of specific recessed portions in the support body refers to a value measured as follows.

[0226] First, a non-contact 3D roughness meter (VertScan, manufactured by Ryoka Systems Inc.) was used to scan the surface of the anodized coating side (image recording layer side) of the support body in a non-contact manner at a resolution of 0.01 μm within a range of 400 μm×400 μm to obtain three-dimensional data. In addition, the device content and measurement conditions of the above-mentioned VertScan are as follows.

[0227] (1) Device content

[0228] CCD camera: Sony HR-57

[0229] Objective lens: ×10

[0230] Lens tube: ×1

[0231] Wavelength filter: 530white

[0232] (2) Measurement conditions

[0233] Measurement mode: wave

[0234] Field of view: 400μm×400μm

[0235] Scanning range: start +6μm, end -10μm

[0236] Next, the obtained three-dimensional data were image analyzed using software (SX Viewer, manufactured by Ryoka Systems Inc.), and the number of recesses with a depth of 0.7 μm or more from the average plane was obtained. In addition, the average plane refers to a plane located at a height where the height values ​​of all measured data on the surface of the image recording layer side of the support within the measurement area (400 μm×400 μm) are averaged.

[0237] For each sample, five locations were measured, the number of predetermined concave portions was counted at each location, and then their average value was calculated and converted into a value per unit area (mm 2 ) is taken as the density of specific concave portions.

[0238] (Surface area ratio ΔS)

[0239] In the support, from the viewpoint of better brush resistance, the actual area Sx obtained by the three-dimensional data obtained by measuring 256×256 points in the range of 25μm×25μm on the surface of the anodized film side using an atomic force microscope and the geometrically measured area S0 of the surface of the anodized film is preferably 25% or more, more preferably 35% or more, and further preferably 45% or more. The upper limit of the surface area ratio ΔS is not particularly limited, but is preferably 90% or less, and more preferably 80% or less.

[0240] ΔS=(Sx-S0) / S0×100(%)···(S1)

[0241] The surface area ratio ΔS in the support is a value measured as follows.

[0242] Specifically, the support body is cut into a size of 1 cm square, and is placed on a horizontal sample stage on a piezoelectric scanner. The cantilever is brought close to the sample surface. When the area where the atomic force acts is reached, it is scanned in the XY direction. At this time, the concave and convex of the sample is obtained by the piezoelectric displacement in the Z direction. For the piezoelectric scanner, a piezoelectric scanner capable of scanning 150 μm in the XY direction and 10 μm in the Z direction is used. For the cantilever, a cantilever with a resonance frequency of 130 to 200 kHz and a spring constant of 7 to 20 N / m (OMCL-AC200-TS, manufactured by 0lympus Corporation) is used, and the measurement is performed in DFM mode (Dynamic Force Mode). In addition, the slight tilt of the sample is corrected by performing least squares approximation on the obtained three-dimensional data to obtain the reference surface.

[0243] The measurement was performed at 256×256 points on a 25×25 μm area of ​​the surface, with a resolution of 0.05 μm in the X direction, 1.9 μm in the Y direction, and 1 nm in the Z direction, and a scanning speed of 18 μm / sec.

[0244] From the viewpoint of improving the image visibility in the on-press development type planographic printing plate precursor, it is useful that the brightness at the surface of the anodic oxide film of the support is high.

[0245] In the printing process of lithographic printing plates, plate inspection is usually performed before the printing plate is installed in the printing press to confirm whether the image is recorded as intended. In the case of an on-press developed lithographic printing plate precursor, it is required to confirm the image at the stage of image exposure, so a mechanism for generating a so-called printed image is applied to the image exposure section.

[0246] As a method for quantitatively evaluating the visibility (visibility) of the image portion of the image-exposed on-press developed lithographic printing plate precursor, there can be mentioned a method of measuring the brightness of the image-exposed portion and the brightness of the unexposed portion and finding the difference between the two. Here, as brightness, the CIE L * a * b * Lightness L in the color system * The value of can be measured by using a colorimeter (SpectroEye, manufactured by X-Rite Inc.). The greater the difference between the brightness of the image exposure portion obtained by the measurement and the brightness of the unexposed portion, the easier it is to see the image portion.

[0247] In order to improve the visibility, that is, to increase the difference in brightness between the image exposure area and the unexposed area, the L * a * b * Lightness L in the color system * The value of is preferably higher, more preferably 60-100.

[0248] The support may have a back coating layer including an organic polymer compound described in Japanese Patent Application Laid-Open No. 5-045885 or a silicon alkoxide compound described in Japanese Patent Application Laid-Open No. 6-035174 as needed on the surface on the aluminum alloy plate side.

[0249] <Method for Manufacturing Support Body>

[0250] The support used in the lithographic printing plate precursor of the present invention can be produced using a known method.

[0251] A preferred embodiment of the method for producing the support body includes a method comprising a step of roughening the cast aluminum alloy plate (roughening step) and a step of anodizing the roughened aluminum alloy plate (anodizing step).

[0252] As the aluminum alloy plate used for manufacturing the support body, an aluminum alloy plate manufactured by a continuous casting method is preferable.

[0253] In rolling based on continuous casting, since the solidification rate of the surface of the casting material is high, the crystals are fine and uniform, and the homogenization heat treatment of the ingot required in the semi-continuous casting method (DC casting method) is not required. Long-term treatment is not required, so the quality is stable. Therefore, it is suitable as a plain plate for a support body for a lithographic printing plate.

[0254] As the continuous casting method, specifically, the following method is preferably exemplified.

[0255] First, the aluminum alloy molten metal adjusted to a predetermined alloy component content is subjected to a cleaning process as necessary.

[0256] Examples of cleaning treatments include degassing treatments for removing unnecessary gases such as hydrogen in the molten metal (for example, flux treatments using argon, chlorine, etc.); filtration treatments using so-called rigid media filters such as ceramic tube filters and ceramic foam filters, filters using alumina sheets and alumina balls as filter materials, and filters such as glass cloth filters; treatments combining such degassing treatments and filtration treatments; and the like.

[0257] These cleaning treatments are preferably performed to prevent defects caused by foreign matter such as non-metallic inclusions and oxides in the molten metal and defects caused by gas dissolved in the molten metal. Regarding the filtration of the molten metal, Japanese Patent Laid-Open No. 6-057432, Japanese Patent Laid-Open No. 3-162530, Japanese Patent Laid-Open No. 5-140659, Japanese Patent Laid-Open No. 4-231425, Japanese Patent Laid-Open No. 4-276031, Japanese Patent Laid-Open No. 5-311261 and Japanese Patent Laid-Open No. 6-136466 are described. In addition, regarding the degassing of the molten metal, Japanese Patent Laid-Open No. 5-051659, Japanese Utility Model Laid-Open No. 5-049148 and Japanese Patent Laid-Open No. 7-040017 are described.

[0258] Next, continuous casting is performed using the molten metal that has been cleaned as necessary.

[0259] Continuous casting is a process of supplying aluminum alloy molten metal between a pair of cooling rollers and other components through a molten metal supply nozzle, and rolling the aluminum alloy molten metal while solidifying it through the pair of cooling rollers and other components. Continuous casting can be implemented by using cooling rollers represented by the twin-roll method (Hunter method) and the 3C method, and by using cooling belts or cooling blocks represented by the twin-belt method (Hazlett method) and AlSwiss caster (AlSwiss caster) II.

[0260] The continuous casting method generally has the following characteristics: the cooling rate is faster than that of the DC casting method, so the solid solubility of the alloy components in the aluminum matrix can be increased. In the continuous casting method, the molten metal is cooled and solidified at a cooling rate within the range of 100 to 1000°C / sec.

[0261] In this way, in the case where the cooling rate is fast when the aluminum alloy plate is cast, the density of the specific intermetallic compound on the target surface of the manufactured support body tends to decrease.

[0262] Regarding the continuous casting method, the technology proposed by the applicant is described in the publications of Japanese Patent Application Laid-Open No. 3-079798, Japanese Patent Application Laid-Open No. 5-201166, Japanese Patent Application Laid-Open No. 5-156414, Japanese Patent Application Laid-Open No. 6-262203, Japanese Patent Application Laid-Open No. 6-122949, Japanese Patent Application Laid-Open No. 6-210406, and Japanese Patent Application Laid-Open No. 6-026308.

[0263] In continuous casting, for example, if a method using cooling rolls such as the Hunter method is used, a cast plate having a thickness of 1 to 10 mm can be directly continuously cast, and there is an advantage that a hot rolling step can be omitted.

[0264] Furthermore, if a method using a cooling belt such as the Hazeltt method is used, a cast plate with a plate thickness of 10 to 50 mm can be cast. Generally, by using a method using a cooling belt, a hot rolling roll is immediately arranged after casting and continuous rolling is performed to obtain a continuously cast and rolled plate with a plate thickness of 1 to 10 mm.

[0265] From the viewpoint of being able to reduce the density of specific intermetallic compounds and increasing the density of intermetallic compounds having a major diameter of 0.1 μm or more and less than 2.0 μm to the above preferred range, the method using a cooling roll is preferred. Furthermore, the thickness of the cast plate produced using the cooling roll is preferably set to 7 mm or less.

[0266] After continuous casting, the obtained aluminum alloy plate is subjected to a cold rolling process or the like as necessary, and is finished to a predetermined thickness, for example, a plate thickness of 0.1 to 0.5 mm.

[0267] In continuous casting, from the viewpoint of increasing the solid solution amount of Si or suppressing the solid solution amount of Fe before or after cold rolling or during the cold rolling, intermediate annealing can be performed. In addition, appropriate intermediate annealing also has the effect of making the crystal grains fine, which can improve the surface quality.

[0268] From the perspective of optimizing the size and number of intermetallic compounds (i.e., reducing the density of specific intermetallic compounds and adjusting the density of intermetallic compounds with a major diameter of 0.1 μm or more and less than 2.0 μm to the above preferred range), it is preferred to avoid performing the above intermediate annealing treatment at excessively high temperatures or for excessively long periods of time. In particular, it is preferred to avoid heat treatments exceeding 550°C and exceeding 36 hours. This is because sometimes the above intermetallic compounds are dissolved in aluminum again, or intermetallic compounds of quasi-stable phases such as α-AlFeSi and β-AlFeSi become stable phases of Al. 3 Fe.

[0269] As the preferred conditions for the above-mentioned intermediate annealing treatment, from the above-mentioned viewpoint, there can be cited the conditions of heating at 280-550°C for 2-20 hours, preferably at 350-550°C for 2-10 hours, more preferably at 350-550°C for 2-5 hours using a batch annealing furnace; heating at 400-550°C for less than 6 minutes, preferably at 450-550°C for less than 2 minutes using a continuous annealing furnace; etc.

[0270] Through the above process, the aluminum alloy plate finished to a specified thickness, such as 0.1 to 0.5 mm, can be further improved in flatness by correction devices such as a roller straightener and a tension leveler. The improvement of flatness can be performed after the aluminum alloy plate is cut into sheets, but in order to improve productivity, it is preferably performed in a continuous coil state.

[0271] Furthermore, in order to process the aluminum alloy plate into a predetermined plate width, it may be passed through a slitting line.

[0272] Furthermore, in order to prevent scratches caused by friction between aluminum alloy plates, a thin oil film may be provided on the surface of the aluminum alloy plate. A volatile substance or a non-volatile substance may be appropriately used in the oil film as required.

[0273] (Roughening process)

[0274] The roughening treatment step is a step of roughening the surface of the aluminum alloy plate.

[0275] As the roughening treatment, generally, one or a combination of two or more of mechanical roughening treatment, chemical roughening treatment, and electrochemical roughening treatment is used.

[0276] From the viewpoint of being able to effectively manufacture a predetermined support body, the roughening treatment step preferably includes the following hydrochloric acid electrolytic treatment step: for the aluminum alloy plate, in a hydrochloric acid treatment solution that may contain sulfuric acid, the liquid temperature of the hydrochloric acid treatment solution is 30°C or less, and the total amount of electricity participating in the anodic reaction of the aluminum alloy plate is 500C / dm 2Below, and the peak current value of the AC current waveform is 80A / dm 2 AC electrolysis was performed under the following conditions to produce a roughened aluminum alloy plate.

[0277] Furthermore, when the hydrochloric acid treatment liquid contains sulfuric acid, the ratio of the content of sulfuric acid to the content of hydrochloric acid is preferably 0.1 or less.

[0278] The method for producing a support body preferably includes an anodizing step of performing an anodizing step on the roughened aluminum alloy plate after the hydrochloric acid electrolytic treatment step to form an aluminum anodized film on the aluminum alloy plate.

[0279] The method for producing a support body preferably includes a pore expanding step of performing an etching process on the aluminum alloy plate having the anodic oxide film formed thereon after the anodic oxide step to expand the diameter of micropores in the anodic oxide film.

[0280] Hereinafter, each of the above steps and optional treatments will be described in detail.

[0281] (Mechanical roughening treatment)

[0282] The method for producing the support body may include performing a mechanical roughening treatment before the hydrochloric acid electrolytic treatment step.

[0283] As mechanical roughening treatment methods, for example, there can be cited a wire brush grinding method in which the surface of the aluminum alloy plate is scratched with a metal wire, a ball milling method in which the surface of the aluminum alloy plate is frosted with grinding balls and abrasives, and a brush grinding method in which the surface is frosted with a nylon brush and abrasives as described in Japanese Patent Gazette No. 6-135175 and Japanese Patent Publication No. 50-040047.

[0284] (Hydrochloric acid electrolysis process)

[0285] The hydrochloric acid electrolysis treatment step of the support manufacturing method is preferably the following hydrochloric acid electrolysis treatment step: for the aluminum alloy plate, in a hydrochloric acid treatment solution that may contain sulfuric acid, when the liquid temperature of the hydrochloric acid treatment solution is below 30°C and the total amount of electricity participating in the anodic reaction of the aluminum alloy plate is 500C / dm 2 Below, and the peak current value of the AC current waveform is 80A / dm 2 The roughened aluminum alloy plate was produced by performing alternating current electrolysis under the following conditions. The above-mentioned planographic printing plate precursor can be efficiently produced by performing such hydrochloric acid electrolysis treatment and anodizing treatment described later.

[0286] The hydrochloric acid treatment solution contains hydrochloric acid. The concentration of hydrochloric acid in the hydrochloric acid treatment solution is preferably 5 to 30 g / L, more preferably 10 to 20 g / L.

[0287] The hydrochloric acid treatment solution may contain sulfuric acid. When the hydrochloric acid treatment solution contains sulfuric acid, the sulfuric acid concentration in the hydrochloric acid treatment solution is preferably 2.0 g / L or less, more preferably 1.0 g / L or less, and further preferably 0.5 g / L. When the hydrochloric acid treatment solution contains sulfuric acid, the lower limit of the sulfuric acid concentration in the hydrochloric acid treatment solution is not particularly limited, and may be more than 0 g / L.

[0288] The hydrochloric acid treatment solution may contain aluminum ions. When the hydrochloric acid treatment solution contains aluminum ions, the concentration of the aluminum ions is preferably 1.0 to 30.0 g / L, more preferably 5.0 to 20.0 g / L.

[0289] When the hydrochloric acid treatment liquid contains sulfuric acid, the ratio of the content of sulfuric acid to the content of hydrochloric acid is preferably 0.1 or less. The lower limit is not particularly limited, but may be greater than 0.

[0290] The liquid temperature of the hydrochloric acid treatment liquid is preferably 30° C. or lower, more preferably 26° C. or lower, and further preferably 23° C. or lower. The lower limit is not particularly limited, but is preferably 10° C. or higher, and more preferably 15° C. or higher.

[0291] In the hydrochloric acid electrolysis process, the total amount of electricity (the total amount of electricity participating in the anode reaction of the aluminum alloy plate at the time when the hydrochloric acid electrolysis treatment is completed) is preferably 500C / dm 2 Below, more preferably 350C / dm 2 The lower limit of the total amount of electricity is not particularly limited, but is preferably 50 C / dm 2 More preferably 200C / dm 2 above.

[0292] The peak current value of the AC current waveform is preferably 80A / dm 2 Below, more preferably 70A / dm 2 The peak current value is preferably 10A / dm 2 More preferably 20A / dm 2 above.

[0293] The AC current waveform of the hydrochloric acid electrolysis treatment can be a sine wave, a rectangular wave, a trapezoidal wave, a triangular wave, etc. The frequency is preferably 0.1 to 250 Hz.

[0294] Figure 6 This is a graph showing an example of an alternating waveform current waveform used in hydrochloric acid electrolysis treatment.

[0295] exist Figure 6 In the figure, ta is the anode reaction time, tc is the cathode reaction time, tp is the time until the current reaches the peak from 0, Ia is the current at the peak on the anode circulation side, and Ic is the current at the peak on the cathode circulation side. In the trapezoidal wave, the time tp until the current reaches the peak from 0 is preferably 1 to 10 msec.

[0296] The conditions for one cycle of alternating current used for hydrochloric acid electrolysis treatment are preferably: the ratio of the anodic reaction time ta to the cathodic reaction time tc of the aluminum alloy plate tc / ta is 1 to 20, the ratio of the electric quantity Qc when the aluminum alloy plate is the anode to the electric quantity Qa when the aluminum plate is the anode Qc / Qa is 0.3 to 20, and the anodic reaction time ta is in the range of 5 to 1000 msec.

[0297] Regarding the current density, both the anode circulation side Ia and the cathode circulation side Ic of the current peak of the trapezoidal wave are preferably within the above range (80 A / dm 2 Below).

[0298] Can be used in hydrochloric acid electrolysis using alternating current Figure 7 The device shown.

[0299] Figure 7 This is a side view showing an example of a radial type unit used in hydrochloric acid electrolysis using alternating current.

[0300] exist Figure 7 50 is a main electrolytic cell, 51 is an AC power supply, 52 is a radial drum roller, 53a and 53b are main electrodes, 54 is an electrolyte supply port, 55 is an electrolyte, 56 is a slit, 57 is an electrolyte channel, 58 is an auxiliary anode, 60 is an auxiliary anode tank, and W is an aluminum alloy plate. When more than two electrolytic cells are used, the electrolysis conditions may be the same or different.

[0301] The aluminum alloy plate W is wound on a radial drum roller 52 which is immersed in the main electrolytic tank 50, and the aluminum plate W is electrolytically treated by the main pole 53a and the main pole 53b connected to the AC power supply 51 during the conveying process. The electrolyte 55 is supplied from the electrolyte supply port 54 to the electrolyte channel 57 between the radial drum roller 52 and the main pole 53a and the main pole 53b through the slit 56. Then, the aluminum alloy plate W treated in the main electrolytic tank 50 is electrolytically treated in the auxiliary anode tank 60. In the auxiliary anode tank 60, the auxiliary anode 58 and the aluminum alloy plate W are arranged opposite to each other, and the electrolyte 55 is supplied in a manner that the electrolyte 55 flows in the space between the auxiliary anode 58 and the aluminum alloy plate W.

[0302] (Alkali etching treatment)

[0303] In the method for producing a support body, it is preferred that an alkali etching treatment be performed after the mechanical roughening treatment when the mechanical roughening treatment is performed or before or after the hydrochloric acid electrolytic treatment step.

[0304] In addition, regarding the alkaline etching treatment performed before the hydrochloric acid electrolysis treatment, when no mechanical roughening treatment is performed, it is performed for the purpose of removing rolling oil, pollution and natural oxide film on the surface of the aluminum alloy plate (rolled aluminum), and when the mechanical roughening treatment has been performed, it is performed for the purpose of dissolving the edge portions of the unevenness generated by the mechanical roughening treatment and changing the steep unevenness into a surface with smooth corrugations.

[0305] When mechanical roughening treatment is not performed before alkali etching treatment, the etching amount is preferably 0.1 to 10 g / m 2 , more preferably 1 to 5 g / m 2 If the etching amount is 1 to 10 g / m 2 , the rolling oil, pollution, natural oxidation film, etc. on the surface can be fully removed.

[0306] When mechanical roughening treatment is performed before alkali etching treatment, the etching amount is preferably 3 to 20 g / m 2 , more preferably 5 to 15 g / m 2 .

[0307] The alkali etching treatment performed immediately after the hydrochloric acid electrolysis treatment is performed for the purpose of dissolving the stains generated in the acidic electrolyte and dissolving the edge portions of the unevenness formed by the hydrochloric acid electrolysis treatment. The unevenness formed by the hydrochloric acid electrolysis treatment varies depending on the type of electrolyte, so the optimal etching amount also varies. However, the etching amount of the alkali etching treatment performed after the hydrochloric acid electrolysis treatment is preferably 0 to 0.5 g / m 2 , more preferably 0 to 0.3 g / m 2 .

[0308] Examples of the alkali used in the alkali solution include caustic soda and alkali metal salts, and an aqueous solution of caustic soda is particularly preferred.

[0309] The concentration of the alkaline solution can be determined according to the etching amount, but is preferably 1 to 50% by mass, more preferably 10 to 35% by mass. When aluminum ions are dissolved in the alkaline solution, the concentration of the aluminum ions is preferably 0.01 to 10% by mass, more preferably 3 to 8% by mass. The temperature of the alkaline solution is preferably 20 to 90° C. The treatment time is preferably 0 to 120 seconds.

[0310] Examples of methods for contacting the aluminum alloy plate with the alkaline solution include passing the aluminum alloy plate through a tank filled with the alkaline solution, immersing the aluminum alloy plate in a tank filled with the alkaline solution, and spraying the alkaline solution onto the surface of the aluminum alloy plate.

[0311] (Decontamination treatment)

[0312] In the method for producing the support, after the hydrochloric acid electrolysis treatment or the alkali etching treatment, it is preferred to perform pickling (desmutation treatment) to remove corrosive organisms remaining on the surface.

[0313] Examples of the acid used in the desmear treatment generally include nitric acid, sulfuric acid, and hydrochloric acid, but other acids may also be used.

[0314] The desmear treatment is performed, for example, by bringing the aluminum alloy plate into contact with an acidic solution (containing 0.01 to 5 mass % of aluminum ions) having a concentration of 0.5 to 30 mass % such as hydrochloric acid, nitric acid, and sulfuric acid.

[0315] Examples of methods for contacting the aluminum alloy plate with the acidic solution include passing the aluminum alloy plate through a tank filled with the acidic solution, immersing the aluminum alloy plate in a tank filled with the acidic solution, and spraying the acidic solution onto the surface of the aluminum alloy plate.

[0316] The surface condition of the aluminum alloy plate after the desmear treatment affects the subsequent growth of the natural oxide film, so the selection of the acid, the concentration and the temperature conditions are appropriately selected according to the purpose.

[0317] (Water washing)

[0318] The support body manufacturing method preferably includes water washing after the above-mentioned treatment steps are completed. In particular, water washing at the end of the step affects the subsequent natural oxide film growth, so it needs to be fully performed using pure water, well water, tap water, etc.

[0319] (Anodizing process (surface anodizing process))

[0320] The anodizing step is a step of performing anodizing treatment on the roughened aluminum alloy plate after the hydrochloric acid electrolytic treatment step to form an aluminum anodized film on the aluminum alloy plate.

[0321] The anodizing treatment step may be performed only once or may be performed multiple times.

[0322] The order of the anodizing treatment steps is not particularly limited, and a known method can be used.

[0323] In the anodizing treatment step, an aqueous solution of sulfuric acid, phosphoric acid, oxalic acid, or the like can be used as an electrolytic cell. For example, the concentration of sulfuric acid may be 100 to 300 g / L.

[0324] The conditions for the anodizing treatment can be appropriately set by the electrolyte used, and examples thereof include a liquid temperature of 5 to 70° C. (preferably 10 to 60° C.), a current density of 0.5 to 60 A / dm 2 (Preferably 5 to 60 A / dm 2), voltage 1 to 100 V (preferably 5 to 50 V), electrolysis time 1 to 100 seconds (preferably 5 to 60 seconds) and coating weight 0.1 to 5 g / m 2 (Preferably 0.2 to 3 g / m 2 ).

[0325] In the method for producing a support, from the viewpoint of further improving the adhesion between the support and the image recording layer, the electrolytic cell used in the anodizing step preferably contains an aqueous solution of sulfuric acid or phosphoric acid.

[0326] (Hole expansion process)

[0327] The pore expansion treatment step is a step of performing an etching treatment on the aluminum alloy plate having the anodic oxide film formed thereon after the above-mentioned anodic oxide treatment step to expand the diameter of micropores in the anodic oxide film (pore diameter expansion treatment).

[0328] The pore expansion treatment can be performed by bringing the aluminum alloy plate obtained by the above-mentioned anodizing treatment step into contact with an acid aqueous solution or an alkali aqueous solution. The contact method is not particularly limited, and examples thereof include immersion and spraying.

[0329] (Lower layer anodizing step (second anodizing step))

[0330] In the method for producing a support body, after the above-mentioned surface anodizing treatment and pore expanding treatment, a lower layer anodizing treatment step of further performing anodizing treatment to form an anodized film of aluminum on the aluminum alloy plate may be performed.

[0331] The order of the lower layer anodizing treatment step is not particularly limited, and a known method can be used.

[0332] In the lower layer anodizing step, an aqueous solution of sulfuric acid, phosphoric acid, oxalic acid, or the like can be used as an electrolytic cell. For example, the concentration of sulfuric acid may be 100 to 300 g / L.

[0333] The conditions for the lower layer anodizing treatment can be appropriately set by the electrolyte used, and examples thereof include a liquid temperature of 5 to 70° C. (preferably 10 to 60° C.) and a current density of 0.5 to 60 A / dm 2 (Preferably 5 to 60 A / dm 2 ), voltage 1 to 100 V (preferably 5 to 50 V), electrolysis time 1 to 100 seconds (preferably 5 to 60 seconds) and coating weight 0.1 to 5 g / m 2 (Preferably 0.2 to 3 g / m 2 ).

[0334] As the electrolytic cell used in the lower layer anodizing treatment step, an aqueous solution containing sulfuric acid or phosphoric acid is preferred, and an aqueous solution containing sulfuric acid is more preferred.

[0335] (Intermediate layer anodizing process)

[0336] In the method for manufacturing a support body, after the above-mentioned surface anodizing treatment and pore expansion treatment and before the above-mentioned lower layer anodizing treatment, an anodizing treatment using a phosphoric acid solution can be further performed to form an anodizing film having a pore size larger than that of the upper layer between the upper anodizing film and the lower anodizing film (intermediate layer anodizing treatment step).

[0337] The order of the intermediate layer anodizing treatment step is not particularly limited, and a known method can be used.

[0338] In the intermediate layer anodizing treatment step, a phosphoric acid aqueous solution can be used as an electrolytic cell. For example, the concentration of phosphoric acid in the phosphoric acid aqueous solution is 10 to 300 g / L.

[0339] The conditions for the intermediate layer anodizing treatment can be appropriately set by the electrolyte used, and examples thereof include a liquid temperature of 5 to 70° C. (preferably 10 to 60° C.) and a current density of 0.5 to 60 A / dm 2 (Preferably 5 to 60 A / dm 2 ), voltage 1 to 100 V (preferably 5 to 50 V), electrolysis time 1 to 100 seconds (preferably 5 to 60 seconds) and coating weight 0.1 to 5 g / m 2 (Preferably 0.2 to 3 g / m 2 ).

[0340] As the electrolytic bath used in the intermediate layer anodizing treatment, an aqueous solution containing phosphoric acid is preferred.

[0341] The method for producing a support body may include a hydrophilization step of subjecting the aluminum alloy plate subjected to the anodizing and pore-expanding steps to a hydrophilization treatment. The hydrophilization treatment may be performed by a method described in paragraphs 0109 to 0114 of Japanese Patent Application Laid-Open No. 2005-254638.

[0342] As the hydrophilization treatment, a method of immersing in an aqueous solution of an alkali metal silicate such as sodium silicate and potassium silicate, or a method of coating a hydrophilic vinyl polymer or a hydrophilic compound to form a hydrophilic primer layer is preferred.

[0343] The hydrophilization treatment using an aqueous solution of an alkali metal silicate such as sodium silicate or potassium silicate can be performed according to the method and procedure described in US Pat. No. 2,714,066 and US Pat. No. 3,181,461.

[0344] 〔Image recording layer〕

[0345] The lithographic printing plate precursor according to the present invention has an image recording layer containing at least an infrared absorber and an acid color former.

[0346] The image recording layer is preferably an image recording layer that can be removed by at least one of printing ink and fountain solution.

[0347] Furthermore, the image recording layer is preferably a negative image recording layer, and more preferably a water-soluble or water-dispersible negative image recording layer.

[0348] Hereinafter, the contents of each component contained in the image recording layer will be described.

[0349] <Infrared absorber>

[0350] The image recording layer contains an infrared absorber.

[0351] The infrared absorber is not particularly limited, and examples thereof include pigments and dyes.

[0352] As the dye that can be used as an infrared absorber, it is possible to use a commercially available dye and a known dye described in documents such as "Dye Handbook" (The Society of Synthetic Organic Chemistry, Japan. Edited, Showa 45). Specifically, dyes such as azo dyes, metal complex azo dyes, pyrazolone azo dyes, naphthoquinone dyes, anthraquinone dyes, phthalocyanine dyes, carbonium dyes, quinone imine dyes, methine dyes, cyanine dyes, squaric acid pigments, pyrylium salts, and metal thiolate complexes can be cited.

[0353] Among these dyes, a cyanine dye, a squarylium dye, a pyrylium salt, a nickel thiol complex, or an indocyanine dye is preferred, a cyanine dye or an indocyanine dye is more preferred, and a cyanine dye is further preferred.

[0354] And, as infrared absorber, preferably, there is cationic polymethine pigment with oxygen atom or nitrogen atom at meta position.As cationic polymethine pigment, preferably, cyanine pigment, pyrylium pigment, thiopyrylium pigment, azulenium pigment etc. can be mentioned, and from the viewpoint of easy availability, solvent solubility during introduction reaction etc., cyanine pigment is more preferable.

[0355] Specific examples of cyanine pigments include compounds described in paragraphs 0017 to 0019 of Japanese Patent Application Publication No. 2001-133969, paragraphs 0016 to 0021 of Japanese Patent Application Publication No. 2002-023360, and paragraphs 0012 to 0037 of Japanese Patent Application Publication No. 2002-040638. The compounds described in paragraphs 0034 to 0041 of Japanese Patent Application Publication No. 2002-278057, the compounds described in paragraphs 0080 to 0086 of Japanese Patent Application Publication No. 2008-195018, the compounds described in paragraphs 0035 to 0043 of Japanese Patent Application Publication No. 2007-090850, and the compounds described in paragraphs 0105 to 0113 of Japanese Patent Application Publication No. 2012-206495.

[0356] Furthermore, compounds described in paragraphs 0008 to 0009 of JP-A-5-005005 and paragraphs 0022 to 0025 of JP-A-2001-222101 can also be preferably used.

[0357] As the pigment, the compounds described in paragraphs 0072 to 0076 of JP-A-2008-195018 are preferred.

[0358] Furthermore, the infrared absorber preferably includes an infrared absorber that decomposes upon exposure to infrared rays (a decomposable infrared absorber), and more preferably includes a decomposable color-developing infrared absorber.

[0359] It is presumed that the use of a decomposable infrared absorber as the infrared absorber promotes polymerization of the decomposable infrared absorber or its decomposition product, and that the decomposition product of the decomposable infrared absorber interacts with the polymerizable compound, thereby improving the printing durability.

[0360] The decomposable infrared absorber preferably has the function of absorbing infrared rays caused by infrared exposure and decomposing and developing colors. Hereinafter, the color-forming compound formed by the decomposable infrared absorber absorbing infrared rays caused by infrared exposure and decomposing is also referred to as "color body of the decomposable infrared absorber".

[0361] Furthermore, the decomposable infrared absorbent preferably has a function of absorbing infrared rays due to infrared exposure and converting the absorbed infrared rays into heat.

[0362] The decomposable infrared absorber may absorb at least a portion of the light in the infrared wavelength region (wavelength 750 nm to 1 mm) and decompose. Preferably, the infrared absorber has a maximum absorption wavelength in the wavelength region of 750 to 1,400 nm, and more preferably, has a maximum absorption wavelength in the wavelength region of 760 to 900 nm.

[0363] Furthermore, the decomposable infrared absorbent is preferably a compound that is decomposed by exposure to infrared light and generates a compound having a maximum absorption wavelength in the wavelength region of 500 to 600 nm.

[0364] As the decomposable infrared absorber, an infrared absorber that decomposes by heat, electron transfer, or both caused by infrared exposure is preferred, and an infrared absorber that decomposes by electron transfer caused by infrared exposure is more preferred. Here, "decomposes by electron transfer" means that the infrared absorber that decomposes by infrared exposure is decomposed by electron transfer from HOMO (highest occupied molecular orbital) to LUMO (lowest unoccupied molecular orbital) in the molecule, whereby the electrons are transferred to electron accepting groups (groups with electric potential close to LUMO) in the molecule.

[0365] As the infrared absorber and the infrared absorber that decomposes by infrared exposure, the compounds described in International Publication No. 2020 / 262692 can be preferably used.

[0366] As the infrared absorber that decomposes by infrared exposure, compounds described in JP-A-2008-544322 or WO 2016 / 027886 can be preferably used.

[0367] As the cyanine dye of the decomposable infrared absorber, the infrared absorbing compound described in International Publication No. 2019 / 219560 can be preferably used.

[0368] Among them, as the decomposable infrared absorber, a compound (cyanine dye) represented by the following formula (A) is preferred.

[0369] [Chemical formula 1]

[0370]

[0371] In the formula, R 1 Indicates that R 1 -L bond cleavage group,

[0372] R 11 ~R 18 Each independently represents a hydrogen atom, a halogen atom, -Ra, -ORb, -SRc or -NRdRe,

[0373] Ra to Re each independently represent a hydrocarbon group,

[0374] A 1 , A 2 and multiple R 11 ~R 18 Can be linked to form a single ring or multiple rings,

[0375] A1 and A 2 each independently represents an oxygen atom, a sulfur atom or a nitrogen atom,

[0376] n 11 and n 12 Each independently represents an integer from 0 to 5, wherein n 11 and n 12 The total of is 2 or more,

[0377] n 13 and n 14 Each independently represents 0 or 1,

[0378] L represents an oxygen atom, a sulfur atom or -NR 10 -,

[0379] R ㈢ represents a hydrogen atom, an alkyl group or an aryl group,

[0380] Za represents a counter ion for neutralizing the charge.

[0381] Examples of the compound represented by the above formula (A) include compounds IR-6 to IR-9 described below.

[0382] From the viewpoint of printing durability and halftone dot reproducibility, the value of the highest occupied molecular orbital (HOMO) of the infrared absorber is preferably -5.00 eV or less, more preferably -5.30 eV or less. As the lower limit, from the viewpoint of printing durability and halftone dot reproducibility, it is preferably -5.90 eV or more, more preferably -5.75 eV or more, and further preferably -5.60 eV or more.

[0383] In this specification, MO (molecular orbital) energy calculations of the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) are performed by the following method.

[0384] First, the free counter ions in the compound to be calculated are excluded from the calculation object. For example, in cationic infrared absorbers and cationic polymerization initiators, counter anions are excluded from the calculation object, and in anionic infrared absorbers and anionic polymerization initiators, counter cations are excluded from the calculation object. Free as mentioned here means that the compound to be calculated is not linked to its counter ion through a covalent bond.

[0385] The structure was optimized by DFT (B3LYP / 6-31G(d)) using quantum chemical calculation software Gaussian16.

[0386] Regarding MO energy calculation, the optimal structure obtained by the above-mentioned structural optimization was used and the quantum chemical calculation software Gaussian16 was used for DFT (B3LYP / 6-31+G(d, p) / PCM (solvent = methanol). In addition, the iodine-containing compound was calculated under DFT (B3LYP / DGDZVP / PCM (solvent = methanol)).

[0387] The optimal structure here refers to the structure with the most stable total energy obtained by DFT calculation. The optimal structure is found by repeating the structural optimization as needed.

[0388] The MO energy Ebare (unit: hartree) obtained by the above-mentioned M0 energy calculation is converted into Escaled (unit: eV) used as the value of HOMO and LUMO according to the following formula.

[0389] [Calculation formula of HOMO] Escaled = 0.823168 × 27.2114 × Ebare - 1.07634

[0390] [Calculation formula of LUMO] Escaled = 0.820139 × 27.2114 × Ebare - 1.086039

[0391] In addition, 27.2114 is a coefficient used only for converting Hartree to eV, 0.823168 and -1.07634 used in calculating HOMO, and 0.820139 and -1.086039 used in calculating LUMO are adjustment coefficients, and are determined in such a way that the calculated and measured values ​​of HOMO and LUMO of the compound to be calculated match.

[0392] The infrared absorber may be used alone or in combination of two or more. Furthermore, as the infrared absorber, a pigment and a dye may be used in combination.

[0393] The content of the infrared absorber in the image recording layer is preferably 0.1 to 10.0% by mass, more preferably 0.5 to 5.0% by mass, based on the total mass of the image recording layer.

[0394] <Acid coloring agent>

[0395] The image-recording layer contains an acid color former.

[0396] In the present specification, the "acid color former" refers to a compound having a property of developing color through an electron-accepting compound such as an acid and changing the color of the image recording layer.

[0397] Furthermore, in this specification, unless otherwise specified, "color development property" means the degree of color development of an acid coloring agent caused by an electron accepting compound such as an acid.

[0398] The acid color forming agent contained in the image recording layer of the planographic printing plate precursor according to the present invention has a color development coefficient of 20,000 or more as determined by the following measurement X.

[0399] Determination of X: Using 1 mL of a first acetonitrile solution having a mixed acid coloring agent concentration of 0.02 mmol / L, 1 mL of a second acetonitrile solution having a 10-camphorsulfonic acid concentration of 0.02 mmol / L, 5 mL of water, and 93 mL of acetonitrile, ultraviolet-visible absorption spectrum measurement was performed under the condition that the optical path width of the measurement unit was 10 mm. When the absorbance at the absorption maximum wavelength was defined as Amax, the value obtained by formula (1) was defined as the coloring coefficient.

[0400] Formula (1) Color coefficient (L·mol -1 cm -1 )=Amax / {(0.0002mmol / L)×(1cm)}

[0401] A more specific method for measuring X is as follows.

[0402] -Preparation of Pigment Solution X1-

[0403] Accurately weigh 0.1 mmol of the acid coloring agent and add it to a 50 mL volumetric flask.

[0404] About 40 mL of acetonitrile was added to the volumetric flask, and after visually confirming that the acid coloring agent was completely dissolved, the volume was fixed to 50 mL with acetonitrile to obtain a dye solution X1.

[0405] -Preparation of acid solution X2-

[0406] 0.2 mmol of 10-camphorsulfonic acid (CSA) was added to a 100 mL volumetric flask, followed by about 80 mL of acetonitrile. After confirming that CSA was completely dissolved, the volume was fixed to 100 mL with acetonitrile to obtain an acid solution D.

[0407] - Preparation of Assay Solution X3 -

[0408] Using a full volume pipette, 5 mL of ion exchange water and 80 mL of acetonitrile were added to a 100 mL volumetric flask. Next, 1 mL of the pigment solution X1 and 1 mL of the acid solution X2 were added to the volumetric flask, and the volume was fixed to 100 mL with acetonitrile to obtain a measurement solution X3.

[0409] The concentration of the acid color-forming agent contained in the color-forming body generated in the measurement liquid X3 was 0.02 mmol / L.

[0410] The measurement liquid X3 was filled into a measurement cell (quartz glass, optical path width: 10 mm), and the measurement was carried out using an ultraviolet visible spectrophotometer (manufactured by SHIMADZU CORPORATION, “UV-1800”).

[0411] The blank culture medium was set to water:acetonitrile = 5:95.

[0412] The absorption maximum wavelength λmax in the visible light region (380 to 750 nm) is read from the obtained spectrum, and the absorbance at this wavelength is substituted as Amax into the above formula (1) to calculate the luminescence coefficient of the acid coloring agent.

[0413] From the viewpoint of better visibility, the color development coefficient of the acid color former contained in the image recording layer is preferably 20,000 or more, more preferably 35,000 or more, and further preferably 50,000 or more.

[0414] Furthermore, from the viewpoint of better suppression of color development failure over time, the color development coefficient of the acid color former contained in the image recording layer is preferably 100,000 or less, more preferably 80,000 or less, and still more preferably 70,000 or less.

[0415] The acid coloring agent is preferably a compound that develops color when heated in a state where it receives an electron accepting compound such as an acid.

[0416] Examples of the acid include protonic acids and Lewis acids. The heating temperature during the heating is preferably 80 to 200°C, more preferably 100 to 180°C.

[0417] As the acid coloring agent, the following colorless compound is preferred: having a parent core structure and a decomposable group bonded to the parent core structure, and the decomposable group rapidly opens or cleaves when in contact with an electron accepting compound. Among them, from the viewpoint of better coloring properties, the acid coloring agent more preferably has a structure that opens the ring by decomposition of the decomposable group when in contact with an electron accepting compound. In addition, the ring opening of the decomposable group means that the ring structure possessed by the decomposable group is cleaved by decomposition, and the cleavage of the decomposable group means that the leaving group as a part of the decomposable group is separated by decomposition.

[0418] Examples of the degradable group include groups having a partial structure selected from the group consisting of lactone, lactam, sultone, spiropyran, ester, and amide.

[0419] The number of degradable groups in the acid coloring agent is not particularly limited, but is preferably 1 to 4, more preferably 1 or 2, and even more preferably 1, from the viewpoint of coloring properties.

[0420] From the viewpoint of color development property and time-dependent fading inhibition property, the acid coloring agent preferably has at least one of the groups represented by the following formulae (1a) to (1d) as a degradable group, more preferably has at least one of the groups represented by the following formulae (1a) to (1c), and even more preferably has a group represented by the following formula (1a).

[0421] [Chemical formula 2]

[0422]

[0423] In formulas (1a) to (1d), R 1 and R 2 Indicates the site connected to the above-mentioned mother core structure.

[0424] In formula (1b), R 3 represents a hydrogen atom, an alkyl group, an aryl group or a heteroaryl group.

[0425] In formula (1c), R 4 represents an aryl group or a heteroaryl group.

[0426] In formula (1d), R 5 represents a hydrocarbon group, and X represents a leaving group.

[0427] From the perspective of color development, R 3 and R 4 An aryl group having 6 to 12 carbon atoms or a heteroaryl group having 6 to 12 ring members is preferred, an aryl group having 6 to 12 carbon atoms is more preferred, and a phenyl group is further preferred.

[0428] From the perspective of color development, R 5 An alkyl group or an aryl group is preferred, an aryl group is more preferred, an aryl group having 6 to 12 carbon atoms is further preferred, and a phenyl group is particularly preferred.

[0429] There are no particular limitations on X as long as it is a group that can be decomposed by the above-mentioned degradable group, but an acyloxy group is preferred, an acyloxy group having 1 to 8 carbon atoms is more preferred, and an acetoxy group is further preferred.

[0430] From the viewpoint of color development, the specific dye compound preferably has any of the structures represented by the following formulae (2a) to (2f) as a core structure, and more preferably has a structure represented by the following formula (2a) as a core structure.

[0431] [Chemical formula 3]

[0432]

[0433] In formulae (2a) to (2f), structure b represents a structure that is ring-opened or cleaved when in contact with an electron-accepting compound.

[0434] In formula (2c) to formula (2f), R 1 ~R 9 Each independently represents a hydrogen atom, an alkyl group or an alkoxy group.

[0435] From the viewpoint of color development and fading inhibition over time, structure b is preferably any of the groups represented by the above formulae (1a) to (1d), more preferably any of the groups represented by the above formulae (1a) to (1c), and still more preferably a group represented by the above formula (1a).

[0436] By R 1 ~R 9 The number of carbon atoms of the alkyl group or alkoxy group represented by is preferably 1 to 15, and more preferably 1 to 10. From the viewpoint of color development and visual recognition, R 1 ~R 9 Each independently is preferably a hydrogen atom or an alkyl group, more preferably an alkyl group, and further preferably a methyl group.

[0437] The structures represented by formula (2a) to formula (2f) include the following: 1 ~R 9 In addition, the aromatic ring or the heterocyclic ring may further have a substituent.

[0438] Preferred substituents include alkyl, aryl, alkoxy, aryloxy, dialkylamino, diarylamino, alkylarylamino, arylamino, and alkylamino groups. Among them, from the viewpoint of color development and fading inhibition over time, it is preferred to have at least one dialkylamino group.

[0439] From the viewpoint of color development and visibility, the acid coloring agent preferably contains a colorless dye, and more preferably a colorless dye.

[0440] Furthermore, the colorless dye is preferably a colorless dye having a phthalide structure or a fluoran structure from the viewpoint of color development and visibility.

[0441] As the acid color former, from the viewpoint of developability after aging, color development property and visibility, a compound represented by the following formula (3a) or formula (3b) is preferred, and a compound represented by the following formula (3a) is more preferred.

[0442] [Chemical formula 4]

[0443]

[0444] In formula (3a), Ar 1 and Ar 2 Each independently represents an aryl group which may have a substituent or a heteroaryl group which may have a substituent, R 10 and R11 Each independently represents a hydrogen atom, an alkyl group, an aryl group which may have a substituent, or a heteroaryl group which may have a substituent.

[0445] In formula (3b), ERG each independently represents an electron donating group, n represents an integer of 1 to 5, and X 1 ~X 4 Each independently represents a hydrogen atom, a halogen atom or a monovalent organic group, and Y 1 and Y 2 Each independently represents C or N, in Y 1 When N is 1 Does not exist in Y 2 When N is 4 Does not exist, R 12 and R 13 Each independently represents a hydrogen atom, an alkyl group, an aryl group which may have a substituent, or a heteroaryl group which may have a substituent.

[0446] The alkyl group in formula (3a) or (3b) may be linear, branched, or cyclic. The number of carbon atoms in the alkyl group in formula (3a) or (3b) is preferably 1 to 20, more preferably 1 to 8, further preferably 1 to 4, and particularly preferably 1 or 2.

[0447] The carbon number of the aryl group in formula (3a) or (3b) is preferably 6 to 20, more preferably 6 to 10, and further preferably 6 to 8. Examples of the aryl group in formula (3a) or (3b) include optionally substituted phenyl, naphthyl, anthracenyl and phenanthryl.

[0448] Examples of the heteroaryl group in the formula (3a) or (3b) include a furyl group, a pyridyl group, a pyrimidyl group, a pyrazolyl group, and a thiophenyl group which may have a substituent.

[0449] In addition, each group such as the alkyl group, aryl group and heteroaryl group in formula (3a) or formula (3b) may have a substituent. As the substituent, an alkyl group, an aryl group, a heteroaryl group, a halogen atom, an amino group, an alkylamino group, an arylamino group, a heteroarylamino group, a dialkylamino group, a monoalkyl monoarylamino group, a monoalkyl monoheteroarylamino group, a diarylamino group, a diheteroarylamino group, a monoaryl monoheteroarylamino group, a hydroxyl group, an alkoxy group, an aryloxy group, a heteroaryloxy group, an acyl group, an alkoxycarbonyl group, an aryloxycarbonyl group, a heteroaryloxycarbonyl group and a cyano group may be mentioned. In addition, these substituents may be further substituted by these substituents.

[0450] The above-mentioned substituent may be an electron donating group.

[0451] As the electron-donating group represented by ERG and the electron-donating group as the above-mentioned substituent, from the viewpoint of color development and visual recognition, preferably an amino group, an alkylamino group, an arylamino group, a heteroarylamino group, a dialkylamino group, a monoalkylmonoarylamino group, a monoalkylmonoheteroarylamino group, a diarylamino group, a diheteroarylamino group, a monoarylmonoheteroarylamino group, an alkoxy group, an aryloxy group, a heteroaryloxy group or an alkyl group, more preferably an alkoxy group, an aryloxy group, a heteroaryloxy group or an alkyl group, and further preferably an alkoxy group.

[0452] From the viewpoint of color development and visual recognition, R in formula (3a) 10 and R 11 An alkyl group or an aryl group which may have an electron-donating group is preferably each independently selected, a methyl group or an aryl group having an electron-donating group is more preferred, and a phenyl group having an electron-donating group at the para position is further preferred.

[0453] From the viewpoint of color development and visual recognition, Ar in formula (3a) 1 and Ar 2 An aryl group which may have at least one substituent at the ortho position or a heteroaryl group which may have at least one substituent at the ortho position is respectively and independently preferred, an aryl group having at least one substituent at the ortho position is more preferred, a phenyl group having at least one substituent at the ortho position is further preferred, and a phenyl group having at least one substituent at the ortho position and an electron donating group at the para position is particularly preferred.

[0454] From the viewpoint of color development and visual recognition, R in formula (3b) 12 and R 13 An aryl group substituted with a hydrogen atom, an alkyl group or an alkoxy group is preferred, an alkyl group is more preferred, and a methyl group is further preferred.

[0455] In the formula (3b), n is preferably an integer of 1 to 3, and more preferably 1 or 2.

[0456] From the viewpoint of color development and visual recognition, X in formula (3b) 1 ~X 4 A hydrogen atom or a chlorine atom is respectively independently preferred, and a hydrogen atom is more preferred.

[0457] From the viewpoint of color development and visual recognition, Y in formula (3b) 1 and Y 2 Preferably at least one is C, more preferably Y 1 and Y 2 These two are C.

[0458] Preferred specific examples of the acid coloring agent include the following compounds S-1 to S-20: Me represents a methyl group, Et represents an ethyl group, and Ph represents a phenyl group.

[0459] [Chemical formula 5]

[0460]

[0461] [Chemical formula 6]

[0462]

[0463] [Chemical formula 7]

[0464]

[0465] [Chemical formula 8]

[0466]

[0467] [Chemical formula 9]

[0468]

[0469] Furthermore, from the viewpoint of visual recognition, the maximum absorption wavelength λmax of the color body generated by the above-mentioned acid coloring agent in the visible light region (380 to 750 nm) is preferably within the range of 500 to 650 nm, more preferably within the range of 520 to 600 nm, further preferably within the range of 530 to 580 nm, and particularly preferably within the range of 540 to 570 nm.

[0470] These acid coloring agents may be used alone or in combination of two or more.

[0471] The content of the acid color former is preferably 0.5 to 10% by mass, more preferably 1 to 5% by mass, based on the total mass of the image recording layer.

[0472] <Polymerization Initiator>

[0473] The image-recording layer preferably contains a polymerization initiator.

[0474] A polymerization initiator is a compound that generates polymerization initiating species such as free radicals or cations by light, heat, or both of these energies. As a polymerization initiator, a compound that generates free radicals by light, heat, or both of these energies and initiates polymerization of a compound having a polymerizable unsaturated group (so-called free radical polymerization initiator) is preferred.

[0475] Furthermore, examples of the polymerization initiator include electron accepting polymerization initiators and electron donating polymerization initiators.

[0476] The image recording layer preferably contains at least one of an electron accepting polymerization initiator and an electron donating polymerization initiator as a polymerization initiator, and more preferably contains both an electron accepting polymerization initiator and an electron donating polymerization initiator.

[0477] (Electron-accepting polymerization initiator)

[0478] The electron accepting polymerization initiator is a compound that generates polymerization initiating species such as free radicals or cations by light, heat, or both. As the electron accepting polymerization initiator, known thermal polymerization initiators, compounds having bonds with low bond dissociation energy, and photopolymerization initiators can be appropriately used.

[0479] As the electron accepting polymerization initiator, a radical polymerization initiator is preferred.

[0480] Examples of the radical polymerization initiator include (a) organic halides, (b) carbonyl compounds, (c) azo compounds, (d) organic peroxides, (e) metallocene compounds, (f) azide compounds, (g) hexaarylbiimidazole compounds, (i) disulfone compounds, (j) oxime ester compounds, and (k) onium salt compounds.

[0481] (a) Examples of the organic halide include compounds described in paragraphs 0022 to 0023 of JP-A-2008-195018.

[0482] Examples of the (b) carbonyl compound include compounds described in paragraph 0024 of JP-A-2008-195018.

[0483] (c) Examples of the azo compound include azo compounds described in Japanese Patent Application Laid-Open No. 8-108621.

[0484] Examples of the (d) organic peroxide include compounds described in paragraph 0025 of JP-A-2008-195018.

[0485] Examples of the (e) metallocene compound include compounds described in paragraph 0026 of JP-A-2008-195018.

[0486] Examples of the azide compound (f) include compounds such as 2,6-bis(4-azidobenzylidene)-4-methylcyclohexanone.

[0487] Examples of the (g) hexaarylbiimidazole compound include compounds described in paragraph 0027 of JP-A-2008-195018.

[0488] (i) Examples of the disulfone compound include compounds described in JP-A Nos. 61-166544 and 2002-328465.

[0489] (j) Examples of the onium salt compound include compounds described in paragraphs 0028 to 0030 of JP-A-2008-195018.

[0490] As the radical polymerization initiator, an onium-based polymerization initiator is preferred. The onium-based polymerization initiator is an onium salt compound that generates polymerization initiating species such as radicals by accepting an electron through intermolecular electron transfer when electrons of an infrared absorber are excited by infrared exposure.

[0491] As the onium polymerization initiator, from the viewpoint of better printing durability, an iodonium salt compound, a sulfonium salt compound or an azinium salt compound is preferred, an iodonium salt compound or a sulfonium salt compound is more preferred, and an iodonium salt compound is further preferred.

[0492] As the iodonium salt compound, a diaryliodonium salt compound is preferred, and a diphenyliodonium salt compound substituted with an electron donating group such as an alkyl group or an alkoxy group is more preferred, and an asymmetric diphenyliodonium salt compound is preferred.

[0493] Specific examples include diphenyliodonium hexafluorophosphate, 4-methoxyphenyl-4-(2-methylpropyl)phenyliodonium hexafluorophosphate, 4-(2-methylpropyl)phenyl-p-tolyliodonium hexafluorophosphate, 4-hexyloxyphenyl-2,4,6-trimethoxyphenyliodonium hexafluorophosphate, 4-hexyloxyphenyl-2,4-diethoxyphenyliodonium tetrafluoroborate, 4-octyloxyphenyl-2,4,6-trimethoxyphenyliodonium 1-perfluorobutylsulfonate, 4-octyloxyphenyl-2,4,6-trimethoxyphenyliodonium hexafluorophosphate, and bis(4-tert-butylphenyl)iodonium tetraphenylborate.

[0494] As the sulfonium salt compound, a triarylsulfonium salt compound is preferred, and a triarylsulfonium salt compound in which at least a part of the electron withdrawing group, for example, the group on the aromatic ring is substituted with a halogen atom is more preferred, and a triarylsulfonium salt compound in which the total number of halogen atoms substituted on the aromatic ring is 4 or more is further preferred.

[0495] Specific examples include triphenylsulfonium hexafluorophosphate, triphenylsulfonium benzoylformate, bis(4-chlorophenyl)phenylsulfonium benzoylformate, bis(4-chlorophenyl)-4-methylphenylsulfonium tetrafluoroborate, tri(4-chlorophenyl)sulfonium 3,5-bis(methoxycarbonyl)benzenesulfonate, tri(4-chlorophenyl)sulfonium hexafluorophosphate, and tri(2,4-dichlorophenyl)sulfonium hexafluorophosphate.

[0496] As the counter anion of the iodonium salt compound and the sulfonium salt compound, a sulfonamide anion or a sulfonimide anion is preferred, and a sulfonimide anion is more preferred.

[0497] As the sulfonamide anion, an arylsulfonamide anion is preferred.

[0498] As the sulfonyl imide anion, a bisarylsulfonyl imide anion is preferred.

[0499] Specific examples of the sulfonamide anion or the sulfonylimide anion include compounds described in International Publication No. 2020 / 262692.

[0500] From the viewpoint of achieving better chemical resistance and brush resistance, the lowest unoccupied molecular orbital (LUM0) of the electron-accepting polymerization initiator is preferably -3.00 eV or less, and more preferably -3.02 eV or less.

[0501] The lower limit is preferably -3.80 eV or more, more preferably -3.60 eV or more.

[0502] When the image recording layer contains an electron-accepting initiator, from the viewpoint of better visual recognition and printing durability, the value obtained by subtracting the LUMO of the infrared absorber from the LUMO of the electron-accepting polymerization initiator (LUMO of the electron-accepting polymerization initiator - LUMO of the infrared absorber) is preferably 0.70 eV or less, more preferably 0.55 eV or less, and further preferably 0.50 eV or less.

[0503] The lower limit is not particularly limited, but is preferably 0.30 eV or more.

[0504] The electron accepting polymerization initiator may be used alone or in combination of two or more.

[0505] The content of the electron accepting polymerization initiator is preferably 0.1 to 50% by mass, more preferably 0.5 to 30% by mass, and further preferably 0.8 to 20% by mass, based on the total mass of the image recording layer.

[0506] (Electron donating polymerization initiator)

[0507] From the viewpoint of achieving better chemical resistance and printing durability in the lithographic printing plate, the polymerization initiator preferably contains an electron donating polymerization initiator.

[0508] Examples of the electron donating polymerization initiator include the following compounds.

[0509] (i) Alkyl or aryl acid radical type complex: It is believed that the carbon-hetero bond is oxidatively broken to generate active radicals. Specific examples include borate compounds.

[0510] (ii) Aminoacetic acid compounds: It is believed that the C—X bond on the carbon adjacent to nitrogen is broken by oxidation to generate an active free radical. X is preferably a hydrogen atom, a carboxyl group, a trimethylsilyl group or a benzyl group. Specifically, N-phenylglycine (the phenyl group may have a substituent) and N-phenyliminodiacetic acid (the phenyl group may have a substituent) are mentioned.

[0511] (iii) Sulfur-containing compounds: Compounds obtained by substituting the nitrogen atom of the aminoacetic acid compound with a sulfur atom can generate active radicals by the same action. Specific examples include phenylthioacetic acid (which may have a substituent in the phenyl group) and the like.

[0512] (iv) Tin-containing compounds: Compounds obtained by replacing the nitrogen atom of the above aminoacetic acid compounds with a tin atom can generate active free radicals through the same action.

[0513] (v) Sulfinates: They can generate active radicals by oxidation. Specific examples thereof include sodium arylsulfinate.

[0514] As the electron donating polymerization initiator, a borate compound is preferred.

[0515] As the borate compound, a tetraaryl borate compound or a monoalkyltriaryl borate compound is preferred. From the viewpoint of the stability of the compound, a tetraaryl borate compound is more preferred, and a tetraphenyl borate compound is further preferred.

[0516] The counter cation of the borate compound is not particularly limited, but is preferably an alkali metal ion or a tetraalkylammonium ion, and more preferably a sodium ion, a potassium ion or a tetrabutylammonium ion.

[0517] As the borate compound, tetraphenylborate is preferred.

[0518] From the viewpoint of chemical resistance and printing durability, the highest occupied molecular orbital (HOMO) of the electron donating polymerization initiator is preferably -6.00 eV or more, more preferably -5.95 eV or more, further preferably -5.93 eV or more, and particularly preferably greater than -5.90 eV.

[0519] The upper limit is preferably -5.00 eV or less, and more preferably -5.40 eV or less.

[0520] Specific examples of the electron donative polymerization initiator include the electron donative polymerization initiators described in International Publication No. 2020 / 262692.

[0521] From the viewpoint of visual recognizability, printing durability and stability over time, the image recording layer preferably contains at least one selected from an onium salt compound as an electron-accepting polymerization initiator and a borate compound as an electron-donating polymerization initiator, and more preferably contains both an onium salt compound as an electron-accepting polymerization initiator and a borate compound as an electron-donating polymerization initiator.

[0522] As an example of a preferred embodiment when the image recording layer contains both an electron accepting polymerization initiator and an electron donating polymerization initiator, an embodiment in which the electron accepting polymerization initiator and the electron donating polymerization initiator form a salt can be cited. As a salt formed by the electron accepting polymerization initiator and the electron donating polymerization initiator, for example, an iodonium borate compound formed by an iodonium compound as an onium polymerization initiator and a borate compound can be cited.

[0523] Specific examples of the iodine borate compound include compounds described in International Publication No. 2020 / 262692.

[0524] The electron donating polymerization initiator may be used alone or in combination of two or more.

[0525] The content of the electron donating polymerization initiator is preferably 0.01 to 30% by mass, more preferably 0.05 to 25% by mass, and further preferably 0.1 to 20% by mass, based on the total mass of the image recording layer.

[0526] The content of the polymerization initiator (the total content of the electron accepting polymerization initiator and the electron donating polymerization initiator) is preferably 0.1 to 50% by mass, more preferably 0.5 to 30% by mass, and further preferably 0.8 to 20% by mass based on the total mass of the image recording layer.

[0527] Furthermore, from the viewpoint of better visual recognition, the content of the polymerization initiator (the total content of the electron accepting polymerization initiator and the electron donating polymerization initiator) is preferably 0.5 molar equivalent or more, more preferably 1.0 molar equivalent or more, and further preferably 3.0 molar equivalent or more relative to the content of the acid coloring agent. The upper limit is not particularly limited, but is preferably 10.0 molar equivalent or less relative to the content of the acid coloring agent.

[0528] <Polymerizable Compound>

[0529] The image recording layer preferably contains a polymerizable compound.

[0530] In this specification, a polymerizable compound refers to a compound having a polymerizable group.

[0531] The polymerizable group is not particularly limited and may be a radical polymerizable group or a cation polymerizable group, but is preferably a radical polymerizable group.

[0532] Examples of the radical polymerizable group include groups having an ethylenically unsaturated group such as a (meth)acryloyl group, an allyl group, a vinylphenyl group, and a vinyl group. From the viewpoint of reactivity, a (meth)acryloyl group is preferred.

[0533] The molecular weight (weight average molecular weight when there is a molecular weight distribution) of the polymerizable compound is preferably 50 or more and less than 2,500.

[0534] The polymerizable compound may be, for example, a radical polymerizable compound or a cation polymerizable compound, and is preferably an addition polymerizable compound (ethylenically unsaturated compound) having at least one ethylenically unsaturated bond.

[0535] The ethylenically unsaturated compound is preferably a compound having at least one terminal ethylenically unsaturated bond, and more preferably a compound having two or more terminal ethylenically unsaturated bonds. The polymerizable compound has a chemical form such as a monomer, a prepolymer, that is, a dimer, a trimer or an oligomer, or a mixture thereof.

[0536] Among them, as the polymerizable compound, from the viewpoint of printing durability, it is preferred to include a polymerizable compound having three or more functional groups, more preferably a polymerizable compound having seven or more functional groups, and further preferably a polymerizable compound having ten or more functional groups. Furthermore, from the viewpoint of printing durability of the obtained lithographic printing plate, the polymerizable compound preferably includes an ethylenically unsaturated compound having three or more functional groups (preferably seven or more functional groups, and more preferably ten or more functional groups), and further preferably includes a (meth)acrylate compound having three or more functional groups (preferably seven or more functional groups, and more preferably ten or more functional groups).

[0537] The polymerizable compound preferably contains a difunctional or lower-functional polymerizable compound, more preferably contains a difunctional polymerizable compound, and further preferably contains a difunctional (meth)acrylate compound, from the viewpoint of on-press developability and suppression of color development failure over time.

[0538] From the viewpoint of printing durability, on-press developability and suppression of color development failure over time, the content of the difunctional or less polymerizable compound (preferably a difunctional polymerizable compound) is preferably 5 to 100% by mass, more preferably 10 to 100% by mass, and further preferably 15 to 100% by mass, relative to the total mass of the polymerizable compound in the above-mentioned image recording layer.

[0539] (Oligomer)

[0540] As the polymerizable compound contained in the image recording layer, a polymerizable compound which is an oligomer is preferred.

[0541] In the present specification, the oligomer refers to a polymerizable compound having a molecular weight (weight average molecular weight when having a molecular weight distribution) of 600 to 40,000 and containing at least one polymerizable group.

[0542] Hereinafter, the polymerizable compound as an oligomer contained in the image recording layer is also simply referred to as an “oligomer”.

[0543] From the viewpoint of excellent chemical resistance and brush resistance, the molecular weight of the oligomer is preferably 1,000 to 25,000.

[0544] Furthermore, from the viewpoint of improving printing durability, the number of polymerizable groups in one molecule of the oligomer is preferably 2 or more, more preferably 3 or more, further preferably 6 or more, and particularly preferably 10 or more.

[0545] In addition, the upper limit of the polymerizable groups in the oligomer is not particularly limited, but the number of polymerizable groups is preferably 20 or less.

[0546] From the viewpoint of printing durability and on-press developability, the oligomer preferably has 7 or more polymerizable groups and a molecular weight of 1,000 to 40,000, and more preferably has 7 or more and 20 or less polymerizable groups and a molecular weight of 1,000 to 25,000.

[0547] In addition, the image recording layer may contain a polymer component which may be generated in the process of producing the oligomer.

[0548] From the viewpoint of printing durability, visibility and on-press developability, the oligomer preferably contains at least one selected from a compound having a urethane bond, a compound having an ester bond and a compound having an epoxy residue, and preferably contains a compound having a urethane bond.

[0549] In the present specification, the epoxy residue refers to a structure formed of an epoxy group, and for example, means the same structure as a structure obtained by a reaction between an acid group (carboxylic acid group or the like) and an epoxy group.

[0550] As the compound having a urethane bond, the compounds described in International Publication No. 2020 / 262692 can be preferably used.

[0551] Furthermore, as the compound having a urethane bond, a compound obtained by introducing a polymerizable group into a polyurethane obtained by a reaction between a polyisocyanate compound and a polyol compound through a polymer reaction can be used.

[0552] For example, a compound having a urethane bond can be obtained by reacting a compound having an epoxy group and a polymerizable group with a urethane oligomer obtained by reacting a polyol compound having an acid group with a polyisocyanate compound.

[0553] The number of polymerizable groups in the compound having an ester bond as an example of an oligomer is preferably 3 or more, and more preferably 6 or more. The upper limit is preferably 20 or less.

[0554] The compound having an epoxy residue as an example of the oligomer is preferably a compound containing a hydroxyl group in the compound.

[0555] Furthermore, the number of polymerizable groups in the compound having an epoxy residue is preferably 2 to 6, and more preferably 2 or 3.

[0556] The compound having an epoxy residue can be obtained, for example, by reacting acrylic acid with a compound having an epoxy group.

[0557] As the oligomer, commercially available products can be used, and examples thereof include UA510H, UA-306H, UA-306I, UA-306T (all manufactured by KYOEISHA CHEMICAL CO., LTD.), UV-1700B, UV-6300B, UV7620EA (all manufactured by Nippon Synthetic Chemical Industry Co., Ltd.), U-15HA (manufactured by Shin-Nakamura Chemical Co., Ltd.), EBECRYL450, EBECRYL657, EBECRYL885, EBECRYL800, EBECRYL3416, EBECRYL860 (all manufactured by DAICEL-ALLNEX LTD.), but the present invention is not limited to these.

[0558] From the viewpoint of improving chemical resistance, printing resistance and suppression of on-press development residue, the content of the oligomer is preferably 30 to 100% by mass, more preferably 50 to 100% by mass, and further preferably 80 to 100% by mass based on the total mass of the polymerizable compound in the image recording layer.

[0559] (Low molecular weight polymerizable compound)

[0560] The polymerizable compound may further contain a polymerizable compound other than the above-mentioned oligomer.

[0561] As polymerizable compounds other than oligomers, low molecular weight polymerizable compounds are preferred from the viewpoint of chemical resistance. The low molecular weight polymerizable compound may be in a chemical form such as a monomer, a dimer, a trimer, or a mixture thereof.

[0562] Furthermore, as the low molecular weight polymerizable compound, at least one polymerizable compound selected from the group consisting of a polymerizable compound having three or more ethylenically unsaturated groups and a polymerizable compound having an isocyanurate ring structure is preferred from the viewpoint of chemical resistance.

[0563] In the present specification, the low molecular weight polymerizable compound refers to a polymerizable compound having a molecular weight (weight average molecular weight when there is a molecular weight distribution) of 50 or more and less than 600.

[0564] The molecular weight of the low molecular weight polymerizable compound is preferably 100 or more and less than 600, more preferably 300 or more and less than 600, and further preferably 400 or more and less than 600, from the viewpoint of excellent chemical resistance, printing resistance, and suppression of on-press development residue.

[0565] When the polymerizable compound contains a low molecular weight polymerizable compound as a polymerizable compound other than the oligomer (the total amount when two or more low molecular weight polymerizable compounds are contained), from the viewpoint of chemical resistance, printing resistance and inhibition of on-press development residue, the ratio of the oligomer to the low molecular weight polymerizable compound (oligomer / low molecular weight polymerizable compound) is preferably 10 / 1 to 1 / 10, more preferably 10 / 1 to 3 / 7, and further preferably 10 / 1 to 7 / 3 on a mass basis.

[0566] Furthermore, as the low molecular weight polymerizable compound, the polymerizable compounds described in paragraphs 0082 to 0086 of International Publication No. 2019 / 013268 can also be preferably used.

[0567] The details of the use method such as the structure of the polymerizable compound, selection of use alone or in combination, and addition amount can be set arbitrarily.

[0568] Among them, from the viewpoint of printing durability, the image recording layer preferably contains two or more polymerizable compounds.

[0569] The content of the polymerizable compound (the total content of the polymerizable compounds when two or more polymerizable compounds are contained) is preferably 5 to 75% by mass, more preferably 10 to 70% by mass, and further preferably 15 to 60% by mass based on the total mass of the image recording layer.

[0570] (particle)

[0571] From the viewpoint of printing durability, the image recording layer preferably contains particles.

[0572] The particles may be either organic particles or inorganic particles, but from the viewpoint of printing durability, organic particles are preferred, and polymer particles are more preferred.

[0573] Organic particles refer to particles composed of organic matter, and polymer particles refer to particles composed of polymers. In other words, polymer particles refer to polymers having a particle shape among the polymers contained in the image recording layer.

[0574] The polymer particles are preferably selected from the group consisting of thermoplastic resin particles, thermoreactive resin particles, polymer particles having polymerizable groups, microcapsules containing hydrophobic compounds, and microgels (crosslinked polymer particles). Among them, polymer particles having polymerizable groups or microgels are preferred.

[0575] The polymer particles preferably contain at least one ethylenically unsaturated group in order to obtain the effect of improving the printing durability of the exposed portion and the on-press developability of the unexposed portion.

[0576] Furthermore, from the viewpoint of printing durability and on-press developability, thermoplastic resin particles are preferably used as the polymer particles.

[0577] Preferred thermoplastic resin particles are those described in Research Disclosure No. 33303 of January 1992, Japanese Patent Application Laid-Open Nos. 9-123387, 9-131850, 9-171249, 9-171250, and European Patent No. 931647.

[0578] Examples of the thermoreactive resin particles include polymer particles having a thermoreactive group. The thermoreactive polymer particles form a hydrophobic region by crosslinking due to a thermal reaction and a change in the functional group at that time.

[0579] The thermoreactive group in the polymer particles having a thermoreactive group may be any functional group that can form a chemical bond, but is preferably a polymerizable group. Examples thereof include ethylenically unsaturated groups that undergo free radical polymerization (e.g., acryloyl, methacryloyl, vinyl, allyl, etc.), cationically polymerizable groups (e.g., vinyl, vinyloxy, epoxy, oxetanyl, etc.), isocyanate groups or blocks thereof that undergo addition reactions, epoxy groups, vinyloxy groups, and functional groups having active hydrogen atoms as their reaction targets (e.g., amino groups, hydroxyl groups, carboxyl groups, etc.), carboxyl groups that undergo fusion reactions and hydroxyl or amino groups as reaction targets, acid anhydrides that undergo ring-opening addition reactions and amino or hydroxyl groups as reaction targets, and the like.

[0580] The microcapsule is, for example, a particle described in Japanese Patent Application Publication No. 2001-277740 or Japanese Patent Application Publication No. 2001-277742, wherein at least a part of the constituent components of the image recording layer are contained in the microcapsule. The constituent components of the image recording layer may also be contained outside the microcapsule. With regard to the image recording layer containing the microcapsule, a structure in which the microcapsule contains a hydrophobic constituent component inside and a hydrophilic constituent component outside the microcapsule is a preferred embodiment.

[0581] The microgel (cross-linked polymer particles) can contain a part of the constituent components of the image recording layer on at least one of its surface or inside. In particular, from the viewpoint of the sensitivity of the obtained lithographic printing plate precursor and the printing durability of the obtained lithographic printing plate, a reactive microgel having a free radical polymerizable group on its surface is preferred.

[0582] The constituent components of the present image recording layer can be microencapsulated or microgelled by applying a known method.

[0583] Furthermore, as polymer particles, from the viewpoint of the printing resistance, stain resistance and storage stability of the obtained lithographic printing plate, resin particles obtained by the reaction of a polyisocyanate compound and a compound having active hydrogen are preferred, wherein the polyisocyanate compound is an adduct of a polyphenol compound having two or more hydroxyl groups in the molecule and isophorone diisocyanate.

[0584] As the polyphenol compound, a compound containing a plurality of benzene rings having a phenolic hydroxyl group is preferred.

[0585] The compound having active hydrogen is preferably a polyol compound or a polyamine compound, more preferably a polyol compound, and still more preferably at least one compound selected from propylene glycol, glycerin, and trimethylolpropane.

[0586] Preferred examples of the resin particles obtained by reaction of a polyvalent isocyanate compound which is an adduct of a polyvalent phenol compound having two or more hydroxyl groups in the molecule and isophorone diisocyanate, and a compound having active hydrogen include polymer particles described in paragraphs 0032 to 0095 of JP-A-2012-206495.

[0587] Moreover, as polymer particles, from the viewpoint of the printing resistance and solvent resistance of the obtained lithographic printing plate, the following polymer particles are preferred: the polymer particles contain a polymer, and the polymer contains both (i): a structural unit having a cyano side group directly bonded to a hydrophobic main chain and (ii): a structural unit having a side group containing a hydrophilic poly (alkylene oxide) chain segment.

[0588] As the hydrophobic main chain, preferably, an acrylic resin chain is used.

[0589] Examples of the cyano side group include -[CH 2 CH(C≡N)]- and -[CH 2 C(CH 3 )(C≡N)]-.

[0590] Furthermore, the structural unit (i) having the above-mentioned cyano side group can be easily derived from an ethylenically unsaturated monomer (for example, acrylonitrile and methacrylonitrile) or a combination thereof.

[0591] Furthermore, as the alkylene oxide in the hydrophilic polyalkylene oxide segment, ethylene oxide or propylene oxide is preferred, and ethylene oxide is more preferred.

[0592] The number of repetitions of the alkylene oxide structure in the hydrophilic polyalkylene oxide segment is preferably 10 to 100, more preferably 25 to 75, and even more preferably 40 to 50.

[0593] Preferred examples of the resin particles comprising both (i) a structural unit having a cyano side group directly bonded to the hydrophobic main chain and (ii) a structural unit having a side group comprising a hydrophilic polyalkylene oxide segment include particles described in paragraphs 0039 to 0068 of JP-A-2008-503365.

[0594] Furthermore, from the viewpoint of printing durability and on-press developability, the polymer particles preferably contain a resin having a hydrophilic group.

[0595] The hydrophilic group is not particularly limited as long as it has a hydrophilic structure, and examples thereof include acid groups such as a carboxyl group, a hydroxyl group, an amino group, a cyano group, and a polyalkylene oxide structure.

[0596] Among them, from the viewpoint of on-press developability and printing durability, a polyalkylene oxide structure is preferred, and a polyethylene oxide structure, a polypropylene oxide structure, or a polyethylene / propylene oxide structure is more preferred.

[0597] Furthermore, from the viewpoint of on-press developability and suppressability of development residue during on-press development, the polyalkylene oxide structure preferably comprises polymer particles of a resin having a polypropylene oxide structure, and more preferably comprises polymer particles of a resin having both a polyethylene oxide structure and a polypropylene oxide structure.

[0598] From the viewpoint of on-press developability, the number of alkylene oxide structures in the polyalkylene oxide structure is preferably 2 or more, more preferably 5 or more, further preferably 5 to 200, and particularly preferably 8 to 150.

[0599] Furthermore, as the above-mentioned hydrophilic group, from the viewpoints of brush resistance, ink adherence and on-press developability, it is preferred that the hydrophilic group contains a structural unit having a cyano group or a group represented by the following formula (Z), more preferably contains a structural unit represented by the following formula (AN) or a group represented by the following formula (Z), and further preferably contains a group represented by the following formula (Z).

[0600] *-QWY(Z)

[0601] In formula (Z), Q represents a divalent linking group, W represents a divalent group having a hydrophilic structure or a divalent group having a hydrophobic structure, Y represents a monovalent group having a hydrophilic structure or a monovalent group having a hydrophobic structure, either W or Y has a hydrophilic structure, and * represents a bonding site with other structures.

[0602] [Chemical formula 10]

[0603]

[0604] In formula (AN), R AN represents a hydrogen atom or a methyl group.

[0605] From the viewpoint of printing durability, the polymer contained in the polymer particles preferably includes a structural unit composed of a compound having a cyano group.

[0606] Regarding the cyano group, it is usually preferred to use a compound (monomer) having a cyano group as a structural unit having a cyano group and introduce it into the resin. Examples of the compound having a cyano group include acrylonitrile compounds, and (meth)acrylonitrile is preferred.

[0607] As the structural unit having a cyano group, a structural unit composed of an acrylonitrile compound is preferred, and a structural unit composed of (meth)acrylonitrile, that is, a structural unit represented by the above formula (AN) is more preferred.

[0608] In the case where the above-mentioned polymer contains a structural unit having a cyano group, from the viewpoint of brush resistance, the content of the structural unit having a cyano group (preferably the structural unit represented by the above-mentioned formula (AN)) in the polymer containing the structural unit having a cyano group is preferably 5 to 90 mass %, more preferably 20 to 80 mass %, and further preferably 30 to 60 mass % relative to the total mass of the polymer containing the structural unit having a cyano group.

[0609] Furthermore, from the viewpoint of printing durability, ink adhesion, and on-press development properties, the polymer particles preferably include a polymer having a group represented by the formula (Z).

[0610] As Q in the above formula (Z), a divalent linking group having 1 to 20 carbon atoms is preferred, and a divalent linking group having 1 to 10 carbon atoms is more preferred.

[0611] Furthermore, Q in the above formula (Z) is preferably an alkylene group, an arylene group, an ester bond, an amide bond, or a group combining two or more of these, and more preferably a phenylene group, an ester bond, or an amide bond.

[0612] As the divalent group having a hydrophilic structure in W of the above formula (Z), a polyalkyleneoxy group or a group in which -CH 2 CH 2NR W - group. In addition, R W represents a hydrogen atom or an alkyl group.

[0613] The divalent group having a hydrophobic structure in W of the above formula (Z) is preferably -R WA -、-OR WA -O-, -R W NR WA -NR W -、-OC(=O)-R WA -O-or-OC(=O)-R WA -O-. In addition, R WA Each independently represents a linear, branched or cyclic alkylene group having 6 to 120 carbon atoms, a halogenated alkylene group having 6 to 120 carbon atoms, an arylene group having 7 to 120 carbon atoms, an alkylenearyl group having 6 to 120 carbon atoms (a divalent group obtained by removing one hydrogen atom from an alkylaryl group) or an aralkylene group having 7 to 120 carbon atoms.

[0614] The monovalent group having a hydrophilic structure in Y of the above formula (Z) is preferably -OH, -C(=O)OH, a polyalkyleneoxy group having a hydrogen atom or an alkyl group at the end, or a polyalkyleneoxy group having a hydrogen atom or an alkyl group at the end and a -CH bonded to the other end. 2 CH 2 NR W -group.

[0615] The monovalent group having a hydrophobic structure in Y of the above formula (Z) is preferably a linear, branched or cyclic alkyl group having 6 to 120 carbon atoms, a halogenated alkyl group having 6 to 120 carbon atoms, an aryl group having 6 to 120 carbon atoms, an alkylaryl group having 7 to 120 carbon atoms (alkylaryl group), an aralkyl group having 7 to 120 carbon atoms, -OR WB 、-C(=O)OR WB or -OC(=O)R WB . R WB It represents an alkyl group having 6 to 20 carbon atoms.

[0616] In the polymer particles having a group represented by the above formula (Z), from the viewpoints of printing resistance, ink adhesion and on-press developability, it is more preferred that W is a divalent group having a hydrophilic structure, it is more preferred that Q is a phenylene group, an ester bond or an amide bond, W is a polyalkyleneoxy group, and Y is a polyalkyleneoxy group having a hydrogen atom or an alkyl group at the end.

[0617] Furthermore, from the viewpoint of printing durability and on-press developability, the polymer particles preferably contain a polymer having a polymerizable group, and more preferably are polymer particles having a polymerizable group on the particle surface.

[0618] Furthermore, from the viewpoint of printing durability, the polymer particles preferably include a polymer having a hydrophilic group and a polymerizable group.

[0619] The polymerizable group may be a cationically polymerizable group or a radically polymerizable group, and is preferably a radically polymerizable group from the viewpoint of reactivity.

[0620] The polymerizable group is not particularly limited as long as it is a polymerizable group, but from the viewpoint of reactivity, an ethylenically unsaturated group is preferred, a vinylphenyl (styryl) group, a (meth)acryloyloxy group or a (meth)acrylamide group is more preferred, and a (meth)acryloyloxy group is further preferred.

[0621] Furthermore, the polymer in the polymer particles having a polymerizable group preferably includes a structural unit having a polymerizable group.

[0622] Furthermore, polymerizable groups can be introduced onto the surface of polymer particles by polymer reaction.

[0623] Furthermore, from the viewpoint of printing durability and on-press development properties, the image recording layer preferably contains addition polymerization type resin particles having a dispersible group as the polymer particles, and more preferably the dispersible group contains a group represented by the formula (Z).

[0624] Furthermore, from the viewpoint of printing durability, ink adhesion, on-press developability, and suppressibility of development residue during on-press development, the polymer particles preferably contain a resin having a urea bond.

[0625] As the resin having a urea bond, preferably, there can be mentioned the resin described in International Publication No. 2020 / 262692.

[0626] Furthermore, from the viewpoint of printing durability and on-press developability, the image recording layer preferably contains thermoplastic resin particles.

[0627] The thermoplastic resin contained in the thermoplastic resin particles is not particularly limited, and examples thereof include polyethylene, polystyrene, polyvinyl chloride, polyvinylidene chloride, polymethyl (meth)acrylate, polyethyl (meth)acrylate, polybutyl (meth)acrylate, polyacrylonitrile, polyvinyl acetate, and copolymers thereof. The thermoplastic resin may be in a latex state.

[0628] The thermoplastic resin is preferably a resin that forms a part or the whole of the hydrophobic film forming the image recording layer by melting or softening the thermoplastic resin by heat generated in an exposure step described later.

[0629] As the thermoplastic resin, from the viewpoint of ink acceptability and printing durability, a resin including a structural unit composed of an aromatic vinyl compound and a structural unit having a cyano group is preferred.

[0630] As the resin containing a structural unit composed of an aromatic vinyl compound and a structural unit having a cyano group, preferably, there can be mentioned the resin described in International Publication No. 2020 / 262692.

[0631] The glass transition temperature (Tg) of the thermoplastic resin contained in the thermoplastic resin particles is preferably 60 to 150°C, more preferably 80 to 140°C, and further preferably 90 to 130°C, from the viewpoint of printing durability and ink adherence.

[0632] When the thermoplastic resin particles contain two or more thermoplastic resins, the value obtained from the FOX equation described below is referred to as the glass transition temperature of the thermoplastic resin.

[0633] In this specification, the glass transition temperature of a resin can be measured using differential scanning calorimetry (DSC).

[0634] The specific measurement method is carried out in accordance with the method described in JIS K 7121 (1987) or JIS K 6240 (2011). The glass transition temperature in this specification refers to the extrapolated glass transition starting temperature (hereinafter, sometimes referred to as Tig).

[0635] The method for measuring the glass transition temperature will be described in more detail.

[0636] When determining the glass transition temperature, the temperature is maintained at about 50°C lower than the predicted Tg of the resin until the device is stable, and then heated at a heating rate of 20°C / min to a temperature about 30°C higher than the temperature at which the glass transition ends, and a differential thermal analysis (DTA) curve or a DSC curve is prepared.

[0637] As the extrapolated glass transition starting temperature (Tig), i.e., the glass transition temperature Tg in this specification, the temperature of the intersection of a straight line extending the low temperature side baseline in a DTA curve or a DSC curve to the high temperature side and a tangent line drawn at a point where the gradient of the curve of the step-like change portion of the glass transition is the maximum is determined.

[0638] When the thermoplastic resin particles contain two or more thermoplastic resins, Tg of the thermoplastic resin contained in the thermoplastic resin particles is determined as follows.

[0639] When the Tg of the first thermoplastic resin is set to Tg1(K), the mass fraction of the first thermoplastic resin in the thermoplastic resin particle relative to the total mass of the thermoplastic resin component is set to W1, the Tg of the second thermoplastic resin is set to Tg2(K), and the mass fraction of the second thermoplastic resin in the thermoplastic resin particle relative to the total mass of the thermoplastic resin component is set to W2, the Tg0(K) of the thermoplastic resin particle can be inferred according to the following FOX formula.

[0640] FOX formula: 1 / Tg0 = (W1 / Tg1) + (W2 / Tg2)

[0641] Furthermore, when the thermoplastic resin particles contain three or more types of resins, or when the pretreatment liquid contains three or more types of thermoplastic resin particles containing different types of thermoplastic resins, when the Tg of the n-th thermoplastic resin is set to Tgn(K) and the mass fraction of the n-th thermoplastic resin relative to the total mass of the thermoplastic resin component in the thermoplastic resin particles is set to Wn, the Tg of the thermoplastic resin particles can be estimated according to the following formula in the same manner as above.

[0642] FOX formula: 1 / Tg0=(W1 / Tg1)+(W2 / Tg2)+(W3 / Tg3)……+(Wn / Tgn)

[0643] As the differential scanning calorimeter (DSC), for example, EXSTAR6220 from Seiko Instruments Inc. can be used.

[0644] From the viewpoint of printing durability, the average particle diameter of the thermoplastic resin particles is preferably 1 to 200 nm, more preferably 3 nm or more and less than 80 nm, and further preferably 10 to 49 nm.

[0645] The average particle size of the thermoplastic resin particles refers to a value measured by dynamic light scattering (DLS) unless otherwise specified. The average particle size of the thermoplastic resin particles by DLS was measured using Brookhaven BI-90 (manufactured by Brookhaven Instrument Company) according to the manual of the instrument.

[0646] The weight average molecular weight of the thermoplastic resin contained in the thermoplastic resin particles is preferably 3,000 to 300,000, more preferably 5,000 to 100,000.

[0647] The method for producing the thermoplastic resin contained in the thermoplastic resin particles is not particularly limited, and the thermoplastic resin particles can be produced by a known method.

[0648] For example, it can be obtained by polymerizing a styrene compound, an acrylonitrile compound, and, if necessary, an N-vinyl heterocyclic compound, a compound used in the formation of a structural unit having an ethylenically unsaturated group, a compound used in the formation of a structural unit having an acidic group, a compound used in the formation of a structural unit having a hydrophobic group, and at least one compound used in the formation of other structural units using a known method.

[0649] As specific examples of the thermoplastic resin contained in the thermoplastic resin particles, preferably, there are mentioned the thermoplastic resins described in International Publication No. 2020 / 262692.

[0650] As the inorganic particles, known inorganic particles can be used, and metal oxide particles such as silica particles and titania particles can be preferably used.

[0651] The average particle size of the particles is preferably 0.01 to 3.0 μm, more preferably 0.03 to 2.0 μm, and still more preferably 0.10 to 1.0 μm. Within this range, good resolution and stability over time can be obtained.

[0652] The average particle size of the particles is measured by the dynamic light scattering method in the same manner as the average particle size of the thermoplastic resin particles. Alternatively, the measurement based on the dynamic light scattering method may be replaced by taking an electron microscope photo of the particles, measuring the particle size of a total of 5,000 particles on the photo, and calculating the arithmetic mean as the average particle size of the particles. In addition, for non-spherical particles, the diameter of a circle having the same area as the particle area on the photo is used.

[0653] In addition, the average particle size of particles is a volume average particle size unless otherwise specified.

[0654] The image recording layer may contain one type of particles (preferably polymer particles) alone, or two or more types thereof.

[0655] From the viewpoint of on-press developability and printing durability, the content of particles (preferably polymer particles) in the image recording layer is preferably 5 to 90% by mass, more preferably 10 to 90% by mass, further preferably 20 to 90% by mass, and particularly preferably 50 to 90% by mass, relative to the total mass of the image recording layer.

[0656] Furthermore, from the viewpoint of on-press developability and printing durability, the content of the polymer particles in the above-mentioned image recording layer is preferably 20 to 100 mass %, more preferably 35 to 100 mass %, further preferably 50 to 100 mass %, and particularly preferably 80 to 100 mass %, relative to the total mass of the components having a molecular weight of 3,000 or more in the above-mentioned image recording layer.

[0657] <Binder Polymer>

[0658] The image-recording layer may contain a binder polymer.

[0659] The polymer particles described above do not belong to the binder polymer described above. In other words, the binder polymer is a polymer that is not in the form of particles.

[0660] As the binder polymer, a (meth)acrylic resin, a polyvinyl acetal resin or a polyurethane resin is preferred.

[0661] As the binder polymer, a known binder polymer used in the image recording layer of a planographic printing plate precursor can be used. As an example, a binder polymer used in an on-press developing type planographic printing plate precursor (hereinafter also referred to as an on-press developing binder polymer) is described in detail.

[0662] As the binder polymer for on-machine development, a binder polymer having an alkylene oxide chain is preferred. The binder polymer having an alkylene oxide chain may have a poly(alkylene oxide) moiety in the main chain or in the side chain. Furthermore, it may be a graft polymer having a poly(alkylene oxide) in the side chain, or a block copolymer of a block composed of a repeating unit containing a poly(alkylene oxide) and a block composed of a repeating unit not containing an (alkylene oxide).

[0663] When the main chain has a poly(alkylene oxide) moiety, polyurethane resin is preferred. When the side chain has a poly(alkylene oxide) moiety, the main chain polymer includes (meth)acrylic resins, polyvinyl acetal resins, polyurethane resins, polyurea resins, polyimide resins, polyamide resins, epoxy resins, polystyrene resins, novolac-type phenolic resins, polyester resins, synthetic rubbers and natural rubbers, and (meth)acrylic resins are preferred.

[0664] Furthermore, as other preferred examples of binder polymers, there can be cited polymer compounds having a polyfunctional thiol having more than 6 functions and less than 10 functions as a core portion, a polymer chain bonded to the core portion via a sulfide bond, and the polymer chain having a polymerizable group (hereinafter also referred to as a star-shaped polymer compound).

[0665] As the star-shaped polymer compound, from the viewpoint of curability, preferably, a compound has a polymerizable group such as an ethylenically unsaturated group in a main chain or a side chain, and more preferably has a polymerizable group such as an ethylenically unsaturated group in a side chain.

[0666] Examples of the star-shaped polymer compound include compounds described in JP-A-2012-148555 and WO-2020 / 262692.

[0667] The molecular weight of the binder polymer (weight average molecular weight (Mw) obtained as a polystyrene conversion value based on the GPC method) is preferably 2,000 or more, more preferably 5,000 or more, and further preferably 10,000 to 300,000.

[0668] If necessary, a hydrophilic polymer such as polyacrylic acid or polyvinyl alcohol described in Japanese Patent Application Laid-Open No. 2008-195018 may be used in combination. Furthermore, a lipophilic polymer and a hydrophilic polymer may also be used in combination.

[0669] Furthermore, from the viewpoint of printing durability and on-press development properties, the image recording layer preferably contains a binder polymer comprising a structural unit formed from an aromatic vinyl compound, and more preferably contains a binder polymer comprising a structural unit formed from an aromatic vinyl compound and contains an infrared absorber that is decomposed by infrared exposure.

[0670] Furthermore, from the viewpoint of suppressing a decrease in on-press developability over time, the glass transition temperature (Tg) of the binder polymer is preferably 50° C. or higher, more preferably 70° C. or higher, further preferably 80° C. or higher, and particularly preferably 90° C. or higher.

[0671] The upper limit of the glass transition temperature of the binder polymer is preferably 200° C. or lower, and more preferably 120° C. or lower, from the viewpoint of facilitating water penetration into the image recording layer.

[0672] As the binder polymer having the above glass transition temperature, polyvinyl acetal is preferred from the viewpoint of further suppressing a decrease in on-press developability over time.

[0673] Polyvinyl acetal is a resin obtained by acetalizing the hydroxyl group of polyvinyl alcohol with an aldehyde. Among them, polyvinyl butyral obtained by acetalizing the hydroxyl group of polyvinyl alcohol with butyraldehyde (ie, butyralization) is preferred.

[0674] Furthermore, from the viewpoint of improving printing durability, the polyvinyl acetal preferably has an ethylenically unsaturated group.

[0675] Specific examples of polyvinyl acetal include polymers described in International Publication No. 2020 / 262692.

[0676] The image recording layer preferably contains a resin having fluorine atoms as a binder polymer, and more preferably contains a copolymer containing a fluoroaliphatic group.

[0677] By using a resin having fluorine atoms, especially a copolymer containing a fluorinated aliphatic group, surface quality abnormality caused by bubbling during formation of an image recording layer can be suppressed, the coating surface shape can be improved, and the ink adherence of the formed image recording layer can be improved.

[0678] Furthermore, the image recording layer containing the fluoroaliphatic group-containing copolymer has a high grayscale and, for example, high sensitivity to laser beams, and can obtain a planographic printing plate having good fogging resistance due to scattered light, reflected light, etc. and excellent printing durability.

[0679] Specific examples of the above-mentioned fluoroaliphatic group-containing copolymer include copolymers described in International Publication No. 2020 / 262692.

[0680] The binder polymer may be used alone or in combination of two or more.

[0681] The image recording layer may contain any amount of the binder polymer, and the content of the binder polymer is preferably 1 to 90% by mass, more preferably 5 to 80% by mass, based on the total mass of the image recording layer.

[0682] <Polymerization Inhibitor>

[0683] The image recording layer preferably contains a polymerization inhibitor from the viewpoint of better stability over time and better developability after time. The image recording layer containing a polymerization inhibitor can prevent unnecessary thermal polymerization of polymerizable compounds, especially radical polymerizable compounds, during the production or storage of the image recording layer.

[0684] Examples of the polymerization inhibitor include hydroquinone, p-methoxyphenol, di-tert-butyl-p-cresol, pyrogallol, tert-butylcatechol, benzoquinone, 4,4′-thiobis(3-methyl-6-tert-butylphenol), 2,2′-methylenebis(4-methyl-6-tert-butylphenol) and N-nitroso-N-phenylhydroxylamine aluminum salt.

[0685] As the polymerization inhibitor, a compound represented by the following formula (Ph) is preferred from the viewpoint of superior stability over time and developability after a certain period of time.

[0686] [Chemical formula 11]

[0687]

[0688] In formula (Ph), X P Indicates O, S or NH, Y P Indicates N or CH, R P1 represents a hydrogen atom or an alkyl group, R P2 and R P3 Each independently represents a halogen atom, an alkylthio group, an arylthio group, an alkoxy group, an aryloxy group, an alkyl group, an aryl group, an acylthio group or an acyl group; and mp and np each independently represent an integer of 0 to 4.

[0689] From the viewpoint of stability over time and developability after time, X in formula (Ph)P O or S is preferred, and S is more preferred.

[0690] From the viewpoint of stability over time and developability after time, Y in formula (Ph) P N is preferred.

[0691] From the viewpoint of stability over time and developability after time, R in formula (Ph) P1 A hydrogen atom or a methyl group is preferred, and a hydrogen atom is more preferred.

[0692] R in formula (Ph) P2 and R P2 A halogen atom, an alkylthio group, an arylthio group, an alkoxy group, an aryloxy group, an alkyl group or an aryl group is preferably each independently a group.

[0693] In the formula (Ph), mp and np are each independently preferably an integer of 0 to 2, more preferably 0 or 1, and even more preferably 0, from the viewpoint of stability over time and developability after time.

[0694] The polymerization inhibitor may be used alone or in combination of two or more.

[0695] The content of the polymerization inhibitor is preferably 0.001 to 5% by mass, more preferably 0.01 to 1% by mass, based on the total mass of the image recording layer.

[0696] <Chain transfer agent>

[0697] The image recording layer may contain a chain transfer agent. The chain transfer agent contributes to improving the printing durability of the planographic printing plate.

[0698] As the chain transfer agent, a thiol compound is preferred, and from the viewpoint of boiling point (low volatility), a thiol compound having 7 or more carbon atoms is more preferred, and a compound having 7 or more carbon atoms and having a mercapto group on an aromatic ring (aromatic thiol compound) is further preferred. As the thiol compound, a monofunctional thiol compound is preferred.

[0699] Specific examples of the chain transfer agent include compounds described in International Publication No. 2020 / 262692.

[0700] The chain transfer agent may be used alone or in combination of two or more.

[0701] The content of the chain transfer agent is preferably 0.01 to 50% by mass, more preferably 0.05 to 40% by mass, and further preferably 0.1 to 30% by mass, based on the total mass of the image recording layer.

[0702] <Other ingredients>

[0703] In the image recording layer, as other components other than the above, a sensitizer (e.g., a scaly compound, a nitrogen-containing low molecular compound, an ammonium group-containing polymer), a development accelerator, a surfactant, a higher fatty acid derivative, a plasticizer, an inorganic layered compound, etc. can be included. For these other components, reference can be made to paragraphs 0114 to 0159 of Japanese Patent Application Laid-Open No. 2008-284817.

[0704] Furthermore, specific examples of the development accelerator include compounds described in International Publication No. 2020 / 262692.

[0705] <Method for Forming Image Recording Layer>

[0706] The image recording layer can be formed by dispersing or dissolving the above components in a known solvent to prepare a coating solution, applying the coating solution on a support by a known method such as bar coating, and drying the coating solution, as described in paragraphs 0142 to 0143 of Japanese Patent Application Laid-Open No. 2008-195018.

[0707] As the solvent, a known solvent can be used, for example, water, acetone, methyl ethyl ketone (2-butanone), cyclohexane, ethyl acetate, ethylene dichloride, tetrahydrofuran, toluene, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol dimethyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, acetylacetone, cyclohexanone, diacetone alcohol, ethylene glycol monomethyl ether acetate, ethylene glycol ethyl ether acetate, ethylene glycol monoisopropyl ether, ethylene glycol monobutyl ether acetate, 1-methoxy-2-propanol, 3-methoxy-1-propanol, methoxymethoxyethanol, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, 3-methoxypropyl acetate, N,N-dimethylformamide, dimethyl sulfoxide, γ-butyrolactone, methyl lactate and ethyl lactate.

[0708] The solvent may be used alone or in combination of two or more. The solid content concentration in the coating liquid is preferably 1 to 50% by mass.

[0709] The coating weight (solid content) of the image recording layer after coating and drying varies depending on the application, but is preferably 0.3 to 3.0 g / m2 from the viewpoint of obtaining good sensitivity and good coating properties of the image recording layer. 2 .

[0710] The thickness of the image recording layer is preferably 0.1 to 3.0 μm, more preferably 0.3 to 2.0 μm.

[0711] The thickness of each layer in the lithographic printing plate precursor is measured by preparing a slice cut in a direction perpendicular to the surface of the lithographic printing plate precursor and observing the cross section of the slice using a scanning microscope (SEM).

[0712] (Other layers)

[0713] The lithographic printing plate precursor may include other layers in addition to the support and the image recording layer described above.

[0714] The lithographic printing plate precursor may have an undercoat layer disposed between the support and the image recording layer, if necessary, for example, to improve the adhesion between the support and the image recording layer.

[0715] Furthermore, the lithographic printing plate precursor may include a protective layer (overcoat layer) on the image recording layer as necessary to prevent scratches etc. from being generated in the image recording layer, block oxygen, and prevent ablation during high-intensity laser exposure.

[0716] <Base Coating>

[0717] The undercoat layer is a layer disposed between the support and the image recording layer, and has a function of improving the adhesion between the two.

[0718] The structure of the undercoat layer is not particularly limited, but it preferably contains polyvinylphosphonic acid from the viewpoint of suppressing ink adhesion in the unexposed portion while maintaining printing durability.

[0719] Here, as the polyvinylphosphonic acid, compounds disclosed in US Pat. No. 3,276,868, US Pat. No. 4,153,461, and US Pat. No. 4,689,272 can be used.

[0720] The structure of the undercoat layer is not particularly limited, but it preferably contains a compound having a betaine structure from the viewpoint of good stain resistance and ink removal ability during suspended printing.

[0721] Here, the betaine structure refers to a structure having at least one cation and at least one anion. In addition, generally, the number of cations is equal to the number of anions, and the structure is neutral as a whole. However, in this specification, when the number of cations is not equal to the number of anions, a structure having a necessary amount of counter ions in order to eliminate the charge is also considered as a betaine structure.

[0722] The content of the compound having the betaine structure in the primer layer is preferably 80% by mass or more, more preferably 90% by mass or more, based on the total mass of the primer layer, and the upper limit thereof may be 100% by mass.

[0723] The undercoat layer may be in a form containing other compounds in addition to the compound having a betaine structure.

[0724] For example, the primer layer may be in a form containing a compound having a hydrophilic group. Examples of the hydrophilic group include a carboxylic acid group and a sulfonic acid group.

[0725] The compound having a hydrophilic group may further have a radical polymerizable reactive group.

[0726] (Method for forming primer layer)

[0727] The primer layer is produced by forming the primer layer on a support.

[0728] The method for producing the undercoat layer is not particularly limited, and examples thereof include a method in which a coating liquid for forming an undercoat layer containing a predetermined compound (eg, a compound having a betaine structure) is applied onto the anodized film of the support.

[0729] The undercoat layer-forming coating liquid preferably contains a solvent. Examples of the solvent include water and organic solvents.

[0730] As a coating method for the coating liquid for forming the undercoat layer, various known methods can be mentioned, for example, bar coater coating, spin coating, spray coating, curtain coating, dip coating, air knife coating, blade coating and roll coating.

[0731] The coating amount (solid content) of the primer layer is preferably 0.1 to 100 mg / m 2 .

[0732] <Protective layer>

[0733] The lithographic printing plate precursor preferably has a protective layer (also referred to as "overcoat layer") on the surface of the image recording layer opposite to the support. That is, the lithographic printing plate precursor preferably has a support, an image recording layer, and a protective layer in this order.

[0734] The protective layer may have at least one of a function of suppressing an image formation inhibiting reaction by blocking oxygen, a function of preventing the generation of scratches in the image recording layer, and a function of preventing ablation during high-intensity laser exposure.

[0735] The protective layer of this characteristic is described in, for example, U.S. Patent No. 3,458,311 and Japanese Patent Publication No. 55-049729. As the low oxygen permeability polymer used in the protective layer, any one of a water-soluble polymer and a hydrophobic polymer (water-insoluble polymer) can be appropriately selected for use, and two or more kinds can be mixed and used as needed. From the viewpoint of on-press developability, a water-soluble polymer is preferred.

[0736] In this specification, a water-soluble polymer refers to a polymer having a solubility in pure water at 25° C. exceeding 5% by mass.

[0737] Examples of the water-soluble polymer used in the protective layer include polyvinyl alcohol, modified polyvinyl alcohol, polyvinyl pyrrolidone, cellulose derivatives, polyethylene glycol, and poly(meth)acrylonitrile.

[0738] Furthermore, the water-soluble polymer preferably contains at least one selected from modified polyvinyl alcohol and cellulose derivatives.

[0739] As the modified polyvinyl alcohol, an acid-modified polyvinyl alcohol having a carboxyl group or a sulfonic group can be preferably used. Specifically, the modified polyvinyl alcohols described in JP-A-2005-250216 and JP-A-2006-259137 can be mentioned.

[0740] Examples of the cellulose derivative include methyl cellulose, hydroxypropyl methyl cellulose, and carboxymethyl cellulose.

[0741] The water-soluble polymer preferably contains polyvinyl alcohol, and more preferably contains polyvinyl alcohol having a saponification degree of 50% or more.

[0742] The saponification degree is preferably 60% or more, more preferably 70% or more, and even more preferably 85% or more. The upper limit of the saponification degree is not particularly limited as long as it is 100% or less.

[0743] The saponification degree is measured according to the method described in JIS K 6726:1994.

[0744] Furthermore, as one aspect of the protective layer, an aspect including polyvinyl alcohol and polyethylene glycol is also preferably mentioned.

[0745] When the protective layer contains a water-soluble polymer, the content of the water-soluble polymer is preferably 1 to 99% by mass, more preferably 3 to 97% by mass, and further preferably 5 to 95% by mass based on the total mass of the protective layer.

[0746] The protective layer preferably comprises a hydrophobic polymer.

[0747] The hydrophobic polymer refers to a polymer that dissolves less than 5 g or does not dissolve in 100 g of pure water at 125°C.

[0748] Examples of the hydrophobic polymer include polyethylene, polystyrene, polyvinyl chloride, polyvinylidene chloride, polyalkyl (meth)acrylates (e.g., polymethyl (meth)acrylate, polyethyl (meth)acrylate, polybutyl (meth)acrylate, etc.), and copolymers obtained by combining raw material monomers of these resins.

[0749] It is preferable that a polyvinylidene chloride resin is contained as the hydrophobic polymer. Also, it is preferable that a styrene-acrylic copolymer (also referred to as a styrene acrylic resin) is contained as the hydrophobic polymer.

[0750] From the viewpoint of on-press developability, the hydrophobic polymer is preferably hydrophobic polymer particles.

[0751] The hydrophobic polymer may be used alone or in combination of two or more.

[0752] When the protective layer contains a hydrophobic polymer, the content of the hydrophobic polymer is preferably 1 to 70% by mass, more preferably 5 to 50% by mass, and further preferably 10 to 40% by mass, based on the total mass of the protective layer.

[0753] From the viewpoint of improving the visibility of the exposed portion, the protective layer preferably contains a color body precursor.

[0754] The chromogen precursor is a compound that develops color when stimulated by light, acid, or the like and has a property of changing the color of the image recording layer.

[0755] Examples of the color body precursor include infrared absorbers and acid coloring agents.

[0756] The protective layer preferably contains an infrared absorber as a color body precursor, and more preferably contains a decomposable infrared absorber.

[0757] The infrared absorbing agent and the acid color forming agent contained in the protective layer are the same as those contained in the image recording layer, including preferred embodiments thereof.

[0758] The color body precursor contained in the protective layer may be used alone or in combination of two or more components.

[0759] From the viewpoint of color development properties, the content of the color body precursor in the protective layer is preferably 0.10 to 50% by mass, more preferably 0.50 to 30% by mass, and further preferably 1.0 to 20% by mass based on the total mass of the protective layer.

[0760] From the viewpoint of suppressing poor development failure, the protective layer preferably contains a filler.

[0761] Examples of fillers include inorganic particles, organic resin particles, and inorganic layered compounds. Among them, inorganic layered compounds are preferred. By using inorganic layered compounds, it is possible to effectively prevent re-attached matter from the roller surface from directly attaching to the image recording layer surface.

[0762] Examples of the inorganic particles include metal oxide particles such as silica particles. The inorganic layered compounds described below are not included in the inorganic particles.

[0763] Examples of the organic resin particles include crosslinked resin particles.

[0764] Inorganic layered compounds are particles having a thin plate shape, and examples thereof include natural mica, synthetic mica, and mica of the formula: 3MgO·4SiO·H 2 O represents talc, mica, montmorillonite, saponite, hectorite, zirconium phosphate, and the like.

[0765] The inorganic layered compound that can be preferably used is a mica compound. Examples of the mica compound include a mica compound represented by the formula: A(B, C) 2-5 D 4 O 10 (OH, F, O) 2 [A is any one of K, Na and Ca, B and C are any one of Fe(II), Fe(III), Mn, Al, Mg and V, and D is Si or Al.] A mica group such as natural mica and synthetic mica represented by.

[0766] In the mica group, examples of natural mica include muscovite, sodium mica, phlogopite, biotite, and lepidolite. Examples of synthetic mica include fluorphlogopite KMg 3 (AlSi 3 O 10 )F 2 、Potassium tetrasilicon mica (KMg 2.5 Si 4 O 10 )F 2 Non-swelling mica and Na tetrafluorosilicon mica NaMg 2.5 (Si 4 O 10 )F 2 、Na or Li with mica (Na, Li)Mg 2 Li(Si 4 O 10 )F 2 , Na or Li hectorite of the montmorillonite system (Na, Li) 1 / 8 Mg 2 / 5 Li 1 / 8 (Si 4 O 10 )F 2 Swellable mica, etc. Furthermore, synthetic bentonite is also useful.

[0767] As for the shape of the mica compound, from the viewpoint of diffusion control, the thinner the thickness, the better, and the larger the plane size, the better within a range that does not hinder the smoothness of the coating surface and the transmittance of the activating light.

[0768] Therefore, the aspect ratio is preferably 20 or more, more preferably 100 or more, and further preferably 200 or more. The aspect ratio is the ratio of the major diameter of the particle to the thickness, and can be measured, for example, from a projection of a micrograph of the particle. The larger the aspect ratio, the higher the effect obtained.

[0769] The particle size of the mica compound is preferably an average major diameter of 0.3 to 20, more preferably 0.5 to 10 μm, and further preferably 1 to 5 μm. The average thickness of the particles is preferably 0.1 μm or less, more preferably 0.05 μm or less, and further preferably 0.01 μm or less. In the case of swelling synthetic mica as a representative compound, the thickness is preferably about 1 to 50 nm and the surface size (major diameter) is about 1 to 20 μm.

[0770] The content of the inorganic layered compound is preferably 1 to 60% by mass, more preferably 3 to 50% by mass, relative to the total mass of the protective layer. When multiple inorganic layered compounds are used in combination, the total amount of the inorganic layered compounds is also preferably the above content. Within the above range, the oxygen barrier is improved and good sensitivity can be obtained. In addition, it is possible to prevent the ink adhesion from being reduced.

[0771] The protective layer may contain, in addition to the above components, known additives such as a plasticizer for imparting flexibility and a surfactant for improving coating properties. Furthermore, the protective layer may contain the sensitizer described in the image recording layer.

[0772] The protective layer can be formed by a known method of applying a composition containing the above-mentioned components. The coating amount of the protective layer (in terms of solid content) is preferably 0.0 to 10 g / m 2 , more preferably 0.02 to 3 g / m 2 , more preferably 0.02 to 1 g / m 2 .

[0773] The film thickness of the protective layer in the lithographic printing plate precursor is not particularly limited, but is preferably 0.1 to 5.0 μm, and more preferably 0.3 to 4.0 μm.

[0774] The lithographic printing plate precursor may further have a known layer laminated on the lithographic printing plate precursor other than the above. For example, a back coat layer may be provided on the surface of the support on the side opposite to the image recording layer side as required.

[0775] [Laminated body]

[0776] The lithographic printing plate precursor may constitute a laminated body in which a plurality of lithographic printing plate precursors are laminated.

[0777] It is preferred that the laminated body formed by stacking a plurality of lithographic printing plate originals also has a protective material for protecting the lithographic printing plate originals. The lithographic printing plate original is a thin plate-shaped support made of metal, so if there are bends, scratches or deformations at the corners, edges and inside, it is easy to cause problems such as blurred images during exposure or uneven ink during printing. Therefore, in the case of forming a laminated body in which a plurality of originals are stacked, it is preferred to configure a protective material for a predetermined number of originals to protect the originals.

[0778] For example, by packaging a stack of a plurality of planographic printing plate originals and a protective material with a packaging material to form a package, and performing cargo handling (transportation and storage, etc.) of the package, deformation (bending, etc.) of the original during cargo handling is less likely to occur, thereby suppressing damage to the original. Furthermore, even if external force acts on the package, part of it is absorbed by the protective material, thereby suppressing deformation and scratches of the original.

[0779] The placement of the protective material in the stack is not particularly limited, and examples thereof include the top of the stack, between the stacked planographic printing plate precursors, and the bottom of the stack. The protective material is preferably placed at least at the top of the stack, and more preferably at least at the top and bottom.

[0780] The material of the protective material is not particularly limited, and examples thereof include thick paper, cardboard, and plastic. From the viewpoint of suppressing poor development failure, cardboard or plastic is preferred, and plastic is more preferred. Examples of the plastic include polyester, polycarbonate, and polyolefin, and polyester is preferred.

[0781] The size (vertical and horizontal) and thickness of the protective material are not particularly limited and can be appropriately selected depending on the lithographic printing plate precursor to be protected.

[0782] The moisture content of the protective material is preferably 10% by mass or less, more preferably 7% by mass or less, and further preferably 3% by mass or less from the viewpoint of suppressing poor development failure. The lower limit of the moisture content is 0% by mass. The moisture content (equilibrium moisture content) of the protective material is measured by the method described in JIS P 8202 (1998).

[0783] The laminate may have interleaving paper between the lithographic printing plate precursors.

[0784] Examples of the material of the interleaving paper include paper made of 100% by mass wood pulp, paper made of a mixture of wood pulp and synthetic pulp, and paper having a low-density or high-density polyethylene layer provided on the surface thereof.

[0785] Furthermore, the entire stacked body may be packaged with a known packaging material.

[0786] [Method for producing lithographic printing plate precursor]

[0787] Examples of the method for producing the lithographic printing plate precursor of the present invention include a method comprising the steps of preparing a support including an aluminum alloy plate and an anodic oxide film and forming an image recording layer on the surface of the anodic oxide film side of the prepared support.

[0788] The process of manufacturing the support is described in the above-mentioned <Method for Manufacturing Support>, and the process of forming the image recording layer is described in the above-mentioned <Method for Forming Image Recording Layer>.

[0789] If necessary, after the step of preparing the support, a step of forming a primer layer on the surface of the obtained support on the anodized film side may be performed, and then a step of forming the image recording layer on the surface of the formed primer layer may be performed.

[0790] Furthermore, after performing the step of forming the image recording layer, a step of forming a protective layer on the surface of the formed image recording layer may be performed.

[0791] The method for forming the primer layer and the step for forming the protective layer are as described above.

[0792] [Method for producing lithographic printing plate, printing method]

[0793] A method for producing a lithographic printing plate using a lithographic printing plate precursor and a printing method using the lithographic printing plate precursor are described.

[0794] The method for manufacturing a lithographic printing plate of the present invention comprises: exposing the image recording layer of the lithographic printing plate original to an image state (image exposure) to form an exposed portion and an unexposed portion (exposure step); and supplying at least one of printing ink and fountain solution on a printing press, and removing the unexposed portion of the image recording layer exposed to an image state, thereby manufacturing the lithographic printing plate (on-press development step).

[0795] The printing method of the present invention, for example, includes: exposing the image recording layer of the planographic printing plate original into an image state (image exposure) to form an exposed portion and an unexposed portion (exposure step); supplying at least one of printing ink and fountain solution on a printing press and removing the unexposed portion of the image recording layer to produce a planographic printing plate (on-press development step); and a step of printing using the produced planographic printing plate (printing step).

[0796] Hereinafter, each of the above steps will be described in detail.

[0797] <Exposure Process>

[0798] The method for producing a lithographic printing plate and the printing method of the present invention include an exposure step of image-wise exposing the image recording layer of the lithographic printing plate precursor to form exposed areas and unexposed areas.

[0799] Image exposure is performed, for example, by laser exposure through a transparent original having a line image or a halftone dot image or by laser beam scanning based on digital data.

[0800] The wavelength of the light source for image exposure is preferably 750 to 1,400 nm. When a light source emitting light with a wavelength of 750 to 1,400 nm is used, it is preferred to use an image recording layer containing an infrared absorbing agent having absorption in this wavelength region.

[0801] As the light source emitting light with a wavelength of 750 to 1,400 nm, there can be mentioned solid lasers and semiconductor lasers that radiate infrared light. For infrared lasers, the output power is preferably 100 mW or more, the exposure time per pixel is preferably within 20 microseconds, and the irradiation energy is preferably 10 to 300 mJ / cm 2 Furthermore, it is preferable to use a multi-beam laser device to shorten the exposure time. The exposure mechanism may be any of an inner drum type, an outer drum type, and a flat plate type.

[0802] Image exposure can be performed by a conventional method using a plate-making machine, etc. Image exposure can be performed on a printing press after the planographic printing plate precursor is mounted on the printing press.

[0803] <On-press development process>

[0804] In the on-press development step, at least one of a printing ink and a fountain solution is supplied to the image-exposed lithographic printing plate precursor on a printing press to remove the image recording layer in the unexposed area, thereby producing a lithographic printing plate.

[0805] That is, if after the lithographic printing plate precursor is exposed to the image, it is directly installed on the printing press without any developer treatment, or after the lithographic printing plate precursor is installed on the printing press, the image is exposed on the printing press, and then the printing ink and the fountain solution are supplied and printing is performed, then in the initial stage of printing, in the unexposed part, the unexposed part of the image recording layer is dissolved or dispersed and removed by the supplied printing ink and / or fountain solution, so that the hydrophilic surface is exposed to the part. On the other hand, in the exposed part, the image recording layer solidified by exposure forms an oily ink receiving part with an oleophilic surface. The compound first supplied to the plate surface can be a printing ink or a fountain solution, but from the viewpoint of preventing contamination of the image recording layer components from which the fountain solution is removed, it is preferred to supply the printing ink first.

[0806] In this way, the lithographic printing plate precursor is produced on a printing press by on-press development and is directly used in a multi-sheet printing operation.

[0807] <Printing process>

[0808] The printing method includes a printing step of printing on a recording medium using a planographic printing plate manufactured through an exposure step and an on-press development step.

[0809] As the printing ink used in the printing step, various known inks can be used as needed. As the printing ink, oil-based ink or ultraviolet curing ink (UV ink) is preferred.

[0810] In the above-mentioned printing step, a fountain solution may be further supplied as needed.

[0811] Regarding the above-mentioned printing step, the above-mentioned on-press development step may be continuously performed without stopping the printing press.

[0812] As the recording medium, a known recording medium can be used as necessary.

[0813] In the method for producing a lithographic printing plate and the printing method, the entire surface of the lithographic printing plate precursor or the lithographic printing plate may be heated as required before exposure, during exposure, from exposure to development, and after development. Such heating can promote the image forming reaction in the image recording layer, resulting in advantages such as improved sensitivity and printing durability, and stabilization of sensitivity.

[0814] When the lithographic printing plate precursor is heated before development, problems such as curing of the unexposed portion can be prevented, and therefore, heating is preferably performed under mild conditions of 150° C. or less.

[0815] When the planographic printing plate is heated after development, sufficient image enhancement can be obtained and problems such as degradation of the support and thermal decomposition of the image area can be suppressed. Therefore, it is preferably heated under very strong conditions, for example, in the range of 100 to 500°C.

[0816] Example

[0817] Hereinafter, the present invention will be described in detail by examples, but the materials, usage, ratio, processing contents and processing sequence etc. shown in the following examples can be appropriately changed without departing from the purpose of the present invention. Therefore, the scope of the present invention will not be interpreted in a limited manner by the specific examples shown below.

[0818] In the present examples, “parts” refers to “parts by mass” unless otherwise specified. In polymer compounds, molecular weight refers to weight average molecular weight (Mw) and the ratio of structural repeating units refers to molar percentage unless otherwise specified.

[0819] [Manufacturing Example A: Manufacture of Aluminum Alloy Plate]

[0820] [Manufacturing Examples A1 to A9]

[0821] Aluminum alloy plates of Production Examples A1 to A9 were produced as follows.

[0822] Aluminum alloy molten metal consisting of 0.08 mass % Si, 0.31 mass % Fe, 0.002 mass % Cu, 0.020 mass % Ti, 0.05 mass % or less of other components, and the remainder being Al was continuously cast by twin-roll continuous casting to a cast plate thickness of 5.5 mm.

[0823] During continuous casting, the cooling rate conditions of the casting process were appropriately adjusted within the range of 100 to 500° C. / sec for each production example. The density of the specific intermetallic compound in the aluminum alloy plate can be adjusted according to the cooling rate conditions.

[0824] Next, the obtained continuously cast plate was cold-rolled to a plate thickness of 0.9 mm, and then subjected to intermediate annealing heat treatment at 450° C. for 4 hours, and further cold-rolled again to a finish thickness of 0.3 mm.

[0825] Next, flatness correction was performed using a tension leveler to produce each aluminum alloy plate. The aluminum alloy plates produced in Production Examples A1 to A9 in which the cooling rate conditions of the casting process were changed were referred to as aluminum alloy plates 1 to 9, respectively.

[0826] The composition of each aluminum alloy plate produced was the same as the composition of the aluminum alloy molten metal used in the production. The density of the intermetallic compound with a major diameter of 2.0 μm or more on the surface of the produced aluminum alloy plate was the same as the density of the specific intermetallic compound shown in Table 2 below.

[0827] [Comparative Production Examples A1 to A3]

[0828] The aluminum alloy plates of Comparative Manufacturing Examples A1 to A3 were produced as follows.

[0829] Using aluminum alloy molten metal having the same composition as that of the aluminum alloy plates of Production Examples A1 to A9, slabs having a thickness of 500 mm were cast by DC (Direct Chill) casting.

[0830] During casting, the cooling rate conditions of the casting process were appropriately adjusted within the range of a cooling rate of 1 to 5° C. / sec for each comparative manufacturing example.

[0831] Next, after cutting away a 20 mm thick region from both surfaces of the obtained slab, heat treatment (soaking treatment) was performed at 500 to 600° C. in the slab state.

[0832] Next, the heat-treated slab was hot-rolled to a thickness of 3 mm, intermediate annealed at 410 to 550° C., and then cold-rolled to a thickness of 0.3 mm.

[0833] Next, flatness correction was performed using a tension leveler to produce each aluminum alloy plate. The aluminum alloy plates produced in Comparative Production Examples A1 to A3 in which the cooling rate conditions of the casting process were changed were referred to as aluminum alloy plates C1 to C3, respectively.

[0834] The composition of each aluminum alloy plate produced was the same as the composition of the aluminum alloy molten metal used in the production. The density of the intermetallic compound with a major diameter of 2.0 μm or more on the surface of the produced aluminum alloy plate was the same as the density of the specific intermetallic compound shown in Table 2 below.

[0835] [Manufacturing Example B: Manufacture of Support Body]

[0836] [Production Example B1]

[0837] The aluminum alloy plate 1 having a thickness of 0.3 mm produced in the above-mentioned Production Example A1 was subjected to the following treatments to produce a support 1. In addition, a water washing treatment was performed between all the treatment steps in the production of the support, and liquid was drained by a nip roll after the water washing treatment.

[0838] <Alkali Etching Treatment (1)>

[0839] The etching treatment was performed by spraying a caustic soda aqueous solution with a caustic soda concentration of 26 mass % and an aluminum ion concentration of 6.5 mass % at a temperature of 70°C onto the aluminum alloy plate using a sprayer. Afterwards, the plate was rinsed with water using a sprayer. The amount of aluminum dissolved in the surface subjected to electrochemical roughening treatment was 5 g / m 2 .

[0840] <Decontamination treatment using an acidic aqueous solution (1)>

[0841] Next, decontamination treatment was performed using an acidic aqueous solution. Specifically, the decontamination treatment was performed for 3 seconds by spraying the acidic aqueous solution onto the aluminum alloy plate using a sprayer. The acidic aqueous solution used in the decontamination treatment was an aqueous solution of 150 g / L sulfuric acid. The liquid temperature was 30°C.

[0842] <Hydrochloric acid electrolysis treatment>

[0843] Next, hydrochloric acid electrolysis was performed using an electrolytic solution having a hydrochloric acid concentration of 13 g / L, an aluminum ion concentration of 15 g / L, and a sulfuric acid concentration of 1.0 g / L, using an alternating current. The electrolyte temperature was 25° C. Aluminum chloride was added to adjust the aluminum ion concentration.

[0844] The waveform of the AC current is a sine wave with symmetrical positive and negative waveforms, the frequency is 50Hz, the anode reaction time and cathode reaction time in one cycle of the AC current are 1:1, and the current density is 35A / dm based on the current peak value of the AC current waveform. 2In addition, the total amount of electricity in the aluminum alloy plate participating in the anode reaction is 300C / dm 2 For electrolysis, the current was 75C / dm at a 2.5 second interval. 2 This was performed four times. A carbon electrode was used as the counter electrode of the aluminum alloy plate. Afterwards, a water washing treatment was performed.

[0845] <Alkali Etching Treatment (2)>

[0846] The aluminum alloy plate after hydrochloric acid electrolysis was etched by spraying a caustic soda aqueous solution with a caustic soda concentration of 5 mass % and an aluminum ion concentration of 0.5 mass % at a temperature of 45°C. The amount of aluminum dissolved on the surface subjected to hydrochloric acid electrolysis was 0.2 g / m 2 After that, a water washing process was performed.

[0847] <Decontamination treatment using an acidic aqueous solution (2)>

[0848] Next, decontamination treatment was performed using an acidic aqueous solution. Specifically, the decontamination treatment was performed for 3 seconds by spraying the acidic aqueous solution onto the aluminum alloy plate using a sprayer. As the acidic aqueous solution used for decontamination treatment, an aqueous solution with a sulfuric acid concentration of 170 g / L and an aluminum ion concentration of 5 g / L was used. The liquid temperature was 35°C.

[0849] <First Anodizing Treatment>

[0850] use Figure 8 The first anodizing treatment (surface anodizing treatment) was performed using a direct current electrolysis anodizing device having the structure shown. The anodizing treatment was performed under the conditions shown in Table 1 to form an anodized film having a predetermined film thickness. The concentration of sulfuric acid in the first anodizing treatment was 170 g / L.

[0851] exist Figure 8 In the anodizing treatment device 610 shown in FIG. Figure 8The aluminum alloy plate 616 is transported as shown by the arrow in the middle. The aluminum alloy plate 616 is charged (+) by the power supply electrode 620 in the power supply tank 612 storing the electrolyte 618. In addition, the aluminum alloy plate 616 is transported upward by the roller 622 in the power supply tank 612, and after changing its direction downward by the clamping roller 624, it is transported to the electrolytic treatment tank 614 storing the electrolyte 626, and is changed in the horizontal direction by the roller 628. Next, the aluminum alloy plate 616 is charged (-) by the electrolytic electrode 630, thereby forming an anodic oxide film on its surface, and the aluminum alloy plate 616 leaving the electrolytic treatment tank 614 is transported to the subsequent process. In the anodizing device 610, a direction conversion mechanism is formed by rollers 622, clamping rollers 624, and rollers 628. In the inter-tank portion between the power supply tank 612 and the electrolytic treatment tank 614, the aluminum alloy plate 616 is conveyed in a mountain shape and an inverted U shape by rollers 622, clamping rollers 624, and rollers 628. The power supply electrode 620 and the electrolytic electrode 630 are connected to a DC power supply 634. A tank wall 632 is disposed between the power supply tank 612 and the electrolytic treatment tank 614.

[0852] <Hole expansion treatment>

[0853] The anodized aluminum alloy plate was immersed in a caustic soda aqueous solution having a temperature of 40° C., a caustic soda concentration of 5 mass % and an aluminum ion concentration of 0.5 mass %, and subjected to a pore expansion treatment for the treatment time shown in Table 1. Thereafter, the plate was washed with water using a sprayer.

[0854] <Second Anodizing Treatment>

[0855] use Figure 8 The aluminum alloy plate subjected to the above-mentioned hole expansion treatment was subjected to a second anodizing treatment (lower layer anodizing treatment) by a direct current electrolysis anodizing device of the structure shown. Anodizing treatment was performed under the conditions shown in Table 1, and an anodized film having a predetermined film thickness was formed to manufacture a support 1. The concentration of sulfuric acid in the second anodizing treatment was 170 g / L.

[0856] [Manufacturing Examples B2 to 20, 23 and 24, Comparative Manufacturing Examples B1 to B3]

[0857] The supporting bodies were respectively prepared according to the same steps as in Manufacturing Example B1, except that the aluminum alloy plates shown in Table 1 were used instead of the aluminum alloy plate 1, and the conditions of the alkali etching treatment (2), the conditions of the anodizing treatment and / or the conditions of the hole expansion treatment in Manufacturing Example B1 were changed to the conditions shown in Table 1.

[0858] [Production Example B21]

[0859] The conditions of the alkali etching treatment (2), the conditions of the anodizing treatment and / or the conditions of the hole expansion treatment were changed to the conditions shown in Table 1. In addition, the same steps as those in Manufacturing Example B1 were followed to carry out alkali etching treatment (1), decontamination treatment (1), hydrochloric acid electrolysis treatment, alkali etching treatment (2), decontamination treatment (2), the first anodizing treatment (surface anodizing treatment) and the hole expansion treatment.

[0860] <Intermediate layer anodizing treatment (1)>

[0861] use Figure 8 The aluminum alloy plate subjected to the hole expansion treatment was subjected to an intermediate layer anodization treatment using a direct current electrolysis anodizing device having the structure shown. The anodization treatment was performed under the conditions shown in Table 1 to form an anodized film having a predetermined film thickness.

[0862] use Figure 8 The anodizing apparatus based on direct current electrolysis of the structure shown performs a second anodizing treatment (lower layer anodizing treatment) on the aluminum alloy plate subjected to the above-mentioned intermediate layer anodizing treatment (1) under the conditions shown in Table 1 to form an anodized film of a specified film thickness, thereby manufacturing the support body 21.

[0863] Micropores including upper pores, middle pores, and small-diameter pores are formed in the anodized film of the support body 21 .

[0864] [Production Example B22]

[0865] The conditions of the alkali etching treatment (2), the conditions of the anodizing treatment and / or the conditions of the pore expansion treatment were changed to the conditions shown in Table 1. In addition, the same steps as those in Manufacturing Example B21 were followed to carry out alkali etching treatment (1), decontamination treatment (1), hydrochloric acid electrolysis treatment, alkali etching treatment (2), decontamination treatment (2), first anodizing treatment (surface anodizing treatment), pore expansion treatment and intermediate layer anodizing treatment (1).

[0866] <Intermediate layer anodizing treatment (2)>

[0867] use Figure 8 The aluminum alloy plate subjected to the intermediate layer anodizing treatment (1) was subjected to the second intermediate layer anodizing treatment by using a direct current electrolysis anodizing device having the structure shown. The anodizing treatment was performed under the conditions shown in Table 1 to form an anodized film having a predetermined film thickness.

[0868] use Figure 8The anodizing apparatus based on direct current electrolysis of the structure shown performs a second anodizing treatment (lower layer anodizing treatment) on the aluminum alloy plate that has been subjected to the above-mentioned intermediate layer anodizing treatment (2) under the conditions shown in Table 1 to form an anodized film of a specified film thickness, thereby manufacturing the support body 22.

[0869] Micropores including an upper pore portion, a middle pore portion having a two-layer structure, and a small-diameter pore portion are formed in the anodized film of the support body 22 .

[0870] The density of the specific intermetallic compound and various physical properties of the anodic oxide film were measured by the above-mentioned methods for the supports 1 to 24 produced in Production Examples B1 to 24 and the supports C1 to C3 produced in Comparative Production Examples B1 to B3.

[0871] In the table, with respect to support body 21 and support body 22, the "Average Diameter" column and the "Depth" column of the "Large Diameter Hole Portion" column respectively indicate the average diameter and depth of the coating surface of the "upper hole portion", and the "Average Diameter" column and the "Depth" column of the "Small Diameter Hole Portion" column respectively indicate the average diameter and depth of the "lower hole portion" at the connecting position with the middle hole portion.

[0872] In the table, regarding the support body 21, the column "Maximum diameter (1)" in the column "Middle hole" indicates the maximum value of the inner diameter of the middle hole.

[0873] In the table, regarding the support body 22, the "Maximum Diameter (1)" column of the "Middle Hole" column indicates the maximum value of the inner diameter of the first middle hole, and the "Maximum Diameter (2)" column indicates the maximum value of the inner diameter of the second middle hole.

[0874]

[0875]

[0876] [Preparation of undercoat layer coating liquid]

[0877] The following components were mixed to prepare undercoat layer coating solutions 1 to 4 for forming an undercoat layer.

[0878] (Undercoat coating liquid 1)

[0879] Polyacrylic acid aqueous solution (40% by mass, "Jurymer AC-10S" manufactured by TOAGOSEI CO., LTD.): 3.0 parts

[0880] Water: 27.0 parts

[0881] (Undercoat coating liquid 2)

[0882] · Compound for undercoat layer represented by the following structural formula (U-1) (11 mass % aqueous solution): 0.1050 parts

[0883] Sodium gluconate: 0.0700 parts

[0884] Surfactant (EMALEX (registered trademark) 710, manufactured by NIHON EMULSION Co., Ltd.): 0.0016 parts

[0885] · Preservative (Biohope L, K·I Chemical Industry Co., LTD.): 0.0015 parts

[0886] Water: 3.2900 parts

[0887] [Chemical formula 12]

[0888]

[0889] (Undercoat coating liquid 3)

[0890] Compound for undercoat layer (U-1) (11 mass % aqueous solution): 0.1050 parts

[0891] Sodium gluconate: 0.0700 parts

[0892] Sipomer Pam-100 (Solvay): 0.0058 parts

[0893] Surfactant (EMALEX710, manufactured by NIHON EMULSION Co., Ltd.): 0.0016 parts

[0894] · Preservative (manufactured by Biohope L, K·I Chemical Industry Co., LTD.): 0.0015 parts

[0895] Water: 3.2900 parts

[0896] (Undercoat coating liquid 4)

[0897] · Compound for primer layer (U-2) (vinylphosphonic acid / acrylamide copolymer (molar ratio 1:9)): 0.3200 parts

[0898] Sipomer Pam-100 (Solvay): 0.0970 parts

[0899] Surfactant (EMALEX710, manufactured by NIHON EMULSION Co., Ltd.): 0.0016 parts

[0900] · Preservative (Biohope L, manufactured by K·I Chemical Industry Co., LTD.): 0.0015 parts

[0901] Water: 3.2900 parts

[0902] The compound for undercoat layer (U-2) was synthesized by the following method.

[0903] In a 10-liter flask equipped with a stirrer, a capacitor, and a dropping device, 3500 g of ethanol was added and heated to 70°C. Next, 231.1 g (2.14 moles) of vinylphosphonic acid monomer, 1368.9 g (19.26 moles) of acrylamide, and 52 g of AIBN were dissolved in 1000 g of ethanol, and the solution was added dropwise to the reaction device over 4 hours. During the addition of the monomer solution, a white precipitate was generated. After further heating and stirring for 2 hours while maintaining the temperature at 70°C, the heating was stopped and the reaction solution was cooled to room temperature. The generated precipitate was collected by vacuum filtration and washed with 1000 g of ethanol. The precipitate was vacuum dried at 40°C for 24 hours to obtain white microcrystals (yield: 1,550 g).

[0904] [Preparation of coating liquid for image recording layer]

[0905] The components shown below were used to prepare an image recording layer coating liquid for forming an image recording layer.

[0906] (Acid coloring agent)

[0907] As the acid coloring agent, the above-mentioned compounds S-1 to S-20 and the following compounds S-C1 and S-C2 were used.

[0908] [Chemical formula 13]

[0909]

[0910] In the Examples and Comparative Examples, the absorption maximum wavelength λmax (nm), the color development coefficient (L·mol -1 cm -1 ) and molecular weight are shown in the later-described Table 3. In addition, the absorption maximum wavelength λmax and color development coefficient of the acid coloring agent were measured by the above-mentioned method.

[0911] In addition, compounds S-2, S-5 and S-6 have two peaks representing the maximum absorption wavelength λmax in the visible light region (380 to 750 nm). Table 3 described below shows the maximum absorption wavelength λmax and the color development coefficient of each peak.

[0912] (Infrared absorber)

[0913] As the infrared absorber, the following compounds IR-1 to IR-9 were used.

[0914] The structural formula and the energy level of the lowest unoccupied molecular orbital (LUMO) of each of compounds IR-1 to IR-9 are shown below.

[0915] [Chemical formula 14]

[0916]

[0917] [Chemical formula 15]

[0918]

[0919] (Polymerization initiator)

[0920] As polymerization initiators, the following compounds I-1 to I-3 and B-1 were used. The iodonium ion of compound I-1, the iodonium ion of compound I-2 and compound I-3 were electron accepting polymerization initiators, and the borate compound of compound I-1 and compound B-1 were electron donating polymerization initiators.

[0921] The structural formula and the energy level of the lowest unoccupied molecular orbital (LUMO) of each polymerization initiator are shown below.

[0922] [Chemical formula 16]

[0923]

[0924] (Polymerizable compound)

[0925] As the polymerizable compound, the following compounds M-1 to M-5 were used.

[0926] M-1: polyurethane acrylate (40% 2-butanone solution) obtained by reacting DESMODUR (registered trademark) N100 (manufactured by Bayer), hydroxyethyl acrylate and pentaerythritol triacrylate at a molar ratio of 1:1.5:1.5.

[0927] M-2: 2-ethoxy (10 ethylene oxide) bisphenol A acrylate (40% solution in 2-butanone).

[0928] M-3: polyurethane acrylate (80% 2-butanone solution) obtained by reacting DESMODUR (registered trademark) N100 (manufactured by Bayer), hydroxyethyl acrylate and pentaerythritol triacrylate at a molar ratio of 1:1.5:1.5.

[0929] M-4: A compound represented by the following structural formula.

[0930] M-5: A compound represented by the following structural formula.

[0931] [Chemical formula 17]

[0932]

[0933] (Polymer particles)

[0934] As the polymer particles, the following polymer particles PP-1 to PP-3 were used.

[0935] -Polymer particles PP-1-

[0936] The following polymer emulsion was used: polymer particles containing 24% of a graft copolymer of poly(ethylene glycol) methyl ether methacrylate / styrene / acrylonitrile = 10:9:81 in a mixed solvent of n-propanol / water at a mass ratio of 80 / 20 were used as polymer particles PP-1. The volume average particle size of polymer particles PP-1 was 193 nm.

[0937] -Polymer particles PP-2-

[0938] As polymer particles PP-2, a microgel solution containing the following components was used.

[0939] Microgel (polymer particles PP-2): 2.640 parts

[0940] Distilled water: 2.425 parts

[0941] The method for preparing the microgel used in the above-mentioned microgel solution is shown below.

[0942] -Preparation of polyisocyanate compounds-

[0943] 0.043 parts of bismuth tris(2-ethylhexanoate) (NEOSTANN U-600, manufactured by NITTO KASEI CO., LTD.) was added to a suspension of 17.78 parts (80 molar equivalents) of isophorone diisocyanate and 7.35 parts (20 molar equivalents) of a polyphenol compound (1) represented by the following structural formula in ethyl acetate (25.31 parts) and stirred. When heat generation stopped, the reaction temperature was set to 50° C. and stirred for 3 hours to obtain an ethyl acetate solution (50% by mass) of the polyisocyanate compound (1).

[0944] [Chemical formula 18]

[0945]

[0946] - Preparation of microgels -

[0947] The following oil phase components and aqueous phase components were mixed and emulsified at 12,000 rpm for 10 minutes using a homogenizer. After stirring the obtained emulsion at 45°C for 4 hours, 5.20 g of a 10% aqueous solution of 1,8-diazabicyclo[5.4.0]undec-7-ene-octanoate (U-CAT SA102, manufactured by San-Apro Ltd.) was added, stirred at room temperature for 30 minutes, and allowed to stand at 45°C for 24 hours. The solid content concentration was adjusted to 20% by mass with distilled water to obtain an aqueous dispersion of microgel (1). The average particle size was measured by light scattering method and was found to be 0.28 μm.

[0948] ~Oil phase ingredients~

[0949] (Component 1) Ethyl acetate: 12.0 parts

[0950] (Component 2) an adduct prepared by adding trimethylolpropane (6 mol equivalents) to xylene diisocyanate (18 mol equivalents) and adding mono-terminal methylated polyoxyethylene (1 mol equivalent, number of repeating oxyethylene units: 90) (50 mass % ethyl acetate solution, manufactured by Mitsui Chemicals, Inc.): 3.76 parts

[0951] (Component 3) Polyisocyanate compound (1) (as a 50% by mass ethyl acetate solution): 15.0 parts

[0952] (Component 4) 65 mass % ethyl acetate solution of dipentaerythritol pentaacrylate (SR-399, manufactured by Sartomer Company, Inc.): 11.54 parts

[0953] (Component 5) 10% ethyl acetate solution of sulfonate surfactant (PIONIN A-41-C, manufactured by Takemoto Oil & Fat Co., Ltd.): 4.42 parts

[0954] ~Water phase components~

[0955] Distilled water: 46.87 parts

[0956] -Polymer particles PP-3-

[0957] The polymer particles PP-3 were prepared by the following method.

[0958] A polyfunctional isocyanate compound (PM-200: manufactured by Wanhua Chemical Co.): 6.66 parts; a 50% by mass ethyl acetate solution of "Takenate (registered trademark) D-116N (an adduct of trimethylolpropane, meta-xylylene diisocyanate and polyethylene glycol monomethyl ether (E090) (the structure described below))" manufactured by Mitsui Chemicals, Inc.: 5.46 parts; a 65% by mass ethyl acetate solution of dipentaerythritol pentaacrylate (SR-399, manufactured by Sartomer Company, Inc., M-2 described below): 11.53 parts; ethyl acetate: 18.66 g and PIONIN (registered trademark) A-41-C manufactured by Takemoto Oi1 & Fat Co., Ltd.: 0.45 parts were mixed and stirred at room temperature (25°C) for 15 minutes to obtain an oil phase component.

[0959] 46.89 parts of pure water as a water phase component was added to the obtained oil phase component and mixed, and the obtained mixture was emulsified at 12,000 rpm for 12 minutes using a homogenizer to obtain an emulsion.

[0960] The obtained emulsion was added to 16.66 parts of distilled water, and then the stirred liquid was heated to 45°C and stirred for 4 hours while the liquid temperature was kept at 45°C, thereby distilling off ethyl acetate from the above liquid. Next, the liquid from which ethyl acetate was distilled off was heated to 45°C and stirred for 48 hours while the liquid temperature was kept at 45°C, thereby obtaining microcapsule-type internal polymer particles PP-3 based on addition-polymerized resin in the liquid. Next, the liquid containing the internal polymer particles PP-3 was diluted with distilled water so that the solid content concentration became 20% by mass, thereby obtaining an aqueous dispersion of the internal polymer particles PP-3.

[0961] The volume average particle size of the included polymer particles PP-3 was measured by a laser diffraction / scattering particle size distribution analyzer LA-920 (manufactured by Horiba, Ltd.) and found to be 200 nm. The content of the polymerizable compound M-2 in the total mass of the included polymer particles PP-3 was 42% by mass.

[0962] [Chemical formula 19]

[0963]

[0964] (Binder polymer)

[0965] As the binder polymer, the following polymer BP-1 was used.

[0966] BP-1: Polyvinyl acetal ("S-LEC BL10" manufactured by SEKISUI CHEMICAL C0., LTD.)

[0967] (Hydrophilic Compounds)

[0968] As the hydrophilic compound, the following compounds H-1 and H-2 were used.

[0969] H-1: Hydroxypropyl methylcellulose (5% aqueous solution) in which 30% of the methoxylated cellulose is present and 10% of the hydroxypropyloxylated cellulose is present. The viscosity of a 2% by mass aqueous solution of the compound H-1 at 20° C. is 5 mPa·s.

[0970] H-2: A compound represented by the following structural formula.

[0971] [Chemical formula 20]

[0972]

[0973] (Hydrophobic Compounds)

[0974] As the hydrophobic compound, the following compound P-1 was used.

[0975] ·P-1: Phenothiazine

[0976] ·P-2: Tricresyl phosphate

[0977] (Surfactant)

[0978] As surfactants, the following compounds S-1 and S-2 were used.

[0979] W-1: a xylene / methoxypropyl acetate solution containing 25% by mass of a modified polydimethylsiloxane copolymer ("BYK336" manufactured by BYK Chemie).

[0980] W-2: A compound represented by the following structural formula.

[0981] [Chemical formula 21]

[0982]

[0983] <Preparation of coating liquid A-1>

[0984] A coating liquid A-1 was prepared by mixing an acid colorant S-4, an infrared absorber IR-1, a polymerization initiator I-1, polymerizable compounds M-1 and M-2, polymer particles PP-1, a hydrophilic compound H-1, a surfactant S-1 and a mixed solvent of 1-methoxy-2-propanol: methyl ethyl ketone: methanol = 4:4:1 (mass ratio).

[0985] The content (addition amount) of each component other than the mixed solvent contained in the coating liquid A-1 is shown in Table 3 described later. In addition, in each Example and each Comparative Example, when preparing each coating liquid including the coating liquid A-1, the amount of the mixed solvent was adjusted so that the solid content became 6 mass %.

[0986] <Preparation of coating liquids A-2 to A-38 and coating liquids A-C1 to A-C3>

[0987] Coating solutions A-2 to A-38 and A-C1 to A-C3 were prepared in the same manner as coating solution A-1, except that the types and contents (addition amounts) of the components used to prepare the coating solution were changed so as to have the compositions shown in Table 3 described later.

[0988] Table 3 below shows the compositions of coating solutions A-2 to A-38 and coating solutions A-C1 to A-C3 for forming the image recording layer.

[0989] In the table, the column "acid color former / polymerization initiator" shows the molar ratio of the content of the polymerization initiator to the content of the acid color former contained in each coating liquid.

[0990] In the table, "specific energy difference" represents the value (unit: eV) obtained by dividing the lowest unoccupied molecular orbital (LUM0) of the electron accepting polymerization initiator by the lowest unoccupied molecular orbital (LUMO) of the infrared absorber in a coating solution containing the electron accepting polymerization initiator and the infrared absorber.

[0991] [Table 3]

[0992]

[0993] [Table 4]

[0994]

[0995] [Table 5]

[0996]

[0997] [Example 1]

[0998] The surface of the anodized film side of the support body 1 produced in Production Example B1 was coated with a dry coating amount of 0.03 g / m 2 The primer coating liquid 1 was applied in a manner of , dried at 120° C. for 40 seconds, and cooled to 20 to 27° C., thereby forming a primer layer 1 .

[0999] The coating liquid A-1 (image recording layer coating liquid) prepared by the above method was bar-coated on the surface of the formed undercoat layer 1, and dried at 120° C. for 40 seconds to form a dry coating amount of 1.0 g / m2 The image recording layer 1 is formed on the support 1, the undercoat layer 1 and the image recording layer 1, thereby producing a planographic printing plate precursor 1 in which the support 1, the undercoat layer 1 and the image recording layer 1 are stacked.

[1000] [Example 2 to Example 24, Comparative Example 1 to Comparative Example 3]

[1001] Planographic printing plate precursors each having a laminated support, an undercoat layer, and an image recording layer were prepared according to the method described in Example 1 except that the support described in Table 4 described later was used instead of the support 1.

[1002] [Examples 25 to 48, Examples 61 to 64, Comparative Examples 4 to 6]

[1003] Planographic printing plate precursors each having a support, an undercoat layer and an image recording layer laminated thereon were prepared according to the method described in Example 1 except that the image recording layer coating liquid described in Table 5 described later was used instead of coating liquid A-1.

[1004] [Examples 49 to 51]

[1005] Planographic printing plate precursors each having a support, an undercoat layer, and an image recording layer laminated thereon were prepared in the same manner as in Example 1 except that undercoat layer coating liquids 2 to 4 were used instead of undercoat layer coating liquid 1.

[1006] In Examples 49 and 50, the surface of the anodized film side of the support 1 was coated with a dry amount of 0.1 g / m 2 The primer coating liquid 2 and the primer coating liquid 3 were applied in a manner to form respective primer layers.

[1007] [Example 52 to Example 56]

[1008] The support 23 manufactured in Manufacturing Example B23 was used instead of the support 1, the undercoat coating liquid 2 was used instead of the undercoat coating liquid 1, and the image recording layer coating liquid described in Table 5 described later was used instead of the coating liquid A-1. In addition, a laminate consisting of a support, an undercoat layer and an image recording layer was prepared according to the method described in Example 1.

[1009] Next, the protective layer coating liquid 1 described below was bar-coated on the surface of the image recording layer of each laminated body produced, and dried at 120° C. for 60 seconds to form a dry coating amount of 0.1 g / m 2 A protective layer 1 was formed, and a planographic printing plate precursor was prepared by laminating a support, an undercoat layer, an image recording layer and a protective layer.

[1010] (Protective layer coating liquid 1)

[1011] The following components were mixed to prepare a protective layer coating liquid 1.

[1012] Water: 3.0581 parts

[1013] METOLOSE SM04 (methylcellulose, manufactured by Shin-Etsu Chemical Co., Ltd., methoxyl substitution degree = 1.8): 0.1250 parts

[1014] Inorganic layer compound dispersion (1): 0.3375 parts

[1015] · Hydrophilic polymer (1) represented by the following structural formula (Mw: 30,000) (solid content 20% by mass): 0.0825 parts

[1016] · RAPISOL A-80 (anionic surfactant, manufactured by NOF CORPORATION, 80 mass % aqueous solution): 0.0094 parts

[1017] The inorganic layer compound dispersion (1) was prepared by adding 6.4 parts of synthetic mica ("SOMASIF ME-100" manufactured by Co-op Chemical Co., Ltd.) to 193.6 parts of ion exchange water and dispersing the mixture using a homogenizer until the volume average particle size (laser scattering method) became 3 μm. The aspect ratio of the obtained dispersed particles was 100 or more.

[1018] [Chemical formula 22]

[1019]

[1020] [Example 57 to Example 60]

[1021] In addition to using the support 24 manufactured in Manufacturing Example B24 instead of the support 1, directly forming the image recording layer on the surface of the anodized coating side of the support 24 without forming a primer layer, and using the image recording layer coating liquid described in Table 5 described later instead of the coating liquid A-1, a laminate consisting of a support and an image recording layer was prepared according to the method described in Example 1.

[1022] Next, the protective layer coating liquid 2 described below was bar-coated on the surface of the image recording layer of each laminated body produced, and dried at 120° C. for 60 seconds to form a dry coating amount of 0.8 g / m 2 A protective layer 2 was formed, and a planographic printing plate precursor was prepared by laminating a support, an image recording layer and a protective layer.

[1023] (Protective layer coating liquid 2)

[1024] The following components were mixed to prepare a protective layer coating liquid 2.

[1025] · Polyvinyl alcohol ("CKS50" manufactured by Nippon Synthetic Chemical Industry Co., Ltd., sulfonic acid modified, saponification degree 99 mol% or more, polymerization degree 300) 6 mass% aqueous solution: 10 parts

[1026] Polyvinyl pyrrolidone (RUBISCOAL K-17, manufactured by BASF): 1 part

[1027] · RAPISOL A-80 (anionic surfactant, manufactured by NOF CORPORATION): 0.001 part

[1028] Ion exchange water: 6.0 parts

[1029] wIR-1 (decomposable infrared absorber, the following compound): 0.01 part

[1030] [Chemical formula 23]

[1031]

[1032] [evaluate]

[1033] The following properties were evaluated for the lithographic printing plate precursors produced in each of the Examples and Comparative Examples.

[1034] <Visual Recognition>

[1035] The obtained planographic printing plate precursor was exposed to light at a wavelength of 120 mJ / cm using an exposure machine equipped with an infrared semiconductor laser of 830 nm (Luxel PLATESETTER T-6000III manufactured by Fujifilm Corporation). 2 The exposure was carried out in the manner of exposure amount. The characters of "Fuj" exposed in the exposure image became the image of the exposure part with a size of 3 to 14 dots. Under a white light of 800 lux, the exposed lithographic printing plate original was placed vertically relative to the ground, and the tester stood at a distance of 1m from the plate after exposure, and evaluated the number of dots of the smallest character that could be accurately read with both eyes. The evaluation was carried out within 30 minutes after the lithographic printing plate original was exposed. The average value of 10 testers was calculated, and the visual recognition was evaluated according to the following standards. The evaluation of visual recognition is preferably A, B or C, more preferably A or B, and further preferably A.

[1036] (Visual recognition evaluation standard)

[1037] A: 3 points or more and less than 5 points

[1038] B: 5 points or more and less than 6 points

[1039] C: 6 points or more and less than 7 points

[1040] D: 7 points or more and less than 9 points

[1041] E: 9 points or more and less than 11 points

[1042] F: 11 o'clock or above

[1043] <Time-related spotty hair color problems>

[1044] The obtained planographic printing plate precursor was cut into a size of 40 cm in width and 60 cm in length, stored with backing paper at 25°C and 70% RH for 1 hour for humidity adjustment, then wrapped with aluminum kraft paper and heated in an oven set at 60°C for 5 days.

[1045] Then, the temperature was lowered to room temperature and the planographic printing plate was taken out and observed through a 25x magnifying glass to calculate the number of 2 The number of spot-like color development failures with a major diameter of 20 μm or more was calculated at 5 different locations, and the color development failures over time were evaluated based on the average number according to the following evaluation criteria.

[1046] (Evaluation criteria for spotty coloration failure over time)

[1047] 10: There are less than 5 spots of hair color failure (80cm 2 ).

[1048] 9: 6 to 10 spots of hair color failure (80cm 2 ).

[1049] 8: Spot-like color failure is 11 to 20 (80cm 2 ).

[1050] 7: Spot-like color failure is 21 to 30 (80cm 2 ).

[1051] 6: Spot-like color failure is 31 to 40 (80cm 2 ).

[1052] 5: Spot-like color failure is 41 to 50 (80 cm 2 ).

[1053] 4: Spot-like color failure is 51 to 60 (80 cm 2 ).

[1054] 3: Spot-like color failure is 61 to 80 (80 cm 2 ).

[1055] 2: Spot-like color failure is 81 to 100 (80cm 2 ).

[1056] 1: There are more than 101 spots of hair color failure (80cm 2 ).

[1057] <Corrosion Contamination Inhibition>

[1058] The obtained planographic printing plate precursor was stored together with interleaving paper at 25° C. and 70% RH for 1 hour to adjust the humidity, and then wrapped with aluminum kraft paper and heated in an oven set at 60° C. for 5 days.

[1059] Then, after the temperature was lowered to room temperature, the plate was mounted on the plate cylinder of a printing press "LITHRONE 26" (manufactured by KOMORI Corporation) without developing. A fountain solution of Ecolity-2 (manufactured by Fujifilm Corporation) / tap water = 2 / 98 (volume ratio) and Values-G (N) black ink (manufactured by Dainippon Ink and Chemicals, Inc.) were used, and the fountain solution and ink were supplied by the standard automatic printing start method of the above-mentioned printing press, and after on-press development, printing was performed on 500 sheets of Tokubishi coated paper (ream weight: 76.5 kg, manufactured by MITSUBISHIPAPER MILLS LIMITED.).

[1060] Check the 500th print with a magnifying glass (25x magnification) and calculate the number of prints per 80 cm. 2 The number of printed contaminations (micro corrosion contaminations) with a length of 20 μm or more was counted, and the corrosion contamination inhibition property was evaluated according to the following evaluation criteria.

[1061] (Evaluation criteria for corrosion contamination inhibition)

[1062] 10: Minor corrosion contamination is less than 5 (per 80cm 2 ).

[1063] 9: 6 to 10 micro-corrosion contaminations (per 80 cm 2 ).

[1064] 8: Minor corrosion pollution is 11 to 20 (every 80cm 2 ).

[1065] 7: Minor corrosion pollution is 21 to 30 (per 80cm 2 ).

[1066] 6: 31 to 40 micro-corrosion contaminations (per 80 cm 2 ).

[1067] 5: Minor corrosion pollution is 41 to 50 (per 80cm 2 ).

[1068] 4: Minor corrosion pollution is 51 to 60 (per 80cm 2 ).

[1069] 3: Minor corrosion pollution is 61 to 80 (per 80cm 2 ).

[1070] 2: 81 to 100 micro-corrosion contaminations (per 80 cm 2 ).

[1071] 1: Minor corrosion contamination is more than 101 (every 80cm 2 ).

[1072] <Brush resistance>

[1073] The lithographic printing plate precursor prepared in the above manner was exposed (equivalent to an irradiation energy of 110 mJ / cm2) using an exposure machine equipped with an infrared semiconductor laser ("Magnus 800 Quantum" manufactured by Kodak) at an output of 27 W, an external drum rotation speed of 450 rpm, and a resolution of 2,400 dpi (dots per inch, 1 inch is 2.54 cm). 2 ). The exposure image includes a solid image and an AM screen (Amplitude Modulation Screen) 3% dot image.

[1074] The exposed original plate thus obtained was mounted on the cylinder of a printing press "SX-74" manufactured by Heidelberger Druckmaschinen AG, which was 939 mm long and 636 mm wide (chrysanthemum plate size) without being subjected to development treatment. A fountain solution circulation tank with a capacity of 100 L and a built-in non-woven filter and temperature control device was connected to the printing press. 80 L of 2.0% fountain solution S-Z1 (manufactured by Fujifilm Corporation) was loaded into the circulation device, and T&K UVOFSK-HS ink GE-M (manufactured by T&K TOKA Corporation) was used as the printing ink. After supplying the fountain solution and ink by a standard automatic printing start method, printing was performed on TOKUBISHI copperplate (manufactured by Mitsubishi Paper Mills Limited, ream weight 76.5 kg) paper at a printing speed of 10,000 sheets per hour.

[1075] As the number of printed sheets increases, the image part gradually wears away and the ink concentration on the printed material decreases. The dot area ratio of 3% dots of AM screen in the printed material was measured using a Gretag densitometer (manufactured by Gretag Macbeth). The number of printed sheets when the measured value obtained dropped by 1% from the measured value of the 500th printed sheet was set as the number of printed sheets at the end of printing. The relative printing durability when the number of printed sheets was 50,000 was taken as 100 was calculated by the following formula, and the printing durability was evaluated. The larger the value, the better the printing durability.

[1076] Relative printing durability = (number of printed sheets of the target lithographic printing plate precursor) / 50,000×100

[1077] (Evaluation criteria for brush durability)

[1078] 10: Relative brushing durability is 99% or more.

[1079] 9: Relative brushing durability is 90% or more and less than 99%.

[1080] 8: Relative brushing durability is 80% or more and less than 90%.

[1081] 7: Relative brushing durability is 70% or more and less than 80%.

[1082] 6: Relative brushing durability is 60% or more and less than 70%.

[1083] 5: Relative brushing durability is 50% or more and less than 60%.

[1084] 4: Relative brushing durability is 40% or more and less than 50%.

[1085] 3: The relative brushing durability is 30% or more and less than 40%.

[1086] 2: The relative brushing durability is 20% or more and less than 30%.

[1087] 1: Relative brushing resistance is less than 20%.

[1088] <On-press development>

[1089] The obtained planographic printing plate precursor was exposed using an exposure machine equipped with an infrared semiconductor laser (LuxelPLATESETTER T-6000III manufactured by Fujifilm Corporation) at an external drum rotation speed of 1000 rpm, a laser output of 70% and a resolution of 2,400 dpi. The exposure was set to image exposure including a solid image and a 50% dot pattern of FM (Frequency Modulation) screening in the exposure image.

[1090] The lithographic printing plate precursor without image exposure was mounted on the plate cylinder of a printing press "LITHRONE 26" (manufactured by KOMORI Corporation) without development treatment. Using a fountain solution of Ecolity-2 (manufactured by Fujifilm Corporation) / tap water = 2 / 98 (volume ratio) and Values-G (N) black ink (manufactured by Dainippon Ink and Chemicals, Inc.), the fountain solution and ink were supplied by the standard automatic printing start method of the above-mentioned printing press and after on-press development, it was printed on 100 sheets of Tokubishi coated paper (ream weight: 76.5 kg, manufactured by MITSUBISHI PAPER MILLS LIMITED.) at a printing speed of 10,000 sheets per hour.

[1091] After the unexposed portion of the 50% halftone dot pattern was developed on the printing press, the number of sheets of printing paper required until the ink was not transferred to the halftone dot non-image portion (hereinafter also referred to as "wasted paper count") was measured. The on-press developability was evaluated based on the measured number of wasted paper and the following criteria. As described below, it can be said that the smaller the number of wasted paper, the better the on-press developability.

[1092] (Evaluation criteria for on-press development)

[1093] 10: The number of damaged paper sheets is less than 5.

[1094] 9: The number of damaged papers is 6 to 10.

[1095] 8: The number of damaged papers is 11 to 15 sheets.

[1096] 7: The number of damaged papers is 16 to 19 sheets.

[1097] 6: The number of damaged papers is 20 to 25 sheets.

[1098] 5: The number of damaged papers is 26 to 29 sheets.

[1099] 4: The number of damaged papers is 30 to 34 sheets.

[1100] 3: The number of damaged papers is 35 to 39 sheets.

[1101] 2: The number of damaged papers is 40 to 50 sheets.

[1102] 1: The number of damaged paper sheets is 51 or more.

[1103] <Scratch resistance>

[1104] The scratch resistance was evaluated using a surface property measuring machine TRIBOGEAR TYPE: 18LFW (manufactured by Shinto Scientific Co., Ltd.). A sapphire needle (0.1 mm) was used for each planographic printing plate precursor at 5 g / m 2 Scale from 10g / m 2 Up to 90g / m 2 The load was changed until 2000, and the planographic printing plate precursor was scanned at a scanning speed of 20 mm / s to cause scratches. The scratched planographic printing plate precursor was used for on-press development and printing, and the presence of scratch contamination on the 100th sheet after the start of printing was confirmed at each load. The scratch resistance of each planographic printing plate precursor was evaluated based on the following criteria based on the results of the lightest load among the loads that caused scratch contamination.

[1105] (Scratch resistance evaluation standard)

[1106] 10: Even 90g / m 2 No scratch contamination will occur under load.

[1107] 9: 90g / m 2 Scratch contamination occurs under load.

[1108] 8: 85g / m 2 Scratch contamination occurs under load.

[1109] 7: 75 or 80g / m 2 Scratch contamination occurs under load.

[1110] 6: 65 or 70g / m 2 Scratch contamination occurs under load.

[1111] 5: 55 or 60g / m 2 Scratch contamination occurs under load.

[1112] 4: 45 or 50g / m 2 Scratch contamination occurs under load.

[1113] 3: 35 or 40g / m 2 Scratch contamination occurs under load.

[1114] 2: 25 or 30g / m 2 Scratch contamination occurs under load.

[1115] 1: at 20g / m 2 Scratch contamination occurs under loads below 0.05.

[1116] Tables 4 and 5 show the formulations and evaluation results of each example and each comparative example.

[1117] [Table 6]

[1118]

[1119] [Table 7]

[1120]

[1121] As is clear from Tables 4 and 5, the lithographic printing plate precursors according to Examples are superior to the lithographic printing plate precursors according to Comparative Examples in terms of suppression of color development failure after aging and visibility.

[1122] Explanation of symbols

[1123] ta-anodic reaction time, tc-cathode reaction time, tp-time from 0 to peak current, Ia-peak current on the anode circulation side, Ic-peak current on the cathode circulation side, 1-aluminum alloy plate, 2, 4-roller brush, 3-polishing slurry, 5, 6, 7, 8-support roller, 10-lithographic printing plate original, 11-support body, 12-image recording layer, 13-aluminum alloy plate, 14, 14A, 14B-anodized film, 20, 30-micropores, 21, 31-film surface, 22-large diameter pores, 22A, 24A, 32A, 34A, 36A-bottom, 23, 33, 35-connection position, 24- Small diameter hole portion, 32-upper hole portion, 34-middle hole portion, 36-lower hole portion, 50-main electrolytic cell, 51-AC power supply, 52-radial drum roller, 53a, 53b-main pole, 54-electrolyte supply port, 55-electrolyte, 56-slit, 57-electrolyte channel, 58-auxiliary anode, 60-auxiliary anode tank, W-aluminum alloy plate, 610-anodic oxidation treatment device, 612-power supply tank, 614-electrolytic treatment tank, 616-aluminum alloy plate, 618, 626-electrolyte, 620-power supply electrode, 622, 628-roller, 624-clamping roller, 630-electrolytic electrode, 632-tank wall, 634-DC power supply.

Claims

1. A lithographic printing plate precursor, which is an on-press developing type lithographic printing plate precursor having a support and an image recording layer, The support body comprises an aluminum alloy plate and an anodized film disposed on the aluminum alloy plate. The density of the intermetallic compounds having a major diameter of 2.0 μm or more on the surface of the support opposite to the image recording layer is 1000 / mm 2 the following, The image recording layer contains an infrared absorber and an acid color former, The color development coefficient of the acid coloring agent determined by the following measurement X is 20,000 or more, Determination of X: Using a solution obtained by mixing 1 mL of a first acetonitrile solution having a concentration of 0.02 mmol / L of the acid coloring agent, 1 mL of a second acetonitrile solution having a concentration of 0.02 mmol / L of 10-camphorsulfonic acid, 5 mL of water, and 93 mL of acetonitrile, ultraviolet-visible absorption spectrum measurement was performed under the condition that the optical path width of the measurement unit was 10 mm. When the absorbance at the maximum absorption wavelength was defined as Amax, the value obtained by formula (1) was defined as the color development coefficient. Formula (1) Color development coefficient (L·mol -1 cm -1 )=Amax / {(0.0002mmol / L)×(1cm)}.

2. The lithographic printing plate precursor according to claim 1, wherein The density of the intermetallic compounds having a major diameter of 2.0 μm or more on the surface of the support opposite to the image recording layer is 500 / mm 2 the following.

3. The lithographic printing plate precursor according to claim 1, wherein The density of the intermetallic compounds having a major diameter of 2.0 μm or more on the surface of the support opposite to the image recording layer is 10 / mm 2 the following.

4. The lithographic printing plate precursor according to claim 1, wherein The density of the recessed portions having a depth of 0.7 μm or more from the average surface obtained by measuring the range of 400 μm×400 μm on the surface of the anodized film side of the support body using a non-contact three-dimensional roughness meter was 3000 / mm 2 above.

5. The lithographic printing plate precursor according to claim 1, wherein The surface area ratio ΔS calculated by the following formula (S1) is 25% or more based on the actual area Sx obtained by the approximate three-point method based on the three-dimensional data obtained by measuring 256×256 points in a range of 25μm×25μm on the surface of the anodized film side of the support using an atomic force microscope and the geometrically measured area S0 of the surface of the anodized film side of the support, ΔS=(Sx-S0) / S0×100(%) (S1).

6. The lithographic printing plate precursor according to claim 1, wherein The anodized film has micropores extending from the surface of the anodized film in a depth direction. The micropores include: a large-diameter pore portion extending from the surface of the anodized film in the depth direction; and a small-diameter pore portion communicating with the bottom of the large-diameter pore portion and extending in the depth direction. The average diameter of the large-diameter pores on the surface of the anodized film is 15 nm to 50 nm. The depth of the large-diameter pores is 30 nm to 1000 nm. The average diameter of the small-diameter pore portion at the communicating position with the large-diameter pore portion is 15 nm or less, The depth of the small-diameter pores is 300 nm to 3000 nm.

7. The lithographic printing plate precursor according to claim 1, wherein The anodized film has micropores extending from the surface of the anodized film in a depth direction. The micropores include: an upper hole portion extending from the surface of the anodized film in a depth direction; a middle hole portion communicating with the bottom of the upper hole portion and extending in the depth direction; and a lower hole portion, which is connected to the bottom of the middle hole portion and extends to the bottom of the micropore along the depth direction, The average diameter of the upper pores on the surface of the anodized film is 15 nm to 50 nm. The depth of the upper hole is 30nm to 1000nm, The maximum diameter of the middle pores is 20 nm to 100 nm and is larger than the average diameter of the upper pores on the surface of the anodized film. The average diameter of the lower pores at the communicating position with the middle pores is 20 nm or less, The depth of the lower hole portion is 500nm to 3000nm.

8. The lithographic printing plate precursor according to claim 1, wherein The anodized film has micropores extending from the surface of the anodized film in a depth direction. The density of the micropores on the surface of the anodized film is 400 pores / μm 2 ~1500 / μm 2 , The opening ratio of the surface of the anodized film due to the micropores is 30% to 85%.

9. The lithographic printing plate precursor according to claim 1, wherein The color development coefficient of the acid color developing agent determined by the measurement X is 20,000 to 100,000.

10. The lithographic printing plate precursor according to claim 1, wherein The color body generated from the acid color forming agent has an absorption maximum wavelength λmax in the wavelength range of 380 nm to 750 nm in the range of 500 nm to 650 nm.

11. The lithographic printing plate precursor according to claim 1, wherein The acid coloring agent has at least one of the groups represented by the following formulae (1a) to (1d), In the formula, R 1 and R 2 represents a portion connected to the core structure of the acid chromogen, R 3 represents an aryl or heteroaryl group, R 4 represents an aryl or heteroaryl group, R 5 represents a hydrocarbon group, X represents a leaving group.

12. The lithographic printing plate precursor according to claim 11, wherein The acid coloring agent has any of the structures represented by the following formulae (2a) to (2f), In the formula, structure b represents a structure that is ring-opened or cleaved when in contact with an electron-accepting compound, R1 to R9 each independently represent a hydrogen atom, an alkyl group or an alkoxy group.

13. The lithographic printing plate precursor according to claim 11, wherein The acid coloring agent comprises a compound represented by the following formula (3a) or a compound represented by the following formula (3b), In formula (3a), Ar1 and Ar2 each independently represent an aryl group which may have a substituent or a heteroaryl group which may have a substituent, R 10 and R 11 each independently represents a hydrogen atom, an alkyl group, an aryl group which may have a substituent, or a heteroaryl group which may have a substituent, In formula (3b), ERG each independently represents an electron donating group, n represents an integer from 1 to 5, X1 to X4 each independently represent a hydrogen atom, a halogen atom or a monovalent organic group, Y1 and Y2 each independently represent C or N, When Y1 is N, X1 does not exist. When Y2 is N, X4 does not exist. R 12 and R 13 Each independently represents a hydrogen atom, an alkyl group, an aryl group which may have a substituent, or a heteroaryl group which may have a substituent.

14. The lithographic printing plate precursor according to claim 1, wherein The image recording layer further comprises a polymerization initiator, The polymerization initiator includes an electron accepting polymerization initiator and an electron donating polymerization initiator.

15. The lithographic printing plate precursor according to claim 14, wherein The electron-accepting polymerization initiator is an onium salt compound, The electron donating polymerization initiator is a borate compound.

16. The lithographic printing plate precursor according to claim 14, wherein The total content of the electron accepting polymerization initiator and the electron donating polymerization initiator is 1.0 molar equivalent or more relative to the content of the acid color forming agent.

17. The lithographic printing plate precursor according to claim 14, wherein The value obtained by subtracting the lowest unoccupied molecular orbital of the infrared absorber from the lowest unoccupied molecular orbital of the electron accepting polymerization initiator is 0.55 eV or less.

18. The lithographic printing plate precursor according to claim 1, wherein The image-recording layer further comprises polymer particles.

19. The lithographic printing plate precursor according to claim 18, wherein The polymer particles are microgels.

20. The lithographic printing plate precursor according to claim 18, wherein The polymer particles include a polymer having a hydrophobic backbone, The polymer comprises structural units having pendant cyano groups directly bonded to the hydrophobic backbone and structural units having pendant groups comprising hydrophilic polyalkylene oxide segments.

21. The lithographic printing plate precursor according to claim 1, wherein The infrared absorbent includes a decomposable infrared absorbent that is decomposed by exposure to infrared rays.

22. The lithographic printing plate precursor according to claim 21, wherein The decomposable infrared absorber is a compound represented by the following formula (A): In the formula, R 1 Indicates that R 1 -L bond cleavage group, R 11 ~R 18 Each independently represents a hydrogen atom, a halogen atom, -Ra, -ORb, -SRc or -NRdRe, Ra to Re each independently represent a hydrocarbon group, A1, A2 and multiple R 11 ~R 18 are optionally linked to form a single ring or multiple rings, A1 and A2 each independently represent an oxygen atom, a sulfur atom or a nitrogen atom, n 11 and n 12 Each independently represents an integer from 0 to 5, wherein n 11 and n 12 The total of is 2 or more, n 13 and n 14 Each independently represents 0 or 1, L represents an oxygen atom, a sulfur atom or -NR 10 -, R 10 represents a hydrogen atom, an alkyl group or an aryl group, Za represents a counter ion for neutralizing the charge.

23. The lithographic printing plate precursor according to claim 1, further comprising a protective layer on the image recording layer.

24. The lithographic printing plate precursor according to claim 23, wherein The protective layer comprises a chromogen precursor.

25. The lithographic printing plate precursor according to claim 24, wherein The color body precursor contains an infrared absorber.

26. The lithographic printing plate precursor according to claim 24, wherein The color body precursor includes a decomposable infrared absorber that is decomposed by exposure to infrared rays.

27. A method for manufacturing a lithographic printing plate, comprising: an exposure step of exposing the image recording layer of the planographic printing plate precursor according to any one of claims 1 to 26 in an image-like manner to form exposed areas and unexposed areas; and In the on-press development step, at least one of printing ink and fountain solution is supplied on a printing press to remove unexposed portions of the image recording layer exposed in an image form, thereby producing a planographic printing plate.

28. A printing method comprising: An exposure step of exposing the image recording layer of the planographic printing plate precursor according to any one of claims 1 to 26 in an image-like manner to form exposed areas and unexposed areas; an on-press development step of supplying at least one of printing ink and fountain solution on a printing press to remove unexposed portions of the image recording layer exposed in an image form, thereby producing a planographic printing plate; and The printing process is to print using the prepared lithographic printing plate.

Citation Information

Patent Citations

  • Aluminum alloy plate for printing plate and manufacturing method thereof

    CN102618756A

  • Lithographic printing plate support, lithographic printing plate support manufacturing method and lithographic printing plate master

    CN104066591A

  • Original plate for on-press development type lithographic printing plate, method for fabricating lithographic printing plate, and lithographic printing method

    CN114051598A

  • Lithographic printing plate precursors and methods of use

    CN114502378A

  • Lithographic printing method

    CN114845875A